Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Shifting shorelines and hydroclimate changes in southern South Africa: Insights from sediment provenance during the Middle Stone Age (90-50 ka) - E.J. Pryor; M.H. Simon; H.J.L. van der Lubbe; M. Andersen; A. Alsgaard; O.M. Göktürk; M. Cendrowska; A. Muller; K.G.R. Purcell; S. Slater-Lewis; A. Starr; I.R. Hall (Quaternary Science Reviews, 2026)

Red tides, blue holes, and the importance of groundwater and terrestrial sources of nutrients fueling blooms of Karenia brevis - Patricia M. Glibert; Cynthia A. Heil; Emily R. Hall; Cong Fei; Shady A. Amin (Harmful Algae, 2026)

Scheduling follow-up observations of energetic transients with the neutrino target scheduler (NuTS) - Tobias Heibges; Claire Guépin; Luke Kupari; Hannah Wistrand; Randy Lahm; Johannes Eser; Mary Hall Reno; Tonia M. Venters; Lawrence Wiencke (Computer Physics Communications, 2026)

“It's a good reason to get up every morning!”: Perspectives on how feeding and observing birds affects people’s wellbeing - Kelley E. Langhans; Ashley A. Dayer; Caren Cooper; Alia M. Dietsch; Richard J. Hall; Dana M. Hawley; Wesley M. Hochachka; Becki Lawson; Freya McGregor; Tina B. Phillips; Tammah Watts (Ambio, 2026)
In light of growing mental health challenges globally, understanding the positive impacts of nature on mental wellbeing is more important than ever. However, the impacts of one of the most common intentional human–wildlife interactions, feeding wild birds, are not well understood. We surveyed 3658 participatory scientists in the USA and Canada who take part in Project FeederWatch to examine associations between wellbeing and bird feeding. Quantitative data showed that most respondents thought feeding and observing birds had a positive impact on their wellbeing over six months of participation, even when other events in their lives did not. Qualitative data revealed that feeding and observing birds positively impacted respondent wellbeing through their emotions, engagement with the activity, and creating a sense of meaning. These findings suggest linkages between bird feeding and positive mental health, while underscoring a need for further research on the mechanisms through which these linkages operate.

Evaluation of DNA and collagen preservation in Late Pleistocene and Holocene bovid fossils from South Africa - Deon de Jager; Andi M. Wilson; Alba Rey-Iglesia; J. Tyler Faith; Kaedan O'Brien; Wendy Black; Wilhelmina Seconna; Olivia Hall; Paul Szpak; Eline D. Lorenzen (Quaternary Science Reviews, 2026)

Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Lessons learned: drivers of non-response in a large population-based cohort study of Black women - Jeuneviette E. Bontemps-Jones; Lauren E. McCullough; Elizabeth G. Kirkland; Lauren R. Teras; Maddison L. Hall; Peter J. Briggs; Daniela M. Dudas; Maria Moore; Jamal Winn; Alpa V. Patel (Cancer Causes & Control, 2026)

Cognitive components derived from traditional neuropsychological tests and their associations with plasma p-tau217 and p-tau181 in mild cognitive impairment: a multisite analysis - Ana Perez; Hugo Lewi Hammer; Vebjørn Andersson; Timo Saarinen; Soraya Alfonsín; Guido Maria Giuffrè; Naike Caraglia; Noemi Martellacci; Federico Ramírez-Toraño; Thomas Tveitstøl; Antti Kinnunen; Mia Liljeström; et al. (GeroScience, 2026)
Background Currently, no single biomarker can reliably identify preclinical Alzheimer’s disease (AD), particularly at or before the mild cognitive impairment (MCI) stage. Given the heterogeneity of MCI, integrative approaches are needed to improve early risk stratification. Objectives (i) To derive robust latent cognitive components from a multicenter, clinically defined MCI cohort using principal component analysis (PCA); (ii) to investigate the associations between these components and plasma p-tau217 and p-tau181 levels. Methods Data from 742 MCI participants in the AI-Mind cohort were analyzed. Cognitive domains were derived using PCA with varimax rotation and tested for associations with plasma p-tau biomarkers using site-specific linear regressions, adjusted for age, sex, and education. Results A reproducible four-component cognitive structure emerged (memory, executive/processing speed, verbal fluency, visuospatial ability), with memory as the most p-tau-sensitive domain. The p-tau217 measure showed stronger associations with memory than p-tau181, though effects varied by site. Conclusion The findings indicate that a robust four-factor cognitive structure can be identified in clinically defined MCI cohorts without prior biological selection. The association between latent memory factors and plasma p-tau217, observed primarily in cohorts with higher biomarker burden or clearer amnestic profiles, highlights the potential for blood-based biomarkers to refine risk assessment in routine clinical practice.

Climate trade-offs: Greenhouse gas emissions from natural and constructed intertidal wetlands - M.F. Adame; J.M. Hall; N.J. Grundy; I. Sumudumali; M. Sievers; C. Herrera; T. McAlister; S. Umapathi; L. Prouse; K. Risheharan; R.M. Connolly (Journal of Environmental Management, 2026)

Water Quality Variation in Wetland Reserve Easements in the Mississippi Alluvial Valley - Avery J. Wissmueller; Beth Baker; Kara M. Hall; Sandra B. Correa; Mark Hill; Michael Eggleton; J. Brian Davis (Wetlands, 2026)

Untargeted Metabolomics Reveals Major Patterns of Metabolic Shifts in Potato Seed Tubers during Storage - Chunmei Zou; Ric C. H. de Vos; Roland Mumm; Henriëtte D. L. M. van Eekelen; Aurin M. Vos; Alejandro Thérèse Navarro; Robert D. Hall; Martin K. van Ittersum; Willemien J. M. Lommen; Paul C. Struik (Potato Research, 2026)
To obtain comprehensive insight into metabolic changes in potato seed tubers during storage and to identify patterns associated with physiological ageing, we analysed tuber metabolite composition using untargeted metabolomics based on gas and liquid chromatography-mass spectrometry (GC–MS and LC–MS). During two seasons, seed tubers of four contrasting cultivars (Agria, Festien, Innovator, and Lady Claire) were produced in a single field and after harvest, stored at different temperatures. During storage, the number of detected secondary metabolites increased progressively, particularly at higher temperatures (7–17 ˚C). Principal component analysis (PCA) revealed clear cultivar-specific metabolic profiles, with the starch cultivar Festien distinctly separated from the consumption cultivars, primarily caused by different amino acid composition. PCA further highlighted the impact of cold storage (4 ˚C) on primary metabolism, especially the accumulation of reducing sugars, as well as the combined effects of storage duration and elevated temperature on secondary metabolites, notably glycoalkaloids. Factor analysis (FA) supported these findings, with most metabolites strongly associated with the factor distinguishing cv. Festien from the other cultivars. Additionally, the leading factors captured cultivar-specific patterns and diverse trajectories reflecting the effects of storage duration and temperature. Together, these results provide a comprehensive overview of metabolic dynamics during storage and contribute to understanding the functional roles of metabolites in tuber physiological ageing.

Implementing nature-based solutions requires distinguishing place from space - Damon M. Hall; Charles B. van Rees (Ambio, 2026)
Nature-based solutions (NbS) scholarship is overshooting its most basic purpose—the implementation of NbS projects. Investment in high-level design is outpacing the practical realities of implementation. While expert-driven approaches are useful for project prioritization at landscape scales, all NbS projects are implemented in real places, inhabited by human and non-human lives. Projects span multiple properties, impact resident livelihoods, and affect and are affected by local and regional ecological dynamics. In the excitement of novel technical top-down NbS designs, equal attention is needed for ground-up social–ecological contexts of locales. Using geographers’ conceptual distinction between space and place , we outline a place-based inquiry useful for assessing site-level ecological and social feasibility to advance implementation. We identify implementation barriers, routes for top-down and bottom-up integration and call for case studies detailing implementation challenges and remedies. Integrating remote-spatial and place-based data enables contextualizing design—saving time and money and consequently increasing successful implementation.

High-resolution MRI evidence for age- and sex-related changes in hippocampal subfield volume during healthy aging - Megan C. Hall; Giorgia Picci; Maggie P. Rempe; Jason A. John; Lauren K. Webert; Kellen M. McDonald; Hannah J. Okelberry; Hallie J. Johnson; Lucy K. Horne; Madelyn P. Willett; Ryan J. Glesinger; Danielle L. Rice; et al. (GeroScience, 2026)

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Genome-wide association analysis of reproductive partitioning traits in a genetically diverse elite spring wheat panel - Aleyda Sierra-Gonzalez; Matthew P. Reynolds; Gemma Molero; Ryan Joynson; Anthony Hall; M. John Foulkes (Euphytica, 2026)

A large mortality event in New Zealand fur seals (Arctocephalus forsteri) caused by a divergent canine distemper virus - H.S. Taylor; M. Eames; M. Bestbier; S. Hunter; J.S. Weir; J. O'Connell; A.D. Wilson; A. Little; A.A. Hall; S.J. Waller; J.L. Geoghegan; J. Foxwell; et al. (Veterinary Microbiology, 2026)

Ocean acidification reduces diatom and photosynthetic gene abundance on plastic in an coastal bay mesocosm experiment - Zheng Chen; Dorsaf Kerfahi; XueQian He; Xu Zhang; Ping Zhang; Guang Gao; Kunshan Gao; Jason M. Hall-Spencer; Jonathan M. Adams; Xin Lin (Marine Environmental Research, 2026)

Forest restoration thinning and burning treatments create habitat mosaics and facilitate succession of grasshopper and cricket communities (Orthoptera) - Robert R. Parmenter; Tyler J. Obermeit; Benjamin P. Stout; Sarah M. Hall; Orrin B. Myers; David C. Lightfoot (Forest Ecology and Management, 2026)

Development of a New Aerosol Delivery System for Administering Aerosol Surfactant Therapy to Preterm Infants Through a Laryngeal Mask Airway - Sarah C. Strickler; Caleb J. Dalton; Felicia G. Hall; Dale R. Farkas; Mohammad A. M. Momin; Robert M. DiBlasi; Michael Hindle; P. Worth Longest (AAPS PharmSciTech, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Metformin reverses oxandrolone-induced anxiety-like behavior and amygdalar neurochemical dysregulation in male rats - Alaa M. Hammad; Sawsan I. Khdair; Ahmad A. Deeb; Yasmeen A. Ibrahim; Taleb M. Hammad; F. Scott Hall (Psychopharmacology, 2026)

Population genetic insights into biogeography and clonality of the perennial Ambrosia psilostachya DC. (Asteraceae) in the United States of America - Gerhard Karrer; Rea M. Hall; Valerie Le Corre; Matthias Kropf (Flora, 2026)

Multichemical Exposure Assessment Using Silicone Wristbands in Central American Adolescents - Yirong Yuan; Samantha M. Hall; Juan José Amador Velázquez; Damaris López Pilarte; Selene Vences Brown; Magaly Amador Sánchez; Juan Amador Sánchez; Birgit Claus Henn; Madeleine K. Scammell; David J. Friedman; Daniel R. Brooks; Jessica H. Leibler (Exposure and Health, 2026)
Chemical exposures are poorly characterized in Central America, where chronic kidney disease of uncertain etiology (CKDu) is a leading cause of death. Most research evaluates occupational exposures in adults, yet early-life exposures remain understudied. We used silicone wristband passive samplers to characterize exposure to over 1,500 chemicals among Nicaraguan adolescents ( n = 80) residing in CKD high-risk communities but not engaged in agricultural work. We identified exposure profiles using k-means clustering and used LASSO logistic regression to identify predictors of low estimated glomerular filtration rate (eGFR). SHAP (SHapley Additive Explanations) values quantified individual chemical contributions to eGFR in a machine learning model. Of 130 detected chemicals, 21 (16.2%) were pesticides. Pyrethroids were detected on 93.8% of wristbands, most frequently cypermethrin-2 (88.8%) and ethofenprox (60.0%). Phthalates and musks, including bis(2-ethylhexyl) phthalate (DEHP, 98.8%), di-n-butyl phthalate (DnBP, 97.5%), and galaxolide (100%), were near ubiquitous. Esters included benzyl salicylate (97.5%) and ethylene brassylate (93.8%). Organophosphate triphenyl phosphate (TPP, 97.5%) and polyaromatic hydrocarbons (PAHs) pyrene (92.5%) and 2-methylphenanthrene (63.8%) reflected mixed consumer and environmental sources. K-means clustering identified four exposure profiles: two larger clusters reflecting background agrochemical exposures and a low-exposure group, and two smaller clusters dominated by household and personal care products. No individual chemicals were significantly associated with eGFR. SHAP analysis identified phthalates, esters, organophosphates, and phenols as the most influential predictors of kidney function. Adolescents in this CKDu-endemic region experience heterogeneous chemical exposures. Frequently detected compounds with nephrotoxic potential, including pyrethroids, PAHs, phenols, and phthalates, warrant targeted investigation.

Assessment of brick kiln’s air pollutants impact on human health in industrial areas of Kathmandu Valley, Nepal - Bhupendra Das; Hishila Sujakhu; Suvekshya Sitaula; K.C. Sheela; Meera Prajapati; James Hall; James Robert Hodgson; Bijaya Maharjan; Rejina M. Byanju (Atmospheric Pollution Research, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Relationships Between Soil and Vegetation Properties and Soil Carbon Stocks Differ Between Grasslands with Different Water Table Management - Emma M. N. Polman; Kenneth F. Rijsdijk; Perry Cornelissen; Rutger L. van Hall; Franciska T. de Vries (Ecosystems, 2026)
Water table management such as temporal flooding is an important strategy for influencing vegetation development and creating suitable habitat for wildlife in managed wetland systems. Water table fluctuations can also affect soil carbon and nutrient cycling through changes in abiotic soil properties, plant traits and soil microbial communities, but research on the effect of temporal flooding on these relations is limited. Here we tested the hypothesis that winter inundation leads to a plant community with more fast-growth-related plant traits, a bacterial-dominated soil microbial community, and lower soil organic carbon stocks compared to a year-round dry grassland. We compared soil and vegetation of winter-inundated and non-inundated grassland in a Dutch-managed wetland area. In contrast to our hypothesis, we found that winter inundation results in plant communities with more slow-growth-related traits and microbial communities more dominated by fungi, compared to non-inundated grassland. We found no difference between shallow soil organic carbon stocks, carbon-to-nitrogen ratios or nitrogen-to-phosphorous ratios. Winter inundation did, however, change the relationship between soil and vegetation properties and soil carbon stocks, as well as soil nutrient ratios. While soil carbon stocks in non-inundated grassland were explained by abiotic soil and vegetation properties, soil carbon stocks were only explained by microbial properties in winter-inundated grasslands. These findings show that winter inundation can be used for vegetation and wildlife management with limited effects on soil carbon stocks.

Genetic Diversity and Population Structure in Cities Is Not Consistent Among Cosmopolitan Plant Species - Ava M. Hoffman; Jennifer M. Cocciardi; Prothama Manna; Diego F. Alvarado‐Serrano; Jeannine Cavender‐Bares; Peter M. Groffman; Sharon J. Hall; Sarah E. Hobbie; Susannah B. Lerman; Josep Padullés Cubino; Diane E. Pataki; Tara L. E. Trammell; et al. (Molecular Ecology, 2026)
Urbanisation has led to increasing homogenization of plant communities across cities. However, it is unclear whether these patterns extend to cosmopolitan plant species at the genetic level. We examined genome‐wide genetic patterns in six widespread plant species (three Poaceae and three Asteraceae) across five cities in the USA (Boston, Baltimore, Minneapolis‐St. Paul, Phoenix, and Los Angeles) using reduced‐representation sequencing. We assessed genetic structure, differentiation, and patterns of isolation by distance (IBD) and environment (IBE) to determine if species were genetically homogeneous or differentiated by city, percentage of impervious surface, or both. Most species exhibited limited population structure overall, with Poa annua (annual bluegrass), Taraxacum officinale (dandelion), and Cynodon dactylon (Bermuda grass) showing no significant genetic differentiation among cities, a pattern consistent with high gene flow mediated by human activity. Notable exceptions included city‐level differences in Erigeron canadensis (horseweed) and Lactuca serriola (prickly lettuce), especially in Phoenix. We also observed low genetic diversity in Digitaria sanguinalis (crabgrass) from Phoenix, suggesting recent founder effects or selection via environmental filtering. Erigeron canadensis , the only native species studied, displayed stronger differentiation by city, along with significant isolation by temperature and distance. Among all species, we found no evidence for population structure by impervious surface. Our findings indicate that widespread population genetic structure patterns of cosmopolitan plants are likely to depend more on species attributes (e.g., self‐compatibility) and human‐mediated dispersal than on urbanisation per se.

A history of the collaborative group of the Americas on inherited gastrointestinal cancer (CGA-IGC): 1995–2025 - Beth Dudley; Bruce M. Boman; Marc S. Greenblatt; Steven H. Erdman; Paul E. Wise; Randall E. Brand; Carol A. Burke; Jose G. Guillem; Michael J. Hall; Heather Hampel; Brandie Heald; Matthew F. Kalady; et al. (Familial Cancer, 2026)

Evolution of Paleogene to Early Miocene deep-water provenance sources in Sabah, northern Borneo reveals changing Proto-South China Sea paleogeography - H. Tim Breitfeld; Marco W.A. van Hattum; Robert Hall; Stuart Burley; Juliane Hennig-Breitfeld; Max Franzel; Simon M. Suggate; Pieter Vermeesch; Max Webb (Tectonophysics, 2026)

Biosecurity for all: Creating biosecurity plans for swine exhibitors based on secure pork supply templates - Marissa Hall; Andreia G. Arruda; Magnus R. Campler; Jacqueline M. Nolting (Preventive Veterinary Medicine, 2026)

96-h methamphetamine self-administration elicits striatal dopamine depletion in male and female rats: a model of binge-like use - Bo Jarrett Wood; Ethan D. Brackett; Nicole M. Hall; Christopher E. Cannon; Robert D. Dayton; Courtney M. Keller; Nicholas E. Goeders; Kevin S. Murnane (Psychopharmacology, 2026)
Background Methamphetamine is a psychostimulant with significant public health implications. Chronic methamphetamine use is linked to profound dysregulation of the dopaminergic system, cognitive deficits, and psychiatric symptoms. While traditional experimenter administered “binge” dosing models reliably produce dopaminergic neurotoxicity, they fail to capture the volitional, drug intake characteristic of human methamphetamine use. Although self-administration paradigms better reflect human drug-taking behavior, they have yet to consistently reproduce the neurochemical deficits seen in the non-contingent models. Methods In this study, we employed a very long-access (96-h) methamphetamine self-administration model over eight weeks to evaluate whether contingent, volitional drug intake produces dopaminergic neurotoxicity. Male and female rats were given extended access to methamphetamine (0.06 mg/kg/infusion) for 96-h sessions weekly, with saline-yoked controls. Neurochemical analysis focused on striatal dopamine and metabolites to assess drug-induced alterations. Results Rats exhibited significant escalation in methamphetamine intake over eight weeks, with no sex differences in total intake. Importantly, striatal dopamine levels were significantly reduced in both male and female methamphetamine self-administering rats compared to saline-yoked controls, representing the first demonstration of dopamine depletion following voluntary administration methamphetamine self-administration. Dopamine depletion was significantly correlated with total methamphetamine intake. Interestingly, no significant changes were observed in dopamine metabolites (DOPAC, HVA). Conclusions These findings demonstrate that volitional methamphetamine intake under a 96-h access model induces robust dopaminergic deficits, paralleling those seen in non-contingent binge dosing. This model provides a translationally relevant paradigm, capturing both the behavioral and neurobiological aspects of human methamphetamine use, supporting its utility for investigating neurotoxicity and potential treatments.

Accelerated carbon cycling after 50 years of warming and increasing hydrologic variability in a temperate stream - Alice M. Carter; Michael J. Vlah; Robert O. Hall; Emily S. Bernhardt (Limnology and Oceanography, 2026)
Rivers transform and transport much of the organic input they receive from terrestrial ecosystems. This carbon sustains stream food webs and fuels the production and release of carbon dioxide and methane to the atmosphere. Warming water temperatures and intensification of the hydrologic cycle due to climate change are likely to affect these carbon transformations and downstream transport in streams. Here, we examine the natural variability and long‐term shifts in the metabolism of New Hope Creek, North Carolina, USA, site of the earliest published estimates of a stream's annual metabolic regime in 1969. We estimated annual ecosystem metabolism over 3 yr (2017–2020) and used the variability observed in the modern dataset to provide context for interpreting long‐term change in response to climate drivers. We found that New Hope Creek was heterotrophic in all years, with highly seasonal carbon cycling. Much of the modern variability can be explained by water temperature and flow conditions. Warmer temperatures and longer periods of low flow conditions led to faster carbon cycling and increased heterotrophy, while autumn floods suppressed annual ecosystem respiration by reducing river carbon stocks. Comparing modern estimates to those from 50 yr ago, we find that New Hope Creek is now substantially warmer and has higher metabolic fluxes. Despite the limitations of inferring trends between two distant time points, we use modern data to hindcast metabolism and show how climate change has likely accelerated carbon cycling and shortened carbon residence time in New Hope Creek.

Local Adaptation in Climate Tolerance at a Small Geographic Scale Contrasts With Broad Latitudinal Patterns - Greg M. Walter; Avishikta Chakraborty; Fiona E. Cockerell; Vanessa Kellermann; Lesley A. Alton; Craig R. White; Matthew D. Hall; Carla M. Sgrò (Ecology Letters, 2026)
While climate adaptation is typically quantified across broad gradients, the potential for adaptation to the same environmental variables at small scales is rarely tested. If local‐scale environmental heterogeneity can generate patterns of adaptation similar to broad gradients, then we currently underestimate adaptive capacity to global change. We quantified population variation in climate tolerance traits and their plasticity for five populations of Drosophila melanogaster from a 3000‐km latitudinal gradient, which we contrasted with eight local populations from an environmentally heterogeneous 600 × 300 km area. Population variation in stress tolerance at the local scale was comparable to that across latitude. Consistent with local adaptation, populations from warmer and drier environments showed greater heat and desiccation tolerance and populations from more predictable environments showed greater plasticity. Climate adaptation at smaller geographic scales can therefore be comparable to adaptation across broad geographic scales. However, patterns of adaptation often changed across geography, which makes predicting responses to global change challenging.

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

Systematic evaluation of Tox21 compounds that target β-adrenergic receptors and their role in cardiotoxicity - Xi Luo; Li Zhang; Srilatha Sakamuru; Precious A. Adesina; Jinghua Zhao; Menghang Xia; Tuan Xu; Deborah K. Ngan; Jameson Travers; Savannah Wood; Ray Sukhawanit; Anthony Garrison; et al. (Toxicology and Applied Pharmacology, 2025)

Scene Analysis for Gas Estimation (SAGE): A tool for quantification of diffuse and point-source atmospheric trace gas abundance - Jeffrey L. Hall; Clement S. Chang; Karl Westberg; David M. Tratt (Remote Sensing of Environment, 2025)

Algal assemblage drives patterns in ecosystem structure but not metabolism in a productive river - Alice M. Carter; Robert O. Hall; Rafael Feijó‐Lima; Michael DeGrandpre; Qipei Shangguan; H. Maurice Valett (Ecology, 2025)
Algal dynamics are fundamental drivers of lotic ecosystem processes. Although rivers tend to be heterotrophic and have low standing stocks of autotrophic biomass, filamentous algae can cause nuisance algal blooms that alter the structure of the autotrophic assemblage. Still, the influence of these blooms on ecosystem processes can be variable. Here, we examined the structural and functional contribution of filamentous and epilithic algae by linking algal biomass measurements to daily primary production fluxes throughout two growing seasons in six sites along the Upper Clark Fork River, an open canopy, snow melt river in western Montana, USA. We partitioned daily productivity estimates across different algal groups using the spatial and temporal variability in algal assemblages across our six sites. By using reach‐scale metabolism estimates, we assessed the in situ functional rates of individual algal groups. Throughout two growing seasons, we measured high fluxes of ecosystem productivity and spatially variable filamentous algal blooms. We found that the filamentous algal blooms determined the ecosystem structure in terms of total biomass and algal turnover times, but not the ecosystem functions of gross primary productivity, ecosystem respiration, or net production. Whole‐reach estimates of epilithic and filamentous algae growth rates were 0.30 and 0.026 day respectively, which are similar to rates measured in mesocosms. The epilithic algae grew and turned over rapidly, dominating total biomass production and driving ecosystem function while filamentous algae grew slowly and built up large amounts of biomass during a growing season, shaping the structure, but not function, of the ecosystem.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Broad‐scale climate patterns combined with local flow and turbidity disturbances structure the seasonality of gross primary production in an aridland river - Betsy M. Summers; Robert O. Hall; Justin K. Reale; Eric Joseph; Mark C. Stone; David J. Van Horn (Limnology and Oceanography, 2025)
Both local and global climate phenomena shape the hydrologic regimes of watersheds. For aridland rivers in the southwestern United States, peak flows occur during two distinct periods: spring snowmelt and summer monsoons. Although discharge ( Q ) is a primary driver of variation in the production and consumption of instream organic matter, or stream metabolism, few connection have been made regarding how climate impacts ecosystem processes through changes in flow and related disturbances. We considered how variation in disturbance variables, specifically Q and associated changes in turbidity, affected gross primary production during spring snowmelt and summer monsoons in the Rio Grande. Nine years of continuous environmental data ( Q , turbidity, light) and climate indices (i.e., El Niño‐Southern Oscillation and Monsoon Index) were used to explain the variation in gross primary production estimates. We found that relationships were sensitive to the timescale of disturbance: at the seasonal scale, high snowmelt Q decreased spring mean gross primary production, while at the daily scale, high turbidity, and to a lesser extent Q , reduced gross primary production during summer. Also, mean Q and turbidity disturbances were uncoupled in spring and inversely related in summer. We conclude that long‐term datasets are essential to uncover emergent relationships between broad‐scale climate patterns and ecosystem processes and are necessary to better understand how hydroclimatic variability drives ecosystem processes at varying time scales in rivers across Earth.

Establishing scientific confidence in a two-chamber co-culture system to evaluate androgenic response in the presence of hepatic metabolism - Tessa C.A. van Tongeren; Susan J. Hall; Samantha J. Madnick; Blanche C. Ip; Paul L. Carmichael; Hequn Li; Wei Chen; Lori A. Breitweiser; Heather E. Pence; David M. Ames; Andrew J. Bowling; Kamin J. Johnson; et al. (Toxicology Letters, 2025)

A review of circular industrialised construction for sustainable and affordable housing: Towards a process-driven framework - Annette Davis; Núria Martí Audí; Daniel M. Hall (Sustainable Cities and Society, 2025)

How robust are signals of local adaptation? Exposure to a common fungal pathogen does not disrupt clinal trends in host thermal tolerance - Jared Lush; Connor Bevan; Carla M. Sgrò; Matthew D. Hall (Journal of Thermal Biology, 2025)

What’s going on in the livers in my study? Test-item related toxicity or spontaneous finding? - M. Rezaee; P. Hall; S. Rombouts; F. Poosti; L. Ratsamy; J. Ling; R. Fleurance (Journal of Comparative Pathology, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Unraveling microclimate effects on pollinator foraging and crop yield in lowbush blueberry - Garrett Sisk; Anaís Ostroski; Travis Dillard; Bruce Hall; Sarah C. Goslee; Christina M. Grozinger; Vikas Khanna; Heather Grab (Agriculture, Ecosystems & Environment, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

P32-08 Advancing Skin Toxicity Predictions for Cancer Therapies: In vitro to Clinical Extrapolation - J. Komen; V. Fogal; J. Biasetti; S. Bates; A. Hall; A. Bianco; M. Coen (Toxicology Letters, 2025)

Paralytic shellfish toxins and seabirds: evaluating sublethal effects, behavioral responses, and ecological implications of saxitoxin ingestion by common murres (Uria aalge) - Matthew M. Smith; Robert J. Dusek; Tuula Hollmen; Sarah K. Schoen; Caroline Van Hemert; Kristen Steinmetzer; Aidan Lee; Jenna Schlener; Vijay Patil; D. Ransom Hardison; David Kulis; Donald M. Anderson; et al. (Harmful Algae, 2025)

Mollusc epifaunal assemblages are simplified due to habitat shifts under ocean acidification - Gustavo M. Martins; Javier Herrero; Cristina Canella; Sérgio P. Ávila; Afonso Prestes; Joana Barcelos e Ramos; Jason M. Hall-Spencer; João Faria (Estuarine, Coastal and Shelf Science, 2025)

Biodiversity impacts of native versus non-native oaks - Markus Franzén; Marcus Hall; Romana Salis; Johanna Sunde; Laura J. A. van Dijk; Ayco J. M. Tack; Anders Forsman (Biological Invasions, 2025)
Introducing non-native tree species into forest ecosystems is a growing trend, in part as climate change may cause a decline of native species and shifts in species distributions. In European forestry, Quercus rubra (northern red oak) has increasingly been considered a candidate substitute species for native oaks. However, it remains largely unknown how this substitution affects associated biodiversity. This study compares the biodiversity supported by the native oak species Q. petraea (sessile oak) and Q. robur (pedunculate oak) and the invasive Q. rubra in southern Sweden, focusing on both oak-associated organisms and general forest biodiversity. Arthropods were sampled using Malaise traps at the site level. At the same time, vascular plants, leaf herbivory and endophytic insects (leaf miners and gallers) were recorded at the tree level in three sites per oak species. Our results reveal guild-specific effects of oak species on biodiversity. The introduced Q. rubra supported significantly fewer endophytic insects than native oak species. Vascular plant species richness was marginally lower in Q. petraea and Q. rubra sites compared to Q. robur . In contrast, the species richness, abundance, biomass and community composition of arthropods and leaf herbivory did not differ significantly between the three oak species. These findings indicate that the ecological consequences for biodiversity of introduced tree species, such as Q. rubra , are most pronounced for specialised herbivores, including leaf miners and gallers, and suggest that broader forest biodiversity measures may be less responsive to changes in tree species than to local environmental conditions.

The effects of water motion on fragmentation of Asparagopsis armata - Ailise M. Hall; Paul M. South; Jordan E. Elvy; Andrew G. Jeffs (New Zealand Journal of Marine and Freshwater Research, 2025)
The red seaweed Asparagopsis armata presents a promising solution to reducing methane production in ruminant livestock when included in their daily diet. To effectively address these emissions from ruminants in an effort to meet crucial climate targets, the development of efficient cultivation methods for the large‐scale aquaculture of this species is imperative. This study examined the effects of water motion, specifically the effect of water turbulence and laminar velocity on fragmentation of two key life stages of A . armata to understand the potential for fragmentation to contribute to vegetative propagation for commercial cultivation and to assess the potential for losses from marine farms. Increased water motion generally resulted in greater fragmentation in the tetrasporophyte and gametophyte life stages of A. armata . Greater seawater turbulence and velocities led to a greater number, biomass and size of fragments from tetrasporophytes, resulting in an increased number of potentially viable vegetative propagules. The findings of this research contribute to the understanding of fragmentation of A. armata to inform the development of efficient and sustainable aquaculture, contributing to the goal of reducing agricultural methane emissions.

Multi-centre normative brain mapping of intracranial EEG lifespan patterns in the human brain - Heather Woodhouse; Gerard Hall; Callum Simpson; Csaba Kozma; Frances Turner; Gabrielle M. Schroeder; Beate Diehl; John S. Duncan; Jiajie Mo; Kai Zhang; Aswin Chari; Martin Tisdall; et al. (Brain Structure and Function, 2025)
Understanding healthy human brain function is crucial to identify and map pathological tissue within it. Whilst previous studies have mapped intracranial EEG (icEEG) from non-epileptogenic brain regions, they often neglect age and sex effects. Further, they are limited by small sample sizes due to the modality’s invasive nature. This study substantially expands the subject pool compared to existing literature, to create a multi-centre, normative map of brain activity which considers the effects of age, sex and recording hospital. Using interictal icEEG recordings from $$n = 502$$ subjects across 15 centres, we constructed a normative map of non-pathological brain activity by regressing age and sex on relative band power in five frequency bands. A linear mixed model was implemented to account for the hospital effect. Variable importance was assessed using standard statistical measures, and regression coefficients (and their standard errors) were analysed at both whole-brain and regional scales. Recording hospital significantly impacted normative icEEG maps in all frequency bands, and age was a more influential predictor of band power than sex. The age effect varied by frequency band, but no spatial patterns were observed at the region-specific level. Certainty about regression coefficients was also frequency band specific and moderately impacted by sample size. The concept of a normative map is well-established in neuroscience research and particularly relevant to the icEEG modality, which does not allow healthy control baselines. Our key results regarding the hospital site and age effect guide future work utilising normative maps in icEEG.

Latent Growth Models of Longitudinal Changes in Functional Connectivity during Early Stage Psychosis - Kristina M. Holton; Shi Yu Chan; Austin J. Brockmeier; Mei-Hua Hall (Neuroinformatics, 2025)

Lithium toxicity to marine organisms: Establishing water quality guideline values to protect temperate and tropical marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Chemosphere, 2025)

Embryonic temperature shapes morphology, physiology, and survival across life stages for an ectotherm threatened by global change - Julia M. Thulander; Joshua M. Hall (Journal of Thermal Biology, 2025)

Blue carbon as a nature-based climate mitigation strategy for mangrove conservation in Bangladesh - Nathalie Hilmi; Gisele Arruda; David Broussard; Belen Maria Benitez; Laurène Sauron; Tali Lamaud; Nipa Jahan; Jason M. Hall Spencer (Journal for Nature Conservation, 2025)

Summer circulation and water masses transport in Bransfield Strait, Antarctica: An evaluation of their response to combined effects of Southern Annular Mode and El Niño–Southern Oscillation - Brendon Yuri Damini; André L. Brum; Rob A. Hall; Tiago S. Dotto; José Luiz L. Azevedo; Karen J. Heywood; Mauricio M. Mata; Carlos A.E. Garcia; Rodrigo Kerr (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

The effect of clay type on the toxicity of carbendazim and imidacloprid to the earthworm Eisenia andrei in artificial soils - Bart G. van Hall; Shuan Meijer; Anna C. Pelser; Cornelis A. M. van Gestel (Ecotoxicology, 2025)
In Europe, the risk assessment of pesticides to soils organisms is based on standardized laboratory toxicity tests using artificial soil containing kaolin clay. However, kaolin is not the most representative clay type for European agricultural soils, and its use may affect the bioavailability and toxicity of pesticides, potentially leading to an underestimation of the actual risk to soil organisms. In this study, reproduction toxicity tests with the earthworm Eisenia andrei following OECD guideline 222 were performed in artificial soils prepared with kaolin or bentonite clay, using the pesticides carbendazim and imidacloprid. The results showed that the OECD guideline 222 quality criteria could be met in soils prepared with bentonite clay. EC 50 reproduction values (and 95% CIs) in soils prepared with kaolin and bentonite clay were 1.80 (1.02–2.57) and 4.19 (−10.4–18.8) mg kg −1 for carbendazim, and 0.71 (0.06–1.36) and 2.27 (−0.26–4.80) mg kg −1 for imidacloprid. For both pesticides, toxicity (LCx, ECx biomass, ECx reproduction) was higher in soils prepared with kaolin clay, although the differences were not always statistically significant. Differences in toxicity between the soils were likely due to a combination of the bentonite’s larger interlayer distance, providing space for the pesticides to enter in between the clay sheets, and the higher cation exchange capacity (7.30 and 22.8 cmol c kg −1 for kaolin and bentonite soil, respectively) leading to increased pesticide sorption. Overall, these findings suggest that kaolin is a suitable clay type for standardized artificial soil, as it exhibited the highest toxicity, and thus provided a “worst-case” scenario.

Discovering a predictive metabolic signature of drug-induced structural cardiotoxicity in cardiac microtissues - Tara J. Bowen; Andrew R. Hall; Gavin R. Lloyd; Matthew J. Smith; Ralf J. M. Weber; Amanda Wilson; Amy Pointon; Mark R. Viant (Archives of Toxicology, 2025)
Improved prediction of drug-induced structural cardiotoxicity is required to reduce attrition driven by cardiac safety concerns in drug discovery. Omics measurements are well suited to this need, offering the potential to discover molecular signatures associated with toxicological endpoints. In addition, untargeted metabolomics can simultaneously measure xenobiotic fate within the test system. We present an extensive metabolomics study to discover a predictive metabolic signature of drug-induced structural cardiotoxicity. A human-relevant in vitro cardiac model, cardiac microtissues, were exposed to twelve xenobiotics (eight clinically labelled structural cardiotoxins and four non-cardiotoxic pharmaceuticals), each at two concentrations, for 6, 24, and 48 h. The measurements were made by direct-infusion and liquid-chromatography mass spectrometry from intracellular polar and lipid extracts, and spent culture medium, respectively. Data were used to quantify levels, and reveal the metabolic fate of the xenobiotics, and to simultaneously explore their effects on the cardiac microtissues. Xenobiotic quantification revealed free concentrations to be typically lower than nominal values, whilst discovery of xenobiotic-related features evidenced the biotransformation capacity of the microtissues. Both common and condition-specific effects of the xenobiotics on the intracellular metabolome, lipidome, and metabolic footprint were discovered. Moreover, metabolic signatures with capacity to predict structural cardiotoxicity were revealed. These included features representing several ceramides, energy metabolism intermediates, e.g. creatine, purine-related metabolites, and markers of oxidative stress, e.g. glutathione.

Swine production intensity and swine-specific fecal contamination of household surfaces at residences of industrial livestock operation workers and community residents, North Carolina, USA - Kathleen M. Kurowski; Nora Pisanic; Kristoffer Spicer; Kate Kruczynski; Carolyn Gigot; Devon J. Hall; Devon J. Hall; Kyle T. Aune; Bonita Salmerón; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2025)

Probability of extinction and peak time for multi-type epidemics with application to COVID-19 variants of concern - Jacob Curran-Sebastian; Louise Dyson; Edward M. Hill; Ian Hall; Lorenzo Pellis; Thomas House (Journal of Theoretical Biology, 2025)

Tropicalization Interacts with Other Human Stressors to Mediate the Diets of Expanding and Resident Herbivores - Adam R. Searles; Douglas H. Adams; Lauren M. Hall; Lori J. Morris; Charles W. Martin; Laura K. Reynolds (Estuaries and Coasts, 2025)

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Warmer Is Deadlier: A Meta‐Analysis Reveals Increasing Temperatures Accentuate Disease Effects on Fisheries Hosts - Megan M. Tomamichel; Kaitlyn I. Lowe; Kaylee M. H. Arnold; Marc. E. Frischer; Brian J. Irwin; Craig W. Osenberg; Richard J. Hall; James E. Byers (Ecology Letters, 2025)
Rapid warming could drastically alter host–parasite relationships, which is especially important for fisheries crucial to human nutrition and economic livelihoods, yet we lack a synthetic understanding of how warming influences parasite‐induced mortality in these systems. We conducted a meta‐analysis using 266 effect sizes from 52 empirical papers on harvested aquatic species and determined the relationship between parasite‐induced host mortality and temperature and how this relationship was altered by host, parasite, and study design traits. Overall, higher temperatures increased parasite‐induced host mortality; however, the magnitude of this relationship varied. Hosts from the order Salmoniformes experienced a greater increase in parasite‐induced mortality with temperature than the average response to temperature across fish orders. Opportunistic parasites were associated with a greater increase in infected host mortality with temperature than the average across parasite strategies, while bacterial parasites were associated with lower infected host mortality as temperature increased than the average across parasite types. Thus, parasites will generally increase host mortality as the environment warms; however, this effect will vary among systems.

Assessing the cumulative effects of nearshore habitat restoration actions for multiple populations of juvenile salmon in Whidbey Basin, Washington: foundation and approach for synthesis and evaluation - Kathryn L. Sobocinski; Michael LeMoine; Joshua W. Chamberlin; Letitia Conway-Cranos; Annelise Del Rio; Heida L. Diefenderfer; Correigh M. Greene; Jason Hall; Gary E. Johnson; Ronald M. Thom; Elene Trujillo; Todd Zackey (Frontiers in Marine Science, 2025)
Ecosystem restoration is a common tool for re-establishing ecosystem processes, structures, and functions to improve biodiversity and services in coastal and estuarine ecosystems. In the Salish Sea, salmon habitats have been fragmented, reduced in size, and diminished in quality, and the ecosystem processes that form and sustain these habitats have been degraded and disrupted as well. This loss is especially prevalent in estuaries, where up to 90% of former salmon habitat has been lost or compromised. Salmon species are integral to the identities and cultures of people in the Pacific Northwest, yet salmon abundances remain at historic lows, especially in urbanized areas. Recent investments in restoration are creating rearing habitat and repairing lost ecosystem function. However, restoration efforts in this region have largely proceeded at the site scale, with less attention to big-picture thinking regarding how restoration will effectively recover degraded or lost habitats for target species. As a result, no landscape-scale evaluation program exists, and the cumulative benefits of multiple interventions are unknown. We describe innovative methods for science synthesis related to the evaluation of cumulative effects of ecosystem restoration for Pacific salmon, using years of existing, but disparate data. Building from previous work on cumulative effects evaluation and incorporating a hierarchy of hypotheses approach, we propose using causal inference across numerous hypotheses in a framework to assess the cumulative benefits to Pacific salmon from multiple estuarine restoration projects. We present the framework as a method that can be used to address many complex questions and provide examples from the Salish Sea where the approach is being implemented. The framework draws on science synthesis from numerous fields and uses a hierarchy of hypotheses, causal analysis at multiple scales, and a new hierarchy of synthesis for assessing multiple lines of evidence documenting restoration effects on Pacific salmon. We propose causal inference to synthesize dissimilar data streams, in our case, to identify various manifestations of cumulative effects of restoration and benefits to salmon, and to further inform restoration and recovery planning. A unifying framework would allow for the detection of thresholds at which restoration provides measurable improvement and would greatly advance understanding of the effects of restoration on ecosystems.

Phosphine as a possible alternative to methyl bromide for the phytosanitary treatment of wood products - Matthew K.D. Hall; Laura M. Machuca-Mesa; Adnan Uzunovic; Sunil K. Yadav; Dongwoon Lee; Manoj K. Nayak (Journal of Stored Products Research, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Imaging of Intracranial Aneurysms: A Review of Standard and Advanced Imaging Techniques - Sricharan S. Veeturi; Samuel Hall; Soichiro Fujimura; Mahmud Mossa-Basha; Elena Sagues; Edgar A. Samaniego; Vincent M. Tutino (Translational Stroke Research, 2025)

A novel physiologically-based pharmacokinetic model to estimate reduced CYP3A4 activity in cancer patients utilizing the neutrophil-to-lymphocyte ratio as an inflammatory marker - David E. Coutant; Jessica Rehmel; Donna M. Edwards; Stephen D. Hall (European Journal of Clinical Pharmacology, 2025)

Rhoifolin as a potential anxiolytic drug for the effects of nicotine withdrawal: beneficial effects on behavior, neuroinflammation, and oxidative stress - Alaa M. Hammad; Suhair Sunoqrot; Thanaa Al-zuhd; Mohammed Waleed; Ali I. M. Ibrahim; F. Scott Hall; Alaa R. Al-Tamimi; Eveen Al-Shalabi (Metabolic Brain Disease, 2025)

Evaluation of BRCA1/2 testing rates in epithelial ovarian cancer patients: lessons learned from real-world clinical data - Lieke Lanjouw; Claire J. H. Kramer; Arja ter Elst; Geertruida H. de Bock; Katja N. Gaarenstroom; Refika Yigit; Lieke P. V. Berger; Christi J. van Asperen; Sabrina Z. Commandeur-Jan; Dimas M. X. van der Hall; Mathilde Jalving; Marjolein J. Kagie; et al. (Familial Cancer, 2025)
Identification of somatic and germline BRCA1/2 pathogenic variants in epithelial ovarian cancer (EOC) patients is essential for determining poly-(ADP-ribose)-polymerase (PARP) inhibitor sensitivity and genetic predisposition. In the Netherlands, BRCA1/2 testing changed to a tumor-first approach to efficiently identify both somatic and germline pathogenic variants in all patients. Here, we performed an in-depth evaluation of the first four years of the tumor-first test-pathway. Data of consecutive series of patients diagnosed with EOC in two regions were obtained from the Netherlands Cancer Registry. Tumor and/or germline test data were retrieved from hospital databases. The primary outcome was the percentage of patients completing the BRCA1/2 test-pathway, defined as having a negative tumor test or a referral for a germline test in case of a positive tumor test or no tumor test. Factors associated with test-pathway completion were identified through multivariable logistic regression analysis. In total, 69.8% (757/1085) completed the test-pathway. This was 74.4% in the most recent year. Younger patients, patients diagnosed in year three or four, patients with high-grade serous/high-grade endometrioid carcinoma, advanced stage disease, middle or high socioeconomic status, and patients who underwent surgery or chemotherapy, were more likely to complete the test-pathway. We report inequalities in genetic testing access in EOC patients, which highlight the need for better guideline adherence, particularly in older patients, those with low socioeconomic status, low-grade histotypes, early-stage disease and those without surgery or chemotherapy. Additionally, timely testing of patients, and testing relatives if patients cannot be tested, are crucial to increase test uptake.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dolphins share Toxoplasma gondii Type II genotypes with terrestrial animals: Evidence of terrestrial T. gondii contamination in marine environments - Yi-Jou Chen; Heather Fenton; Jane Hall; Karrie Rose; Victor M. Peddemors; Jan Šlapeta (Veterinary Parasitology, 2025)

Technology adoption in the Canadian mining sector: A systematic scoping review - Mackenzie Crabbe; Joelena Leader; Heather M. Hall; Matthew Burdett (Resources Policy, 2025)

Environmental interpretation and environmentally responsible behavior of tourists in heritage villages - Z.-A. Torabi; C. M. Hall; M. Tavakoli; Z. Vahed (International Journal of Environmental Science and Technology, 2025)

Examining Truth Regimes Reveals How Local Communities View Flooding and River Management in the Lower Missouri River Basin, USA - Angela J. Catalano; Damon M. Hall; Gerardo M. Gentil (Environmental Management, 2025)
Riverine flooding is increasing in frequency and intensity, requiring river management agencies to consider new approaches to working with communities on flood mitigation planning. Communication and information sharing between agencies and communities is complex, and mistrust and misinformation arise quickly when communities perceive that they are excluded from planning. Subsequently, riverfront community members create narratives that can be examined as truth regimes—truths created and repeated that indicate how flooding and its causes are understood, represented, and discussed within their communities—to explain why flooding occurs in their area. To better understand community perceptions of river management related to repeated flooding, we employed a qualitative methodology of semi-structured interviews with 112 community members in 3 communities on the Missouri River, USA. Discourse analysis of the interviews revealed three dominant truth regimes that shape perceptions of river management in these communities: (1) upstream reservoir releases are driven by recreational aims, such as fishing and boating within reservoirs, instead of downstream flood control; (2) endangered species protection surpasses other river values and flood management; and (3) river navigation for commerce is no longer prioritized. For environmental managers, understanding the truth regimes circulating within local affected communities can help moderate mistrust of and frustration with governing bodies, guide project messaging to disarm false truth regimes, and improve the communication of river science, management options and policy implementation.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Simple GCM Simulations of Rainfall Over Northeast Brazil, Part 1: Systematic Effect of Canonical Sea Surface Temperature Patterns - Aubains Hounsou‐Gbo; Nicholas M. J. Hall; Leticia Cardoso; Francisco das Chagas Vasconcelos Junior; Eduardo Martins (International Journal of Climatology, 2025)
The response of February to April (FMA) Northeast Brazil precipitation to tropical sea surface temperature anomaly (SSTA) patterns is analysed by making ensemble seasonal forecasts with a simple GCM. The physical and dynamical link between the SSTAs and regional precipitation is examined for a set of tropical Pacific and Atlantic SSTAs, both separately and in combination. Five canonical SSTA patterns are considered: El Niño (strong eastern Pacific and moderate central Pacific); La Niña and the tropical North and South Atlantic. The model's anomaly responses to persisted SSTAs correspond quite well to observed precipitation regressions against SSTA timeseries: dry for El Niño and warm North Atlantic, wet for La Niña and warm South Atlantic. Experiments with reversed SSTAs show that model nonlinearity has a drying effect over northeastern South America. Combined tropical Atlantic SSTA patterns result in wet conditions over northern Northeast Brazil for a warm Atlantic or a negative dipole, and dry conditions for the contrary, so the South Atlantic has a greater impact than the North Atlantic. Combining SSTA patterns in the Pacific and Atlantic gives results that are similar to the sum of individual effects, with the stronger Pacific SSTAs exerting more influence despite the model's sensitivity to Atlantic conditions. Dry dynamical experiments with fixed basic states and heating perturbations confirm that interactive moist thermodynamics is crucial for accurately representing continental rainfall responses, even over short timescales. These results are generally promising for applications in operational seasonal forecasting, and this is reported in the companion paper, part 2.

Simple GCM Simulations of Rainfall Over Northeast Brazil, Part 2: Model Performance for Historical Seasonal Forecasts - Francisco das Chagas Vasconcelos Junior; Nicholas M. J. Hall; Leticia Cardoso; Aubains Hounsou‐Gbo; Eduardo S. P. R. Martins (International Journal of Climatology, 2025)
A dynamical model is used as a simple GCM to perform historical forecasts for rainfall in northeastern Brazil for the years 1982–2020. The model is forced by empirically derived source terms and includes basic parameterisations to simulate vertical diffusion, convection and condensation. Ensemble forecasts with 38 members are initiated on 1st January using persisted tropical sea surface temperature anomalies (SSTAs). Rainfall forecast performance is evaluated for the February–April (FMA) rainy season. The model reproduces the climatological precipitation in the specified Nordeste region with a mainly dry bias as the model rainfall maximum is displaced in the the northwest. Hindcasts for interannual rainfall anomalies correlate with observed values ( r = 0.46) and model variance is weaker than observed. A further set of forecast experiments with SSTAs restricted to the three major ocean basins reveals that most of the forecast skill can be attributed to the Pacific, despite the model's greater sensitivity to Atlantic SSTAs. The sum of results from the three ocean basins is close to the full hindcast result. Finally, a set of 128 forecast runs with idealised SSTAs placed regularly within the tropics is carried out to calibrate the response of modelled rainfall to remote influences. An influence function is diagnosed in the form of a tropical distribution of northeastern Brazil rainfall in mm/day per unit SSTA. It is strongly concentrated in the tropical Atlantic, with dry/wet conditions resulting from positive SSTAs in the northern/southern tropical Atlantic, in keeping with the observed covariance. The influence function is the used to construct a linear approximation to the forecast performance of the simple GCM. It has similar skill but stronger variance, and the skill is partitioned differently between Atlantic and Pacific influences.

Mortality in a cohort of WTC-exposed law-enforcement officers compared to non-WTC law-enforcement officers - Ankura Singh; Malak Khalifeh; John Violanti; Rachel Zeig-Owens; Andrew C. Todd; Moshe Z. Shapiro; Madeline E. Carwile; Christopher R. Dasaro; Jiehui Li; Janette Yung; Mark R. Farfel; Robert M. Brackbill; et al. (International Archives of Occupational and Environmental Health, 2025)
Purpose World Trade Center (WTC) rescue/recovery workers were exposed to materials hazardous to health. Previous studies found lower than expected mortality among WTC rescue/recovery workers when compared to general populations, possibly due to healthy worker effects, better healthcare access and/or incomparability of the groups. We compared mortality rates in WTC-exposed law enforcement officers (LEOs) with rates in LEOs employed by the Buffalo, NY, Police Department. We also compared both cohorts to the general population. Methods Follow-up began at the later of one year after enrollment date or 1/1/2005 and ended at the earlier of death date or 12/31/2018. Analyses were restricted to ages 40–79 years (N = 11,476 WTC LEOs, N = 1668 non-WTC LEOs). We estimated standardized mortality ratios (SMRs) in each cohort using stratum-specific US mortality rates. Relative rates (RRs) and 95% CIs were estimated for the WTC vs. the Buffalo cohort using Poisson regression models adjusted for sex, race, age-group, and calendar-period. Results 185 deaths were observed in the WTC cohort and 186 in the Buffalo cohort. All-cause and cause-specific SMRs were significantly lower in the WTC cohort. Similarly, the adjusted all-cause mortality RR for the WTC vs. Buffalo cohorts was 0.30 (95% CI = 0.23–0.40). The cause-specific mortality RRs were all significantly < 1. Conclusion We found lower overall and cause-specific mortality rates in WTC LEOs compared with both the general population and Buffalo LEOs. These results suggest that factors other than healthy worker effects, such as access to healthcare via the WTC Health Program, contribute to lower mortality rates in WTC rescue/recovery workers.

Increased Cold Tolerance of a Tropical Fish Species at the Northern Edge of Its Expanded Range - Brittany J. Hall-Scharf; Quenton M. Tuckett; Philip W. Stevens; Jeffrey E. Hill (Estuaries and Coasts, 2025)

The effect of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of smokeless powders - S.A. Kane; G.N. Cupp; M. Rangel; A. Medrano; J. Davis-Miller; C. Collins-Pisano; B. Rogers; D. Copeland; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; P.A. Prada-Tiedemann; et al. (Applied Animal Behaviour Science, 2025)

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.

Integrated biostratigraphy, chemostratigraphy and geochronology of the lower Cambrian succession in the western Stansbury Basin, South Australia - J. Castle-Jones; M. J. Betts; J. D. Holmes; R. M. Klaebe; P. A. Hall; J. L. Crowley; Z.-L. Zhang; G. A. Brock (Australian Journal of Earth Sciences, 2025)

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

Assessing riparian functioning condition for improved ecosystem services: A case study of the Back Creek watershed (Virginia, USA) - Santosh R. Ghimire; Brian Schumacher; Sherman Swanson; Robert Hall; Eric S. Hall; José Zambrana; John M. Johnston (Journal of Environmental Management, 2025)

Comparative receptor modelling for the sources of fine particulate matter (PM2.5) at urban sites in the UK - Deepchandra Srivastava; Supattarachai Saksakulkrai; W. Joe F. Acton; Daniel J. Rooney; James Hall; Siqi Hou; Mark Wolstencroft; Suzanne Bartington; Roy M. Harrison; Zongbo Shi; William J. Bloss (Atmospheric Environment, 2025)

Innovations in Wave Energy: A Case Study of TALOS-WEC’s Multi-Axis Technology - Fatemeh Nasr Esfahani; Wanan Sheng; Xiandong Ma; Carrie M. Hall; George Aggidis (Journal of Marine Science and Engineering, 2025)
The technologically advanced learning ocean system—wave energy converter (TALOS-WEC) project addresses the urgent need for sustainable and efficient energy solutions by leveraging the vast potential of wave energy. This project presents a pioneering approach to wave energy capture through its unique multi-axis and omnidirectional point absorber design. Featuring a fully enclosed power take-off (PTO) system, the TALOS-WEC harnesses energy across six degrees of freedom (DoFs) using an innovative internal reaction mass (IRM) mechanism. This configuration enables efficient energy extraction from the relative motion between the IRM and the hull, aiming for energy conversion efficiencies ranging between 75–80% under optimal conditions, while ensuring enhanced durability in harsh marine environments. The system’s adaptability is reflected in its versatile geometric configurations, including triangular, octagonal, and circular designs, customised for diverse marine conditions. Developed at Lancaster University, UK, and supported by international collaborations, the TALOS-WEC project emphasises cutting-edge advancements in hydrodynamic modelling, geometric optimisation, and control systems. Computational methodologies leverage hybrid frequency-time domain models and advanced panel codes (WAMIT, HAMS, and NEMOH) to address non-linearities in the PTO system, ensuring precise simulations and optimal performance. Structured work packages (WPs) guide the project, addressing critical aspects such as energy capture optimisation, reliability enhancement, and cost-effectiveness through innovative monitoring and control strategies. This paper provides a comprehensive overview of the TALOS-WEC, detailing its conceptual design, development, and validation. Findings demonstrate TALOS’s potential to achieve scalable, efficient, and robust wave energy conversion, contributing to the broader advancement of renewable energy technologies. The results underscore the TALOS-WEC’s role as a cutting-edge solution for harnessing oceanic energy resources, offering perspectives into its commercial viability and future scalability.

Evaluating text, icon, and graphic nutrition labels: An eye tracking experiment with Latino adults in the US - Marissa G. Hall; Anna H. Grummon; Callie Whitesell; Cristina J.Y. Lee; Quinn Errico; Tiffiany Portacio; Mirian I. Avendaño-Galdamez; M. Justin Byron; Adam O. Goldstein (Appetite, 2025)

Comment on Functional landscape connectivity for a select few: Linkages do not consistently predict wildlife movement or occupancy. Autumn R. Iverson, David Waetjen, Fraser Shilling - A.T.H. Keeley; P. Beier; R.T. Belote; M. Clark; A.P. Clevenger; T.G. Creech; L. Ehlers; J. Faselt; M. Gogol-Prokurat; K.R. Hall; M.A. Hardy; J.A. Hilty; et al. (Landscape and Urban Planning, 2025)

Obituary for Prof. Stephen (Ben) Walsh, Professor of Nephrology at University College London - Andrew M. Hall; Robert J. Unwin; Matthew Bailey; Chris Laing (Pflügers Archiv - European Journal of Physiology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Reducing real driving fuel consumption and emissions with a hydraulic hybrid vehicle - N.C. Surawski; M. Awadallah; E. Zhao; S. Zhou; T. Dunn; C. Hall; P.D. Walker (Science of The Total Environment, 2024)

Quantification of social metrics for use in optimization: An application to solid waste management - Jenny Gutierrez-Lopez; Ronald G. McGarvey; James S. Noble; Damon M. Hall; Christine Costello (Journal of Cleaner Production, 2024)

Toxicity of rare earth elements (REEs) to marine organisms: Using species sensitivity distributions to establish water quality guidelines for protecting marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Environmental Research, 2024)

Exceptions to the Heterotrophic Rule: Prevalence and Drivers of Autotrophy in Streams and Rivers - Alice M. Carter; Heili E. Lowman; Joanna R. Blaszczak; Carolina C. Barbosa; Melissa DeSiervo; Christa L. Torrens; Matthew R. Dunkle; Sarah M. Collins; Isabella Oleksy; Leon R. Katona; Robert O. Hall (Ecosystems, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Full analysis and deep learning optimization of a sustainable and eco-friendly power plant to generate green hydrogen and electricity; A zero-carbon approach - Poorya Asadbagi; Adib Mahmoodi Nasrabadi; Carrie M. Hall (Process Safety and Environmental Protection, 2024)

Within the optimal thermal range, temperature fluctuations with similar means have little effect on offspring phenotypes: A comparison of two approaches that simulate natural nest conditions - Joshua M. Hall; Sarin Tiatragul; Mallory K. Turner; Daniel A. Warner (Journal of Thermal Biology, 2024)

P21-07 The Environmental Health Language Collaborative (EHLC): harmonizing toxicology data use and sharing - M. Shatz; J. Wignall; J. Freed; P. Kaplan; C. Duncan; S. Hall; K. Vinsonhaler; H. Bledsoe; C. Schmitt (Toxicology Letters, 2024)

P20-10 Embracing regulatory compliance: Genetox meets generation SEND - S. Salazar Arenas; C. Bapat; M. Ellison; M. Wasko; F. Hall (Toxicology Letters, 2024)

Assessing daily patterns in stimulant use during the COVID-19 pandemic in Melbourne, Australia using wastewater analysis - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Phong Thai; Chang He; Fahad Ahmed; Qiuda Zheng; Phil M. Choi; Jake W. O’Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

Clean co-combustion of glycerol and methanol blends using a novel fuel-flexible injector - Timothy Hall; Derek Williams; S M Rafiul Islam; Ishaan Patel; Caleb Chakmakjian; Lulin Jiang (Fuel, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Regional impact assessment of air quality improvement: The air quality lifecourse assessment tool (AQ-LAT) for the West Midlands combined authority (WMCA) area - James Hall; Jian Zhong; Sue Jowett; Andrea Mazzeo; G. Neil Thomas; John R. Bryson; Steve Dewar; Nadia Inglis; Mark Wolstencroft; Catherine Muller; William James Bloss; Roy M. Harrison; et al. (Environmental Pollution, 2024)

Development of a New Dry Powder Aerosol Synthetic Lung Surfactant Product for Neonatal Respiratory Distress Syndrome (RDS) – Part II: In vivo Efficacy Testing in a Rabbit Surfactant Washout Model - Robert M DiBlasi; Hattie KenKnight; Niko Kontoudios; Dale Farkas; Mohammad A. M. Momin; Felicia Hall; Michael Hindle; Worth Longest (Pharmaceutical Research, 2024)

Correction: Development of a New Dry Powder Aerosol Synthetic Lung Surfactant Product for Neonatal Respiratory Distress Syndrome (RDS) – Part I: In Vitro Testing and Characterization - Mohammad A. M. Momin; Dale Farkas; Michael Hindle; Felicia Hall; Robert M. DiBlasi; Worth Longest (Pharmaceutical Research, 2024)

How to close the loop with citizen scientists to advance meaningful science - Damon M. Hall; Pedro M. Avellaneda-Lopez; Darren L. Ficklin; Jason H. Knouft; Christopher Lowry (Sustainability Science, 2024)
Citizen science yields increased scientific capacity in exchange for science literacy and promises of a more responsive science to society’s needs. Yet, citizen science projects are criticized for producing few scientific outputs and having exploitative relationships with the citizens who participate. In the eagerness to capture new data, scientists can fail to see the value of citizen scientists’ expertise beyond data generation and can forget to close the loop with outputs that benefit the public interest. Citizen scientists are experts in their local environments who, when asked, can improve scientific processes and products. To the degree that citizen scientists are relegated to data collection, we shortchange opportunities to advance science. Rather than merely critique, we present an evidence-based engagement approach for listening to citizen scientist participants and incorporating their input into science processes and products that can be retrofitted onto existing citizen science projects or integrated from a project’s inception. We offer this adaptable blueprint in four steps and illustrate this approach via a crowdsourced hydrology project on the Boyne River, USA. We show how engaging voices of citizen scientists at key points in the project improves both the products of science (a real-time ecohydrological model) and the process of conducting the science (adaptations to help improve data collection). Distinct from outreach or education, considering citizen scientists as an equally interesting site of inquiry can improve the practice and outputs of science.

Development of a New Dry Powder Aerosol Synthetic Lung Surfactant Product for Neonatal Respiratory Distress Syndrome (RDS) – Part I: In Vitro Testing and Characterization - Mohammad A. M. Momin; Dale Farkas; Michael Hindle; Felicia Hall; Robert M DiBlasi; Worth Longest (Pharmaceutical Research, 2024)
Purpose Improving the deep lung delivery of aerosol surfactant therapy (AST) with a dry powder formulation may enable significant reductions in dose while providing improved efficacy. The objective of Part I of this two-part study was to present the development of a new dry powder aerosol synthetic lung surfactant (SLS) product and to characterize performance based on aerosol formation and realistic in vitro airway testing leading to aerosol delivery recommendations for subsequent in vivo animal model experiments. Methods A new micrometer-sized SLS excipient enhanced growth (EEG) dry powder formulation was produced via spray drying and aerosolized using a positive-pressure air-jet dry powder inhaler (DPI) intended for aerosol delivery directly to intubated infants with respiratory distress syndrome (RDS) or infant-size test animals. Results The best-case design (D2) of the air-jet DPI was capable of high emitted dose (> 80% of loaded) and formed a < 2 µm mass median aerodynamic diameter (MMAD) aerosol, but was limited to ≤ 20 mg mass loadings. Testing with a realistic in vitro rabbit model indicated that over half of the loaded dose could penetrate into the lower lung regions. Using the characterization data, a dose delivery protocol was designed in which a 60 mg total loaded dose would be administered and deliver an approximate lung dose of 14.7–17.7 mg phospholipids/kg with a total aerosol delivery period < 5 min. Conclusions A high-efficiency aerosol SLS product was designed and tested that may enable an order of magnitude reduction in administered phospholipid dose, and provide rapid aerosol administration to infants with RDS.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

Preconception opioids interact with mouse strain to alter morphine withdrawal in the next generation - Anika Toorie; Claire Davidson Hall; Fair M. Vassoler; Gary Peltz; Elizabeth M. Byrnes (Psychopharmacology, 2024)

Nontargeted lipidomics of Florida seagrasses - Emily K. Griffin; Kaylie Anne Costa; Dylan Lukacsa; Justin Greenberg; Lauren M. Hall; Bradley T. Furman; Victoria M. Congdon; Trisha Green; Katherine Suchanec; John A. Bowden (Aquatic Botany, 2024)

Anticipating change: The impact of simulated seasonal heterogeneity on heat tolerances along a latitudinal cline - Jared Lush; Carla M. Sgrò; Matthew D. Hall (Ecology, 2024)
An understanding of thermal limits and variation across geographic regions is central to predicting how any population may respond to global change. Latitudinal clines, in particular, have been used to demonstrate that populations can be locally adapted to their own thermal environment and, as a result, not all populations will be equally impacted by an increase in temperature. But how robust are these signals of thermal adaptation to the other ecological challenges that animals commonly face in the wild? Seasonal changes in population density, food availability, or photoperiod are common ecological challenges that could disrupt patterns of thermal tolerance along a cline if each population differentially used these signals to anticipate future temperatures and adjust their thermal tolerances accordingly. In this study, we aimed to test the robustness of a cline in thermal tolerance to simulated signals of seasonal heterogeneity. Experimental animals were derived from clones of the Australian water flea, Daphnia carinata , sampled from nine distinct populations along a latitudinal transect in Eastern Australia. We then factorially combined summer (18 h light, 6 h dark) and winter (6 h light, 18 h dark) photoperiods with high (5 million algal cells individual −1 day −1 ) and low (1 million algal cells individual −1 day −1 ) food availabilities, before performing static heat shock assays to measure thermal tolerance. We found that the thermal tolerances of the clonal populations were sensitive to both measures of seasonal change. In general, higher food availability led to an increase in thermal tolerances, with the magnitude of the increase varying by clone. In contrast, a switch in photoperiod led to rank‐order changes in thermal tolerances, with heat resistance increasing for some clones, and decreasing for others. Heat resistance, however, still declined with increasing latitude, irrespective of the manipulation of seasonal signals, with clones from northern populations always showing greater thermal resistance, most likely driven by adaptation to winter thermal conditions. While photoperiod and food availability can clearly shape thermal tolerances for specific populations, they are unlikely to overwhelm overarching signals of thermal adaptation, and thus, observed clines in heat resistance will likely have remained robust to these forms of seasonal heterogeneity.

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Bycatch and pollution are the main threats for Burmeister's porpoises inhabiting a high-industrialized bay in the Humboldt Current System - Ana M. García-Cegarra; Anna Hall; Emma Martínez-López (Environmental Research, 2024)

The simultaneous removal of technetium and iodine from Hanford tank waste - R. Matthew Asmussen; Amy M. Westesen; Christian Alvarez; Reid A. Peterson; Elsa Cordova; Herman Cho; Shirmir D. Branch; Eric D. Walter; Gabriel B. Hall; Andrew L Orgnic; Andrew M. Carney (Chemical Engineering Journal, 2024)

People behind the “pings”; limiting authorship threatens collaboration in telemetry - L. A. Hawkes; P. Davies; A. E. Hall; T. W. Horton; T. Stamp; M. J. Witt; E. V. Sheehan (Journal of Fish Biology, 2024)

Acclimation to warmer temperatures can protect host populations from both further heat stress and the potential invasion of pathogens - Tobias E. Hector; Marta S. Shocket; Carla M. Sgrò; Matthew D. Hall (Global Change Biology, 2024)
Thermal acclimation can provide an essential buffer against heat stress for host populations, while acting simultaneously on various life‐history traits that determine population growth. In turn, the ability of a pathogen to invade a host population is intimately linked to these changes via the supply of new susceptible hosts, as well as the impact of warming on its immediate infection dynamics. Acclimation therefore has consequences for hosts and pathogens that extend beyond simply coping with heat stress—governing both population growth trajectories and, as a result, an inherent propensity for a disease outbreak to occur. The impact of thermal acclimation on heat tolerances, however, is rarely considered simultaneously with metrics of both host and pathogen population growth, and ultimately fitness. Using the host Daphnia magna and its bacterial pathogen, we investigated how thermal acclimation impacts host and pathogen performance at both the individual and population scales. We first tested the effect of maternal and direct thermal acclimation on the life‐history traits of infected and uninfected individuals, such as heat tolerance, fecundity, and lifespan, as well as pathogen infection success and spore production. We then predicted the effects of each acclimation treatment on rates of host and pathogen population increase by deriving a host's intrinsic growth rate ( r m ) and a pathogen's basic reproductive number ( R 0 ). We found that direct acclimation to warming enhanced a host's heat tolerance and rate of population growth, despite a decline in life‐history traits such as lifetime fecundity and lifespan. In contrast, pathogen performance was consistently worse under warming, with within‐host pathogen success, and ultimately the potential for disease spread, severely hampered at higher temperatures. Our results suggest that hosts could benefit more from warming than their pathogens, but only by linking multiple individual traits to population processes can the full impact of higher temperatures on host and pathogen population dynamics be realised.

Highly dynamic evolution of the chemosensory system driven by gene gain and loss across subterranean beetles - Pau Balart-García; Tessa M. Bradford; Perry G. Beasley-Hall; Slavko Polak; Steven J.B. Cooper; Rosa Fernández (Molecular Phylogenetics and Evolution, 2024)

South Atlantic Convergence Zone as Rossby wave source - Hugo A. Braga; Tercio Ambrizzi; Nicholas M. J. Hall (Theoretical and Applied Climatology, 2024)

Inherited terrestrial cosmogenic nuclides in landscapes of selective glacial erosion: lessons from Lochnagar, Eastern Grampian Mountains, Scotland - Adrian M. Hall; David E. Sugden; Steven A. Binnie; Andy Hein; Tibor Dunai; Benedikt Ritter; Margaret Stewart (Journal of Quaternary Science, 2024)
Inheritance from prior exposure often complicates the interpretation of terrestrial cosmogenic nuclide (TCN) inventories in glaciated terrain. Lochnagar, a mountain in eastern Scotland, holds a clear geomorphological record of corrie glaciation and the thinning of the last Scottish ice sheet over the last ~15 ka. Yet attempts to date the main stages in deglaciation after sampling of 21 granite boulders for 10 Be, 26 Al and 14 C from corrie moraines, an ice sheet lateral moraine and boulder spreads revealed widespread, but variable, TCN inheritance. Only the youngest boulder ages fit within the range of expected deglaciation ages. To identify the sources of geological uncertainty, we provide simple models of ice cover duration and erosion histories for plateau, corrie and strath landscape domains, identify the variable nuclide inheritance that derives from different sources for boulders in these domains, and outline the effects of rotation, splitting and erosion of boulders during glacial transport. The combined effects increase clustering around arbitrary mean TCN values that exceed deglaciation ages. A further implication is that boulders have survived beneath overriding ice sheets. Such boulder trapping at Lochnagar may have resulted from topographic controls on katabatic winds and surface ablation acting on a thinning, cold‐based ice sheet.

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Wastewater-based monitoring of the nitazene analogues: First detection of protonitazene in wastewater - Richard Bade; Dhayaalini Nadarajan; Erin M. Driver; Rolf U. Halden; Cobus Gerber; Alex Krotulski; Wayne Hall; Jochen F. Mueller (Science of The Total Environment, 2024)

Unveiling spatial mismatch in childcare supply and demand: An excess commuting analysis of home-to-childcare distance in subsidized families - Yujie Hu; Phillip Sherlock; Jing Huang; Herman T. Knopf; Jaclyn M. Hall (Journal of Transport Geography, 2024)

Mesocosm study of PAC-modified clay effects on Karenia brevis cells and toxins, chemical dynamics, and benthic invertebrate physiology - Victoria M. Devillier; Emily R. Hall; Vince Lovko; Richard Pierce; Donald M. Anderson; Kristy A. Lewis (Harmful Algae, 2024)

Remote influence on regional scale intraseasonal rainfall variability over Vietnam - Hong‐Hanh Le; Nicholas M. J. Hall; Thanh Ngo‐Duc (International Journal of Climatology, 2024)
Remote influences on intraseasonal anomalous rainfall over regions that encompass North and South Vietnam are explored using a 38‐year (1979–2016) global dataset over the extended summer (May–October). Wet and Dry composites in filtered daily data with lags of up to 2 weeks are assembled for various rainfall indices over the two subregions, including atmospheric reanalysis products and in‐situ rainfall data. On the regional scale, the moisture flux convergence correlates well with reanalysed rainfall. The large‐scale dynamics associated with these composites are described. Rainfall composites of opposing signs show asymmetrical large‐scale precursors and different pathways of influence. Wet and Dry anomalies in North Vietnam are seen to originate from Europe and propagate at high latitudes. The exact nature of the precursors is sensitive to the definition of the composite index. There is also a pathway of influence along the Asian jet, which impacts South Vietnam, especially for Wet composites which often coincide with Dry conditions in the North. South Vietnam is also influenced by tropical divergent precursors, which are again asymmetric between Wet and Dry composites.

Continuity between NASA MODIS Collection 6.1 and VIIRS Collection 2 land products - Miguel O. Román; Chris Justice; Ian Paynter; Peter B. Boucher; Sadashiva Devadiga; Arthur Endsley; Angela Erb; Mark Friedl; Huilin Gao; Louis Giglio; Josh M. Gray; Dorothy Hall; et al. (Remote Sensing of Environment, 2024)

Woody Plant–Soil Relationships in Interstitial Spaces Have Implications for Future Forests Within and Beyond Urban Areas - Gisselle A. Mejía; Peter M. Groffman; Meghan L. Avolio; Anika R. Bratt; Jeannine Cavender-Bares; Noortje H. Grijseels; Sharon J. Hall; James Heffernan; Sarah E. Hobbie; Susannah B. Lerman; Jennifer L. Morse; Desiree L. Narango; et al. (Ecosystems, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Consultative or participatory?: how environmental science graduate students envision transdisciplinarity - Jesse M. Engebretson; Zachary Piso; Michael O’Rourke; Troy E. Hall (Journal of Environmental Studies and Sciences, 2024)

Exploring the potential of combining transcranial magnetic stimulation and electroencephalography to investigate mild cognitive impairment and Alzheimer’s disease: a systematic review - J. D. Hall; Jacob M. Green; Yu-Chin A. Chen; Yilin Liu; Hangbin Zhang; Mark H. Sundman; Ying-hui Chou (GeroScience, 2024)

Radiation cataract in Heterogeneous Stock mice after γ-ray or HZE ion exposure - Norman J. Kleiman; Elijah F. Edmondson; Michael M. Weil; Christina M. Fallgren; Adam King; Catherine Schmidt; Eric J. Hall (Life Sciences in Space Research, 2024)

Pathways linking nutrient enrichment, habitat structure, and parasitism to host–resource interactions - Rachel M. Penczykowski; Michelle L. Fearon; Jessica L. Hite; Marta S. Shocket; Spencer R. Hall; Meghan A. Duffy (Oecologia, 2024)

Nitrogen availability regulates the effects of a simulated marine heatwave on carbon sequestration and phycosphere bacteria of a marine crop - Meijia Jiang; Jason M. Hall‐Spencer; Lin Gao; Zengling Ma; Guang Gao (Limnology and Oceanography, 2024)
Great hope has been pinned on seaweed cultivation as being a potent way of removing CO 2 to reduce rates of sea surface warming and acidification. Marine heatwaves and nitrogen pollution in coastal ecosystems are serious current issues that need to be better understood to inform decision making and policy. Here, we investigated the effects of a simulated heatwave and nitrogen pollution on carbon sequestration by an important seaweed crop species and its phycosphere bacteria. Gracilaria lemaneiformis was grown in ambient and high nitrogen conditions (14 and 200 μ M L −1 ). Photosynthetic rate, seaweed biomass and particulate organic carbon accumulation were significantly increased in “high nitrogen‐no heatwave” conditions. In “ambient nitrogen heatwave” conditions, the expression of genes related to photosynthesis was down regulated and the seaweeds lost more dissolved organic carbon (DOC) to the surrounding water, resulting in more refractory dissolved organic carbon (RDOC). In “high nitrogen heatwave” conditions, photosynthetic gene expression was upregulated; bacterial abundance was also increased that can explain the reduced DOC and RDOC accumulation. The simulated heatwave reduced bacterial diversity while high nitrogen alleviated this effect. These findings suggest that the economically important alga G . lemaneiformis may lose more DOC and RDOC to nearshore waters during marine heatwave events, enhancing carbon sequestration, while nitrogen enrichment has a counteractive effect.

Intensive chemical weathering in the Arctic during the Miocene Climatic Optimum - Adrian M. Hall; Dan N. Barfod; H. Albert Gilg; Finlay M. Stuart; Pertti Sarala; Thair Al-Ani (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Elucidating the corrosion characteristics of brine heater and evaporator condenser alloys during acid cleaning of MSF plants and its mitigation - Moses M. Solomon; Saviour A. Umoren; Nsidibeobong M. Solomon; Bamidele Durodola; Akeem Y. Adesina; Philip Hall; Medinat O. Osundiya (Desalination, 2024)

Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

Hurricane Effects on Seagrass and Associated Nekton Communities in the Northern Gulf of Mexico - Kelly M. Correia; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Darnell; M. Zachary Darnell; Bradley T. Furman; Margaret O. Hall; Christian T. Hayes; Charles W. Martin; Ashley McDonald; Delbert L. Smee (Estuaries and Coasts, 2024)

Global dominance of lianas over trees is driven by forest disturbance, climate and topography - Alain Senghor K. Ngute; David S. Schoeman; Marion Pfeifer; Geertje M. F. van der Heijden; Oliver L. Phillips; Michiel van Breugel; Mason J. Campbell; Chris J. Chandler; Brian J. Enquist; Rachael V. Gallagher; Christoph Gehring; Jefferson S. Hall; et al. (Global Change Biology, 2024)
Growing evidence suggests that liana competition with trees is threatening the global carbon sink by slowing the recovery of forests following disturbance. A recent theory based on local and regional evidence further proposes that the competitive success of lianas over trees is driven by interactions between forest disturbance and climate. We present the first global assessment of liana–tree relative performance in response to forest disturbance and climate drivers. Using an unprecedented dataset, we analysed 651 vegetation samples representing 26,538 lianas and 82,802 trees from 556 unique locations worldwide, derived from 83 publications. Results show that lianas perform better relative to trees (increasing liana‐to‐tree ratio) when forests are disturbed, under warmer temperatures and lower precipitation and towards the tropical lowlands. We also found that lianas can be a critical factor hindering forest recovery in disturbed forests experiencing liana‐favourable climates, as chronosequence data show that high competitive success of lianas over trees can persist for decades following disturbances, especially when the annual mean temperature exceeds 27.8°C, precipitation is less than 1614 mm and climatic water deficit is more than 829 mm. These findings reveal that degraded tropical forests with environmental conditions favouring lianas are disproportionately more vulnerable to liana dominance and thus can potentially stall succession, with important implications for the global carbon sink, and hence should be the highest priority to consider for restoration management.

Shift in algal blooms from micro‐ to macroalgae around China with increasing eutrophication and climate change - Yuan Feng; Yonglong Xiong; Jason M. Hall‐Spencer; Kailin Liu; John Beardall; Kunshan Gao; Jingke Ge; Juntian Xu; Guang Gao (Global Change Biology, 2024)
Blooms of microalgal red tides and macroalgae (e.g., green and golden tides caused by Ulva and Sargassum ) have caused widespread problems around China in recent years, but there is uncertainty around what triggers these blooms and how they interact. Here, we use 30 years of monitoring data to help answer these questions, focusing on the four main species of microalgae Prorocentrum donghaiense , Karenia mikimotoi , Noctiluca scintillans , and Skeletonema costatum ) associated with red tides in the region. The frequency of red tides increased from 1991 to 2003 and then decreased until 2020, with S. costatum red tides exhibiting the highest rate of decrease. Green tides started to occur around China in 1999 and the frequency of green tides has since been on the increase. Golden tides were first reported to occur around China in 2012. The frequency of macroalgal blooms has a negative linear relationship with the frequency and coverage of red tides around China, and a positive correlation with total nitrogen and phosphorus loads as well as with atmospheric CO 2 and sea surface temperature (SST). Increased outbreaks of macroalgal blooms are very likely due to worsening levels of eutrophication, combined with rising CO 2 and SST, which contribute to the reduced frequency of red tides. The increasing grazing rate of microzooplankton also results in the decline in areas affected by red tides. This study shows a clear shift of algal blooms from microalgae to macroalgae around China over the past 30 years driven by the combination of eutrophication, climate change, and grazing stress, indicating a fundamental change in coastal systems in the region.

Improving the performance of post-consumer resin feedstocks for rigid packaging applications: A pilot-scale assessment - A.R. McLauchlin; D Hall; D Feldman; P Anderson; M Newman; T Hasell; T.O. McDonald (Resources, Conservation and Recycling, 2023)

Standing Litter Modifies Top-Down Effects of Large Herbivores on a Grassland Plant Community - Zhongnan Wang; Zhiwei Zhong; James F. Cahill; Emily M. Holden; Ho Yi Wan; Logan B. Hysen; Ying Gao; Zhaojun Wang; Oyuntsetseg Batlai; J. Hall Cushman; Deli Wang; Xiaofei Li (Ecosystems, 2023)

Nature-based solutions for leveed river corridors - Matthew L. Chambers; Charles B. van Rees; Brian P. Bledsoe; David Crane; Susana Ferreira; Damon M. Hall; Rod W. Lammers; Craig E. Landry; Donald R. Nelson; Matt Shudtz; Burton C. Suedel (Anthropocene, 2023)

Monitoring spore washoff during a biological contamination incident response using automated stormwater samplers and sensors to predict contamination movement - Anne M. Mikelonis; John Hall; Chris A. Dunn; Timothy McArthur; Garrett Wiley; Chelsea L. Hintz; Joshua Steenbock; Shannon Serre; Michael Worth Calfee; Michael Pirhalla (Science of The Total Environment, 2023)

Prediction of the Renal Organic Anion Transporter 1 (OAT1)- Mediated Drug Interactions for LY404039, the Active Metabolite of Pomaglumetad Methionil - Y. Anne Pak; Maria M. Posada; James Bacon; Amanda Long; William Annes; Jennifer Witcher; Malcolm Mitchell; Rommel G. Tirona; Stephen D. Hall; Kathleen M. Hillgren (Pharmaceutical Research, 2023)

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

PFAS levels in paired drinking water and serum samples collected from an exposed community in Central North Carolina - Samantha M. Hall; Sharon Zhang; George H. Tait; Kate Hoffman; David N. Collier; Jane A. Hoppin; Heather M. Stapleton (Science of The Total Environment, 2023)

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

Barriers and Facilitators to a Healthy Community Environment During COVID-19: Perceptions of Extension Nutrition Educators and Other Key Community Stakeholders - E. Varela; J. Zeldman; A. Kuch; Y. Wang; M. Shushari; E. Hall; J. McNamara; J. Morrell; T. Tolar-Peterson; O. Brown; M. Olfert; L. Franzen-Castle; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Exposure of blue crab (Callinectes sapidus) to modified clay treatment of Karenia brevis as a bloom control strategy - Victoria M. Devillier; Emily R. Hall; Donald M. Anderson; Kristy A. Lewis (Harmful Algae, 2023)

The effect of biochemical composition on the renewable crude oil produced from hydrothermal liquefaction of biosolids - Jasim M. Al-juboori; David M. Lewis; Peter J. Ashman; Tony Hall; Philip J. van Eyk (Biomass and Bioenergy, 2023)

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

Can we predict visitor movement? Using step selection function analysis to map high probability camping areas in a remote Alaskan wilderness - Susan A. Sidder; Ashley D'Antonio; Troy E. Hall; Jonathan B. Dinkins; Evan M. Bredeweg; Christopher A. Monz (Landscape and Urban Planning, 2023)

Fine-tuning the CROPGRO-Sunflower model and its application to the quantification of crop responses to environmental and management variables - Ignacio M. Rodriguez; Jorge L. Mercau; Pablo A. Cipriotti; Antonio J. Hall; Juan P. Monzon (Field Crops Research, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Effects of crustal assimilation on 238U-230Th disequilibria in continental arc settings - L.B. Kant; K.W.W. Sims; G.M. Yogodzinski; J.M. Garrison; J. Blichert-Toft; M. Reagan; C.L. Waters; T.P. Mathews; S.R. Scott; P.A. Mothes; M.L. Hall; P. Ramón; et al. (Geochimica et Cosmochimica Acta, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Antimicrobial Effects of Plasma-Activated Simulated Seawater (PASW) on Total Coliform and Escherichia coli in Live Oysters during Static Depuration - Vashti M. Campbell; Steven Hall; Deepti Salvi (Fishes, 2023)
Recently, our in vitro study on the effects of plasma-activated simulated seawater (PASW) demonstrated its potential as a novel, alternative disinfectant in oyster depuration. In this current study, PASW’s physicochemical and antimicrobial properties were identified and its effects on oyster quality were observed. Simulated seawater (SS) activated by plasma for 10 min (PASW10) increased in temperature, oxidation reduction potential, and electrical conductivity with a decrease in those parameters after 1:1 dilution with SS (PASW10 (1:1)). The pH decreased immediately after plasma activation and subsequently increased after dilution. Nitrate and nitrite concentrations were higher in PASW10 (1:1) compared to PASW10 (3:1). No free available chlorine was detected in undiluted PASW10. Processing using SS and PASW10 (1:1) depuration and refrigeration of E. coli-bioaccumulated oysters was observed. Significantly higher reductions in total coliform and E. coli were noted for PASW10 (1:1) treated oyster samples after 24 h compared to refrigerated samples. No significant differences in values for condition index or biting force of oyster meats were observed for the processed samples after 24 h. Overall, the novel and environment-friendly PASW could be used as an alternative antimicrobial disinfectant in oyster depuration systems because it does not negatively affect an oyster’s viability or quality.

Corrigendum: Symbiont composition and coral genotype determines massive coral species performance under end-of-century climate scenarios - Courtney N. Klepac; Katherine R. Eaton; Chelsea G. Petrik; Lindsay N. Arick; Emily R. Hall; Erinn M. Muller (Frontiers in Marine Science, 2023)

Legume re-establishment in northern temperate grasslands following application of aminocyclopyrachlor and aminopyralid - Edward W. Bork; Amanda J. Miller; Linda M. Hall (Crop Protection, 2023)

PFAS surveillance in abiotic matrices within vital aquatic habitats throughout Florida - Emily K. Griffin; Lauren M. Hall; Melynda A. Brown; Arielle Taylor-Manges; Trisha Green; Katherine Suchanec; Bradley T. Furman; Victoria M. Congdon; Sara S. Wilson; Todd Z. Osborne; Shawn Martin; Emma A. Schultz; et al. (Marine Pollution Bulletin, 2023)

Thallium toxicity to temperate and tropical marine organisms: Derivation of water quality guidelines to protect marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Marine Pollution Bulletin, 2023)

Correction to: Evaluating How Exposure to Scientific Role Models and Work-Based Microbadging Influences STEM Career Mindsets in Underrepresented Groups - Duncan Davis-Hall; Laura Farrelly; Melissa Risteff; Chelsea M. Magin (Biomedical Engineering Education, 2023)

Snow crab (Chionoecetes opilio) hemocytes and hepatopancreas transcriptomes: identification, validation, and application of immune-relevant biomarkers of exposure to noise - Jennifer R. Hall; Sarah J. Lehnert; Emmanuel Gonzalez; Jacqueline M. Hanlon; Surendra Kumar; Corey J. Morris; Matthew L. Rise (Frontiers in Marine Science, 2023)
The snow crab ( Chionoecetes opilio ) fishery off the east coast of Newfoundland and Labrador, Canada, has been impacted by annual seismic oil and gas surveying in recent decades, and commercial crab harvesters are concerned that it could potentially affect this resource. A laboratory study was performed to investigate the effects of chronic noise exposure on the transcriptomes of snow crab hemocytes and hepatopancreas, which are important in immunity, metabolism and response to environmental stress. Snow crab were held in replicate control or experimental tanks; on alternating days, the experimental tanks were exposed to noise from an underwater speaker which played a recording of a seismic airgun firing every 10 sec in a continuous loop for ~ 22 weeks (chronic noise). RNA sequencing was used to identify candidate noise-responsive molecular biomarkers in both hemocytes and hepatopancreas. The quantified transcripts of individuals (i.e. n=10 from each of the four groups) were compared using DESeq2, identifying over 300 noise-responsive transcripts in each cell/tissue type. Real-time quantitative polymerase chain reaction (qPCR) assays were designed and run for 61 of these transcripts with significant BLASTx hits. One transcript ( rgs2 ) was significantly (p < 0.05) higher expressed in both hemocytes and hepatopancreas in response to noise; five and seven other transcripts were either significant or showed a non-significant trend of differential expression (0.05 < p ≤ 0.1) in hemocytes (e.g. cfb upregulated, sacs and myof downregulated) and hepatopancreas (e.g. gpx3 and atf3 upregulated, sult1c4 downregulated), respectively. To further investigate the performance and utility of these candidate biomarkers in the field, expression levels of 25 selected transcripts were then examined in the hepatopancreas of snow crab that had been subjected to 2D and 3D seismic surveying using both qPCR and multivariate statistical analyses. Overall, few of these biomarkers showed consistent results in field-collected snow crab, highlighting the need to combine lab and field-based studies to fully evaluate the utility of biomarkers. Nonetheless, our study still identified noise-responsive biomarkers in both settings (including stress and immune relevant genes), providing valuable information for understanding the impact of ocean noise on snow crab physiology and health.

Extreme low-flow conditions in a dual-chamber denitrification bioreactor contribute to pollution swapping with low landscape-scale impact - Lindsey M. Hartfiel; Natasha L. Hoover; Steven J. Hall; Thomas M. Isenhart; Carmen L. Gomes; Michelle L. Soupir (Science of The Total Environment, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Bi-functional antibody-CRISPR/Cas12a ribonucleoprotein conjugate for improved immunoassay performance - Fei Deng; Yi Li; Tim Hall; Graham Vesey; Ewa M. Goldys (Analytica Chimica Acta, 2023)

Poriferans rift apart: molecular demosponge biodiversity in Central and French Polynesia and comparison with adjacent marine provinces of the Central Indo-Pacific - Adrian Galitz; Merrick Ekins; Eric Folcher; Gabriele Büttner; Kathryn Hall; John N. A. Hooper; Maggie M. Reddy; Simone Schätzle; Olivier P. Thomas; Gert Wörheide; Sylvain Petek; Cécile Debitus; et al. (Biodiversity and Conservation, 2023)
The distribution of marine sponges in the tropical Southwest Pacific Ocean is largely unexplored despite the vital ecological role of sponges in coral reefs and their value as sources of metabolites for drug design. Several collection campaigns to the French Polynesian archipelagos (Society, Marquesas, Tuamotu, Gambier, and Austral) were conducted to assess the bio- and chemodiversity of the island groups. In the course of these scientific expeditions, more than 200 identified sponge specimens were acquired, for which we were able to assign 102 Molecular Operational Taxonomic Units (MOTUs). Based on these MOTUs, we assessed, in the largest analysis of its kind for this area to date, the sponge composition and faunistic overlaps of the marine province Southeast Polynesia with Marquesas and Central Polynesia. We also compared the sponge fauna of these Eastern Indo-Pacific provinces with marine provinces of the adjacent Central Indo-Pacific realm. Our findings corroborate that sponge faunal similarity within marine realms is higher than among realms, and follows the marine barriers to gene flow observed for other taxa. We detected high levels of provincial endemism for marine sponges, consistent with findings from other Indo-Pacific regions. At the level of province, geographical distance and ocean surface currents influence faunal similarity, and constitute the primary factors for the connectivity of sponge faunas between the disjunct and remote island groups in the tropical Southwest Pacific Ocean.

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Geostationary active fire products validation: GOES-17 ABI, GOES-16 ABI, and Himawari AHI - J.V. Hall; W. Schroeder; K. Rishmawi; M. Wooster; C.C. Schmidt; C. Huang; I. Csiszar; L. Giglio (International Journal of Remote Sensing, 2023)

Ocean acidification stunts molluscan growth at CO2 seeps - Liqiang Zhao; Ben P. Harvey; Tomihiko Higuchi; Sylvain Agostini; Kentaro Tanaka; Naoko Murakami-Sugihara; Holly Morgan; Phoebe Baker; Jason M. Hall-Spencer; Kotaro Shirai (Science of The Total Environment, 2023)

SARS-CoV-2 vaccinated hamsters show distinctive lung pathology with Th-2 skewed immune response following infection - R. de Jong; S. Vreman; K. Wiese; B. Small; N. Gerhards; K. Bewley; Y. Hall; F.J. Salguero; M. Caroll; N. Oreshkova (Journal of Comparative Pathology, 2023)

Short-stature and tall maize hybrids have a similar yield response to split-rate vs. pre-plant N applications, but differ in biomass and nitrogen partitioning - Kevin R. Kosola; Magen S. Eller; Frank G. Dohleman; Lia Olmedo-Pico; Brad Bernhard; Eric Winans; Ty J. Barten; Lillian Brzostowski; Lesley R. Murphy; Chiyu Gu; Lyle Ralston; Mike Hall; et al. (Field Crops Research, 2023)

Community composition of bacteria isolated from Swiss banknotes varies depending on collection environment - Anna M. Bischofberger; Alex R. Hall (Molecular Ecology, 2023)
Humans interact constantly with surfaces and associated microbial communities in the environment. The factors shaping the composition of these communities are poorly understood: some proposed explanations emphasize the influence of local habitat conditions (niche‐based explanations), while others point to geographic structure and the distance among sampled locations (dispersal‐based explanations). However, the relative roles of these different drivers for microbial community assembly on human‐associated surfaces are not clear. Here, we used a combination of sampling, sequencing (16S rRNA) and culturing to show that the composition of banknote‐associated bacterial communities varies depending on the local collection environment. Using banknotes collected from various locations and types of shops across Switzerland, we found taxonomic diversity dominated by families such as Pseudomonadaceae and Staphylococcaceae , but with banknote samples from particular types of shops (especially butcher shops) having distinct community structure. By contrast, we found no evidence of geographic structure: similarity of community composition did not decrease with increasing distance among sampled locations. These results show that microbial communities associated with banknotes, one of the most commonly encountered and exchanged human‐associated surfaces, can reflect the local environmental conditions (in this case, the type of shop), and the signal for this type of variation was stronger than that for geographic structure among the locations sampled here.

Lowering temperature to 1 °C results in physiological changes, stress and mortality in cultured Atlantic Salmon (Salmo salar) - Émile Vadboncoeur; Charlotte Nelson; Jennifer R. Hall; Kathy A. Clow; Rebeccah M. Sandrelli; Colin J. Brauner; Andrew K. Swanson; A. Kurt Gamperl (Aquaculture, 2023)

Effects of variation in natural and artificial light at night on acoustic communication: a review and prospectus - Ashton L. Dickerson; Michelle L. Hall; Therésa M. Jones (Animal Behaviour, 2023)

Metabolomics and sensory evaluation of white asparagus ingredients in instant soups unveil important (off-)flavours - Eirini Pegiou; Joanne W. Siccama; Roland Mumm; Lu Zhang; Doris M. Jacobs; Xavier Y. Lauteslager; Marcia T. Knoop; Maarten A.I. Schutyser; Robert D. Hall (Food Chemistry, 2023)

Ocean acidification increases the impact of typhoons on algal communities - Callum J. Hudson; Sylvain Agostini; Shigeki Wada; Jason M. Hall-Spencer; Sean D. Connell; Ben P. Harvey (Science of The Total Environment, 2023)

Gestational organophosphate ester exposure and preschool attention-deficit/hyperactivity disorder in the Norwegian Mother, Father, and Child cohort study - Amber M. Hall; Amanda M. Ramos; Samantha SM. Drover; Giehae Choi; Alexander P. Keil; David B. Richardson; Chantel L. Martin; Andrew F. Olshan; Gro D. Villanger; Ted Reichborn-Kjennerud; Pål Zeiner; Kristin R. Øvergaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Investigation of the chemical composition of antibacterial Psidium guajava extract and partitions against foodborne pathogens - Audrey M. Hall; Swati Baskiyar; Kabre L. Heck; Michelle D. Hayden; Chang Ren; Chris Nguyen; Cheryl D. Seals; Emefa Monu; Angela I. Calderón (Food Chemistry, 2023)

Intra-urban land use maps for a global sample of cities from Sentinel-2 satellite imagery and computer vision - Brookie Guzder-Williams; Eric Mackres; Shlomo Angel; Alejandro M. Blei; Patrick Lamson-Hall (Computers, Environment and Urban Systems, 2023)

Characterisation of chemical properties of the produced organic fractions via hydrothermal liquefaction of biosolids from a wastewater treatment plant - Jasim M. Al-juboori; David M. Lewis; Tony Hall; Philip J. van Eyk (Biomass and Bioenergy, 2023)

Aluminium-normalised trace-element paleoredox proxies and their application to the study of the conditions of Burgess Shale-type preservation - K. C. Meehan; W. G. Powell; D. M. McKirdy; P. A. Hall; C. Nedin; P. A. Johnston; C. J. Collom (Australian Journal of Earth Sciences, 2023)

Symbiont composition and coral genotype determines massive coral species performance under end-of-century climate scenarios - Courtney N. Klepac; Katherine R. Eaton; Chelsea G. Petrik; Lindsay N. Arick; Emily R. Hall; Erinn M. Muller (Frontiers in Marine Science, 2023)
The recent decline of coral health and substantial loss of coral cover along Florida’s Coral Reef (FCR) results from local stressors such as degraded water quality and disease outbreaks in addition to anthropogenically driven global stressors including ocean warming and acidification. Intervention strategies intended for the restoration of degraded reef habitats need a better understanding of the influence of ocean warming and acidification on coral health to target coral species and individual genotypes that may be more resistant or resilient to such stressors. Here, we examined a suite of physiological traits (coral host and algal symbiont) in response to experimentally elevated water temperatures and p CO 2 levels, both separately and in concert, using threatened reef-building corals Pseudodiploria clivosa and Orbicella faveolata reared within a land-based coral nursery. After two months of exposure, responses differed by coral species, where P. clivosa showed declined physiology in response to combined ocean warming and acidification stress and ocean warming alone, whereas O. faveolata showed a positive response under ocean acidification. Responses to temperature could be associated with the algal symbionts harbored, as P. clivosa was dominated by the thermally sensitive Breviolum , and O. faveolata was dominated by the thermally tolerant Durusdinium . Additionally, corals were raised in well-sourced seawater that was naturally high in p CO 2 , which could have led to corals acclimating to acidified conditions. Of the three P. clivosa genets tested, we determined a top-performing genotype under the combined warming and acidification treatment. O. faveolata , however, displayed high genet variation by treatment and phenotypic trait, making genotype performance rankings challenging to discern. The evidence provided in this study demonstrates that high phenotypic variation in nursery-reared corals contributes to variable warming-acidification responses, suggesting that high-standing genetic variation in nursery-reared corals could support diverse coral restoration population outcomes along FCR.

Biochemical metabolomic profiling of the Crown-of-Thorns Starfish (Acanthaster): New insight into its biology for improved pest management - Omar Mendoza-Porras; Thao V. Nguyen; Rohan M. Shah; Peter Thomas-Hall; Lee Bastin; Dione J. Deaker; Cherie A. Motti; Maria Byrne; David J. Beale (Science of The Total Environment, 2023)

A 15-year follow-up study of mortality in a pooled cohort of World Trade Center rescue and recovery workers - Jiehui Li; Charles B. Hall; Janette Yung; Rebecca D. Kehm; Rachel Zeig-Owens; Ankura Singh; James E. Cone; Robert M. Brackbill; Mark R. Farfel; Baozhen Qiao; Maria J. Schymura; Moshe Z. Shapiro; et al. (Environmental Research, 2023)

Atlantic salmon adapt to low dietary n-3 PUFA and warmer water temperatures by increasing feed intake and expression of n-3 biosynthesis-related transcripts - Stefanie M. Colombo; Suzanne M. Budge; Jennifer R. Hall; Jovana Kornicer; Nolan White (Fish Physiology and Biochemistry, 2023)

Neuroimaging and immunological features of neurocognitive function related to substance use in people with HIV - David M. Murdoch; Richard Barfield; Cliburn Chan; Sheri L. Towe; Ryan P. Bell; Alicia Volkheimer; Joyce Choe; Shana A. Hall; Miles Berger; Jichun Xie; Christina S. Meade (Journal of NeuroVirology, 2023)

Turbulent kinetic energy dissipation rate and associated fluxes in the western tropical Atlantic estimated from ocean glider observations - Peter M. F. Sheehan; Gillian M. Damerell; Philip J. Leadbitter; Karen J. Heywood; Rob A. Hall (Ocean Science, 2023)
Ocean gliders enable us to collect the high-resolution microstructure observations necessary to calculate the dissipation rate of turbulent kinetic energy, ε, on timescales of weeks to months: far longer than is normally possible using traditional ship-based platforms. Slocum gliders have previously been used to this end; here, we report the first detailed estimates of ε calculated using the Batchelor spectrum method on observations collected by a FP07 fast thermistor mounted on a Seaglider. We use these same fast thermistor observations to calculate ε following the Thorpe scale method and find very good agreement between the two methods. The Thorpe scale method yields larger values of ε, but the average difference, which is less than an order of magnitude, is smaller than reported elsewhere. The spatio-temporal distribution of ε is comparable for both methods. Maximum values of ε (10−7 W kg−1) are observed in the surface mixed layer; values of approximately 10−9 W kg−1 are observed between approximately 200 and 500 m depth. These two layers are separated by a 100 m thick layer of low ε (10−10 W kg−1), which is co-located with a high-salinity layer of Subtropical Underwater and a peak in the strength of stratification. We calculate the turbulent heat and salt fluxes associated with the observed turbulence. Between 200 and 500 m, ε induces downward fluxes of both properties that, if typical of the annual average, would have a very small influence on the heat and salt content of the overlying salinity-maximum layer. We compare these turbulent fluxes with two estimates of double-diffusive fluxes that occur in regions susceptible to salt fingers, such as the western tropical Atlantic. We find that the double-diffusive fluxes of both heat and salt are larger than the corresponding turbulent fluxes.

Evaluating How Exposure to Scientific Role Models and Work-Based Microbadging Influences STEM Career Mindsets in Underrepresented Groups - Duncan Davis-Hall; Laura Farrelly; Melissa Risteff; Chelsea M. Magin (Biomedical Engineering Education, 2023)

Sustainable pathways towards climate and biodiversity goals in the UK: the importance of managing land-use synergies and trade-offs - Alison C. Smith; Paula A. Harrison; Nicholas J. Leach; H. Charles J. Godfray; Jim W. Hall; Sarah M. Jones; Sarah S. Gall; Michael Obersteiner (Sustainability Science, 2023)
Agricultural and environmental policies are being fundamentally reviewed and redesigned in the UK following its exit from the European Union. The UK government and the Devolved Administrations recognise that current land use is not sustainable and that there is now an unprecedented opportunity to define a better land strategy that responds fully to the interconnected challenges of climate change, biodiversity loss and sustainable development. This paper presents evidence from three pathways (current trends, sustainable medium ambition, and sustainable high ambition) to mid-century that were co-created with UK policymakers. The pathways were applied to a national integrated food and land-use model (the FABLE calculator) to explore potential synergies and trade-offs between achieving multiple sustainability targets under limited land availability and constraints to balance food supply and demand at national and global levels. Results show that under the Current Trends pathway all unprotected open natural land would be converted to urban, agriculture and afforested land, with the consequence that from 2030 onwards tree planting targets could not be met. In contrast, the two sustainable pathways illustrate how dietary change, agricultural productivity improvements and waste reduction can free up land for nature recovery and carbon sequestration. This enables a transition to a sustainable food and land-use system that provides a net carbon sink with up to 44% of land able to support biodiversity conservation. We highlight key trade-offs and synergies, which are important to consider for designing and implementing emerging national policies. These include the strong dependence of climate, food and biodiversity targets on dietary shifts, sustainable improvements in agricultural productivity, improved land-use design for protecting and restoring nature, and rapid reductions in food loss and waste.

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Relationship between interhemispheric Rossby wave propagation and South Atlantic convergence zone during La Niña years - Hugo A. Braga; Tercio Ambrizzi; Nicholas M. J. Hall (International Journal of Climatology, 2022)
Through a set of observational analyses and baroclinic model experiments, we show that during La Niña conditions a wave train in North Pacific propagates eastwards along the Asian jet, crosses the equator and interacts with the SACZ through an equatorial window in the East Pacific. Composites of active SACZ for November–March of 1979–2013 are used, drawn from the full dataset and also from just the La Niña years. The data are filtered in two‐time bands: 20–90 days (intraseasonal) and >200 days (interannual). Interhemispheric waveguides are identified in the anomalous SACZ composites during La Niña years. A similar wave pattern is simulated by a baroclinic atmospheric model with a fixed La Niña basic state where a thermal forcing anomaly is added on Southeast Asia. This La Niña basic state favours anomalous westerly equatorial flow at high levels, enabling a connection between Asia and South America around 15 days.

Stability of patch‐turnover relationships under equilibrium and nonequilibrium metapopulation dynamics driven by biogeography - Steven R. Beissinger; Sean M. Peterson; Laurie A. Hall; Nathan Van Schmidt; Jerry Tecklin; Benjamin B. Risk; Orien M. Richmond; Tony J. Kovach; A. Marm Kilpatrick (Ecology Letters, 2022)
Two controversial tenets of metapopulation biology are whether patch quality and the surrounding matrix are more important to turnover (colonisation and extinction) than biogeography (patch area and isolation) and whether factors governing turnover during equilibrium also dominate nonequilibrium dynamics. We tested both tenets using 18 years of surveys for two secretive wetland birds, black and Virginia rails, during (1) a period of equilibrium with stable occupancy and (2) after drought and arrival of West Nile Virus (WNV), which resulted in WNV infections in rails, increased extinction and decreased colonisation probabilities modified by WNV, nonequilibrium dynamics for both species and occupancy decline for black rails. Area (primarily) and isolation (secondarily) drove turnover during both stable and unstable metapopulation dynamics, greatly exceeding the effects of patch quality and matrix conditions. Moreover, slopes between turnover and patch characteristics changed little between equilibrium and nonequilibrium, confirming the overriding influences of biogeographic factors on turnover.

Air pollution induces Staphylococcus aureus USA300 respiratory tract colonization mediated by specific bacterial genetic responses involving the global virulence gene regulators Agr and Sae - Jo Purves; Shane J. K. Hussey; Louise Corscadden; Lillie Purser; Andie Hall; Raju Misra; Liza Selley; Paul S. Monks; Julian M. Ketley; Peter W. Andrew; Julie A. Morrissey (Environmental Microbiology, 2022)
Summary Exposure to particulate matter (PM), a major component of air pollution, is associated with exacerbation of chronic respiratory disease, and infectious diseases such as community‐acquired pneumonia. Although PM can cause adverse health effects through direct damage to host cells, our previous study showed that PM can also impact bacterial behaviour by promoting in vivo colonization. In this study we describe the genetic mechanisms involved in the bacterial response to exposure to black carbon (BC), a constituent of PM found in most sources of air pollution. We show that Staphylococcus aureus strain USA300 LAC grown in BC prior to inoculation showed increased murine respiratory tract colonization and pulmonary invasion in vivo , as well as adhesion and invasion of human epithelial cells in vitro . Global transcriptional analysis showed that BC has a widespread effect on S . aureus transcriptional responses, altering the regulation of the major virulence gene regulators Sae and Agr and causing increased expression of genes encoding toxins, proteases and immune evasion factors. Together these data describe a previously unrecognized causative mechanism of air pollution‐associated infection, in that exposure to BC can increase bacterial colonization and virulence factor expression by acting directly on the bacterium rather than via the host.

The production of dissolved organic carbon by macroalgae and its consumption by marine bacteria: Implications for coastal ecosystems - Jack R. Hall; Gerli Albert; Isla M. Twigg; Federico Baltar; Christopher D. Hepburn; Georg Martin (Frontiers in Marine Science, 2022)
Through the fixation of large quantities of dissolved inorganic carbon (DIC), macroalgae facilitate the energetic foundation of highly productive coastal ecosystems. While the processes controlling photosynthesis and carbon fixation by macroalgae are well known, the fate of organic matter fixed by macroalgae is less well understood. This study quantified release rates of DOC by three ecologically significant Baltic macroalgae species: the perennial habitat forming Fucus vesiculosus and Furcellaria lumbricalis , and the seasonal fast-growing Ulva intestinalis , under both light and dark conditions. The released products were assessed using bacterial incubations whereby radiolabeled leucine was used to evaluate the uptake and lability of these products by marine heterotrophic bacteria. DOC was found to be released by both F. vesiculosus and U . intestinalis at rates of 0.27 mg C·h −1 under light and 0.13 mg C·h −1 per unit of dry mass under dark treatments, respectively, whereas F. lumbricalis DOC release was observed to be negligible under both light and dark. Our findings further validate previous hypotheses that factors such as photosynthetic activity are a primary driver behind DOC release and that DOC release is not an entirely passive process. Additionally, we reaffirm the need to relate a given species life characteristics and habitat in order to understand why DOC products are released. The consumption of macroalgae-derived DOC by heterotrophic bacteria reveals that released DOC is variable in its lability. After a period of 12 h and under maximum photosynthetic conditions, the release of DOC by F. vesiculosus and U . intestinalis achieved a peak rate of 219 µg C·L −1 ·day −1 and 214 µg C·L −1 ·day −1 for each gram of dry weight material, respectively, directly into the microbial loop via heterotrophic bacterial consumption. In contrast, F. lumbricalis ’ low rate of DOC release and the subsequent low bacterial consumption indicate that habitats dominated by this species have a reduced importance in the transfer energy via the microbial loop. These findings have implications for how we view carbon transfer within coastal food webs and highlight how changes in species composition and coverage may dramatically affect coastal ecosystem productivity through the microbial loop.

Metabolic mechanisms of acute proximal tubular injury - Andrew M. Hall; Sophie de Seigneux (Pflügers Archiv - European Journal of Physiology, 2022)
Damage to the proximal tubule (PT) is the most frequent cause of acute kidney injury (AKI) in humans. Diagnostic and treatment options for AKI are currently limited, and a deeper understanding of pathogenic mechanisms at a cellular level is required to rectify this situation. Metabolism in the PT is complex and closely coupled to solute transport function. Recent studies have shown that major changes in PT metabolism occur during AKI and have highlighted some potential targets for intervention. However, translating these insights into effective new therapies still represents a substantial challenge. In this article, in addition to providing a brief overview of the current state of the field, we will highlight three emerging areas that we feel are worthy of greater attention. First, we will discuss the role of axial heterogeneity in cellular function along the PT in determining baseline susceptibility to different metabolic hits. Second, we will emphasize that elucidating insult specific pathogenic mechanisms will likely be critical in devising more personalized treatments for AKI. Finally, we will argue that uncovering links between tubular metabolism and whole-body homeostasis will identify new strategies to try to reduce the considerable morbidity and mortality associated with AKI. These concepts will be illustrated by examples of recent studies emanating from the authors’ laboratories and performed under the auspices of the Swiss National Competence Center for Kidney Research (NCCR Kidney.ch).

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Large-scale tree planting initiatives as an opportunity to derive carbon and biodiversity co-benefits: a case study from Aotearoa New Zealand - Febyana Suryaningrum; Rebecca M. Jarvis; Hannah L. Buckley; David Hall; Bradley S. Case (New Forests, 2022)

Zooplankton Dominance Shift in Response to Climate-Driven Salinity Change: A Mesocosm Study - Clio A. M. Hall; Aleksandra M. Lewandowska (Frontiers in Marine Science, 2022)
Climate change predictions indicate global changes in salinity with negative implications for plankton food webs; an important baseline for functioning of marine ecosystems. Current understanding of how salinity change will impact plankton communities is mostly limited to the salinization of freshwater environments, with little known about the effects of changing salinity in marine systems. In this study, we investigate the effect of salinity change on zooplankton communities under different salinity change scenarios of the Baltic Sea. Projections for future salinity change derived from regional physical-biogeochemical models were used to set-up an outdoor mesocosm experiment in the coastal area of the Gulf of Finland. Each mesocosm was inoculated with natural plankton using a mixture of both marine and freshwater communities, mimicking the natural influx of freshwater species from rivers into the Baltic Sea. Zooplankton diversity and composition changed possibly due to different salinity tolerances among the species. Among zooplankton, rotifers dominated in low salinities (74%) and cladocerans and copepods (69%) in high salinities. Our results suggest that the zooplankton community will shift to a rotifer dominated community in areas with declining salinity due to the intolerance of other zooplankton groups to freshening.

SAF-A mutants disrupt chromatin structure through dominant negative effects on RNAs associated with chromatin - Heather J. Kolpa; Kevin M. Creamer; Lisa L. Hall; Jeanne B. Lawrence (Mammalian Genome, 2022)
Here we provide a brief review of relevant background before presenting results of our investigation into the interplay between scaffold attachment factor A (SAF-A), chromatin-associated RNAs, and DNA condensation. SAF-A, also termed heterogenous nuclear protein U (hnRNP U), is a ubiquitous nuclear scaffold protein that was implicated in XIST RNA localization to the inactive X-chromosome (Xi) but also reported to maintain open DNA packaging in euchromatin. Here we use several means to perturb SAF-A and examine potential impacts on the broad association of RNAs on euchromatin, and on chromatin compaction. SAF-A has an N-terminal DNA binding domain and C-terminal RNA binding domain, and a prominent model has been that the protein provides a single-molecule bridge between XIST RNA and chromatin. Here analysis of the impact of SAF-A on broad RNA-chromatin interactions indicate greater biological complexity. We focus on SAF-A’s role with repeat-rich C 0 T-1 hnRNA (repeat-rich heterogeneous nuclear RNA), shown recently to comprise mostly intronic sequences of pre-mRNAs and diverse long non-coding RNAs (lncRNAs). Our results show that SAF-A mutants cause dramatic changes to cytological chromatin condensation through dominant negative effects on C 0 T-1 RNA’s association with euchromatin, and likely other nuclear scaffold factors. In contrast, depletion of SAF-A by RNA interference (RNAi) had no discernible impact on C 0 T-1 RNA, nor did it cause similarly marked chromatin changes as did three different SAF-A mutations. Overall results support the concept that repeat-rich, chromatin-associated RNAs interact with multiple RNA binding proteins (RBPs) in a complex dynamic meshwork that is integral to larger-scale chromatin architecture and collectively influences cytological-scale DNA condensation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison of Serum, Plasma, and Liver Zinc Measurements by AAS, ICP-OES, and ICP-MS in Diverse Laboratory Settings - Andrew G. Hall; Janet C. King; Christine M. McDonald (Biological Trace Element Research, 2022)
Progress improving zinc nutrition globally is slowed by limited understanding of population zinc status. This challenge is compounded when small differences in measurement can bias the determination of zinc deficiency rates. Our objective was to evaluate zinc analytical accuracy and precision among different instrument types and sample matrices using a standardized method. Participating laboratories analyzed zinc content of plasma, serum, liver samples, and controls, using a standardized method based on current practice. Instrument calibration and drift were evaluated using a zinc standard. Accuracy was evaluated by percent error vs. reference, and precision by coefficient of variation (CV). Seven laboratories in 4 countries running 9 instruments completed the exercise: 4 atomic absorbance spectrometers (AAS), 1 inductively coupled plasma optical emission spectrometer (ICP-OES), and 4 ICP mass spectrometers (ICP-MS). Calibration differed between individual instruments up to 18.9% ( p < 0.001). Geometric mean (95% CI) percent error was 3.5% (2.3%, 5.2%) and CV was 2.1% (1.7%, 2.5%) overall. There were no significant differences in percent error or CV among instrument types ( p = 0.91, p = 0.15, respectively). Among sample matrices, serum and plasma zinc measures had the highest CV: 4.8% (3.0%, 7.7%) and 3.9% (2.9%, 5.4%), respectively ( p < 0.05). When using standardized materials and methods, similar zinc concentration values, accuracy, and precision were achieved using AAS, ICP-OES, or ICP-MS. However, method development is needed for improvement in serum and plasma zinc measurement precision. Differences in calibration among instruments demonstrate a need for harmonization among laboratories.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Conflicting interests and growing importance of non‐indigenous species in commercial and recreational fisheries of the Mediterranean Sea - Periklis Kleitou; Dimitrios K. Moutopoulos; Ioannis Giovos; Demetris Kletou; Ioannis Savva; Leda L. Cai; Jason M. Hall‐Spencer; Anastasia Charitou; Maria Elia; George Katselis; Siân Rees (Fisheries Management and Ecology, 2022)
Non‐indigenous species (NIS) are spreading and reshaping Mediterranean Sea biological communities and fishery resources. The present study used fisheries data and structured interviews to assess the impacts of NIS on recreational and commercial fishers in Cyprus. NIS that have been present in Cyprus for more than two decades were mostly perceived by local fishers as native, NIS with high market value were considered to be beneficial, and venomous or poisonous NIS were considered to be deleterious. Pufferfishes (Tetraodontidae) were identified by fishers as causing significant economic damage, which undermines the sustainability of the commercial fishing sector. The most popular and highly priced NIS were rabbitfishes ( Siganus spp.). In terms of commercial landings, six non‐indigenous taxa contributed over a quarter of the total landing value and more than half during the summer season. The results of the present study emphasised the multifaceted interactions of NIS with the fishing sector, and how policy objectives may not align with social and commercial fishery interests.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Correction to: Characterization of the Cerebrospinal Fluid Proteome in Patients with Fragile X-Associated Tremor/Ataxia Syndrome - Diana A. Abbasi; Thu T. A. Nguyen; Deborah A. Hall; Erin Robertson-Dick; Elizabeth Berry-Kravis; Stephanie M. Cologna (The Cerebellum, 2022)

Characterization of the Cerebrospinal Fluid Proteome in Patients with Fragile X-Associated Tremor/Ataxia Syndrome - Diana A. Abbasi; Thu T. A. Nguyen; Deborah A. Hall; Erin Robertson-Dick; Elizabeth Berry-Kravis; Stephanie M. Cologna (The Cerebellum, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Climate policy conflict in the U.S. states: a critical review and way forward - Joshua A. Basseches; Rebecca Bromley-Trujillo; Maxwell T. Boykoff; Trevor Culhane; Galen Hall; Noel Healy; David J. Hess; David Hsu; Rachel M. Krause; Harland Prechel; J. Timmons Roberts; Jennie C. Stephens (Climatic Change, 2022)
Many U.S. states have taken significant action on climate change in recent years, demonstrating their commitment despite federal policy gridlock and rollbacks. Yet, there is still much we do not know about the agents, discourses, and strategies of those seeking to delay or obstruct state-level climate action. We first ask, what are the obstacles to strong and effective climate policy within U.S. states? We review the political structures and interest groups that slow action, and we examine emerging tensions between climate justice and the technocratic and/or market-oriented approaches traditionally taken by many mainstream environmental groups. Second, what are potential solutions for overcoming these obstacles? We suggest strategies for overcoming opposition to climate action that may advance more effective and inclusive state policy, focusing on political strategies, media framing, collaboration, and leveraging the efforts of ambitious local governments.

Spatiotemporal Patterns in the Biomass of Drift Macroalgae in the Indian River Lagoon, Florida, United States - Lauren M. Hall; Lori J. Morris; Robert H. Chamberlain; M. Dennis Hanisak; Robert W. Virnstein; Richard Paperno; Bernhard Riegl; L. Rex Ellis; Ali Simpson; Charles A. Jacoby (Frontiers in Marine Science, 2022)
Drift macroalgae plays key roles in the ecology of many coastal systems, including the Indian River Lagoon. In the lagoon, changes in the biomass of drift macroalgae may have interacted with an unprecedented bloom of phytoplankton in 2011. Patterns in the biomass of drift macroalgae were identified using new and original analyses of data from several sampling programs collected between 1997 and 2019. All available data show a relatively low biomass of drift macroalgae in 2010–2012, and surveys of fixed transects and seining as part of a fisheries independent monitoring program also recorded low biomass in 2016. Low light availability and potentially stressful temperatures appeared to be the main influences as indicated by the results of incubations in tanks to determine environmental tolerances and data on ambient conditions. Decreased biomass of drift macroalgae had implications for cycling of nutrients because carbon, nitrogen, and phosphorus not stored in the tissues of drift macroalgae became available for uptake by other primary producers, including phytoplankton. The estimated 14–18% increases in concentrations of these elements in the IRL could have promoted longer and more intense phytoplankton blooms, which would have reduced light availability and increased stress on algae and seagrasses. An improved understanding of such feedback and the ecological roles played by drift macroalgae will support more effective management of nutrient loads and the system by accounting for cycling of nutrients among primary producers.

Light‐driven dynamics between calcification and production in functionally diverse coral reef calcifiers - Jennifer Mallon; Tyler Cyronak; Emily R. Hall; Anastazia T. Banaszak; Dan A. Exton; Adrian M. Bass (Limnology and Oceanography, 2022)
Coral reef metabolism underpins ecosystem function and is defined by the processes of photosynthesis, respiration, calcification, and calcium carbonate dissolution. However, the relationships between these physiological processes at the organismal level and their interactions with light remain unclear. We examined metabolic rates across a range of photosynthesising calcifiers in the Caribbean: the scleractinian corals Acropora cervicornis , Orbicella faveolata , Porites astreoides , and Siderastrea siderea , and crustose coralline algae (CCA) under varying natural light conditions. Net photosynthesis and calcification showed a parabolic response to light across all species, with differences among massive corals, branching corals, and CCA that reflect their relative functional roles on the reef. At night, all organisms were net respiring, and most were net calcifying, although some incubations demonstrated instances of net calcium carbonate (CaCO 3 ) dissolution. Peak metabolic rates at light‐saturation (maximum photosynthesis and calcification) and average dark rates (respiration and dark calcification) were positively correlated across species. Interspecies relationships among photosynthesis, respiration, and calcification indicate that calcification rates are linked to energy production at the organismal level in calcifying reef organisms. The species‐specific ratios of net calcification to photosynthesis varied with light over a diurnal cycle. The dynamic nature of calcification/photosynthesis ratios over a diurnal cycle questions the use of this metric as an indicator for reef function and health at the ecosystem scale unless temporal variability is accounted for, and a new metric is proposed. The complex light‐driven dynamics of metabolic processes in coral reef organisms indicate that a more comprehensive understanding of reef metabolism is needed for predicting the future impacts of global change.

Seagrass in a Changing Estuary, the Indian River Lagoon, Florida, United States - Lori J. Morris; Lauren M. Hall; Charles A. Jacoby; Robert H. Chamberlain; M. Dennis Hanisak; Janice D. Miller; Robert W. Virnstein (Frontiers in Marine Science, 2022)
Seagrass is a major structural habitat in the Indian River Lagoon. Maps documented locations and areal extents of beds periodically since the 1940s, and surveys of fixed transects yielded changes in percent cover and depths at the end of the canopy since 1994. Areal extent increased by ∼7,000 ha from 1994 to 2009, mean percent cover within beds decreased from ∼40 to 20%, and mean percent cover standardized to maximum transect length remained near 20%. Thus, conditions supported a consistent biomass because cover decreased as areal extent increased. Between 2011 and 2019, ∼19,000 ha or ∼58% of seagrasses were lost, with offshore ends of canopies moving shoreward and shallower, and standardized mean percent cover decreased to ∼4%. These changes coincided with blooms of phytoplankton, and ≤ 27% of incident subsurface irradiance at 0.9 m was stressful. Decreases in mean percent cover per month of stress became larger when initial mean cover per transect was < 20%, which suggested that the ratio of aboveground to belowground tissues in the expanded and sparser beds led to respiratory demand that was not met by photosynthesis. Despite intermittent improvements in light penetration, widespread recovery of seagrasses has not occurred potentially due to detrimental feedbacks. For example, loss of seagrass exposed sediments to waves, and the resulting disturbance may have hampered recruitment of new shoots. The same decreases also made 58–88% of the carbon, nitrogen, and phosphorus in seagrass tissue available to other primary producers. These nutrients did not enhance growth of epiphytes, whose biomass decreased by ∼42%, but they apparently fueled blooms of phytoplankton, with mean chlorophyll- a concentrations increasing by > 900%. Such intense blooms increased shading and loss of seagrasses. Fortunately, data showed that patches of seagrasses at depths of 0.5–0.9 m persisted for 22–24 years, which suggested that this depth zone could hold the key to recovery. Nevertheless, optimistic estimates predict recovery could take 12–17 years. Such a long-term, widespread loss of a key structural habitat may generate multiple adverse effects in the system, and mitigating such effects may entail planting seagrasses to accelerate recovery.

Protective role of lactic acid bacteria and yeasts as dietary carcinogen-binding agents – a review - P. F. Cuevas-González; A. F. González-Córdova; B. Vallejo-Cordoba; J. E. Aguilar-Toalá; F. G. Hall; U. C. Urbizo-Reyes; A. M. Liceaga; A. Hernandez-Mendoza; H. S. García (Critical Reviews in Food Science and Nutrition, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Presence of Denitrifiers In Bacterial Communities of Urban Stormwater Best Management Practices (BMPs) - Natalie C. Hall; Masoumeh Sikaroodi; Dianna Hogan; R. Christian Jones; Patrick M. Gillevet (Environmental Management, 2022)
Stormwater best management practices (BMPs) are engineered structures that attempt to mitigate the impacts of stormwater, which can include nitrogen inputs from the surrounding drainage area. The goal of this study was to assess bacterial community composition in different types of stormwater BMP soils to establish whether a particular BMP type harbors more denitrification potential. Soil sampling took place over the summer of 2015 following precipitation events. Soils were sampled from four bioretention facilities, four dry ponds, four surface sand filters, and one dry swale. 16S rRNA gene analysis of extracted DNA and RNA amplicons indicated high bacterial diversity in the soils of all BMP types sampled. An abundance of denitrifiers was also indicated in the extracted DNA using presence/absence of nirS, nirK , and nosZ denitrification genes. BMP soil bacterial communities were impacted by the surrounding soil physiochemistry. Based on the identification of a metabolically-active community of denitrifiers, this study has indicated that denitrification could potentially occur under appropriate conditions in all types of BMP sampled, including surface sand filters that are often viewed as providing low potential for denitrification. The carbon content of incoming stormwater could be providing bacterial communities with denitrification conditions. The findings of this study are especially relevant for land managers in watersheds with legacy nitrogen from former agricultural land use.

Warming increased bark beetle‐induced tree mortality by 30% during an extreme drought in California - Zachary J. Robbins; Chonggang Xu; Brian H. Aukema; Polly C. Buotte; Rutuja Chitra‐Tarak; Christopher J. Fettig; Michael L. Goulden; Devin W. Goodsman; Alexander D. Hall; Charles D. Koven; Lara M. Kueppers; Gavin D. Madakumbura; et al. (Global Change Biology, 2022)
Quantifying the responses of forest disturbances to climate warming is critical to our understanding of carbon cycles and energy balances of the Earth system. The impact of warming on bark beetle outbreaks is complex as multiple drivers of these events may respond differently to warming. Using a novel model of bark beetle biology and host tree interactions, we assessed how contemporary warming affected western pine beetle ( Dendroctonus brevicomis ) populations and mortality of its host, ponderosa pine ( Pinus ponderosa ), during an extreme drought in the Sierra Nevada, California, United States. When compared with the field data, our model captured the western pine beetle flight timing and rates of ponderosa pine mortality observed during the drought. In assessing the influence of temperature on western pine beetles, we found that contemporary warming increased the development rate of the western pine beetle and decreased the overwinter mortality rate of western pine beetle larvae leading to increased population growth during periods of lowered tree defense. We attribute a 29.9% (95% CI: 29.4%–30.2%) increase in ponderosa pine mortality during drought directly to increases in western pine beetle voltinism (i.e., associated with increased development rates of western pine beetle) and, to a much lesser extent, reductions in overwintering mortality. These findings, along with other studies, suggest each degree (°C) increase in temperature may have increased the number of ponderosa pine killed by upwards of 35%–40% °C −1 if the effects of compromised tree defenses (15%–20%) and increased western pine beetle populations (20%) are additive. Due to the warming ability to considerably increase mortality through the mechanism of bark beetle populations, models need to consider climate's influence on both host tree stress and the bark beetle population dynamics when determining future levels of tree mortality.

Understanding coralline algal responses to ocean acidification: Meta‐analysis and synthesis - Christopher E. Cornwall; Ben P. Harvey; Steeve Comeau; Daniel L. Cornwall; Jason M. Hall‐Spencer; Viviana Peña; Shigeki Wada; Lucia Porzio (Global Change Biology, 2022)
Ocean acidification (OA) is a major threat to the persistence of biogenic reefs throughout the world's ocean. Coralline algae are comprised of high magnesium calcite and have long been considered one of the most susceptible taxa to the negative impacts of OA. We summarize these impacts and explore the causes of variability in coralline algal responses using a review/qualitative assessment of all relevant literature, meta‐analysis, quantitative assessment of critical responses, and a discussion of physiological mechanisms and directions for future research. We find that most coralline algae experienced reduced abundance, calcification rates, recruitment rates, and declines in pH within the site of calcification in laboratory experiments simulating OA or at naturally elevated CO 2 sites. There were no other consistent physiological responses of coralline algae to simulated OA (e.g., photo‐physiology, mineralogy, and survival). Calcification/growth was the most frequently measured parameters in coralline algal OA research, and our meta‐analyses revealed greater declines in seawater pH were associated with significant decreases in calcification in adults and similar but nonsignificant trends for juveniles. Adults from the family Mesophyllumaceae also tended to be more robust to OA, though there was insufficient data to test similar trends for juveniles. OA was the dominant driver in the majority of laboratory experiments where other local or global drivers were assessed. The interaction between OA and any other single driver was often additive, though factors that changed pH at the surface of coralline algae (light, water motion, epiphytes) acted antagonistically or synergistically with OA more than any other drivers. With advances in experimental design and methodological techniques, we now understand that the physiology of coralline algal calcification largely dictates their responses to OA. However, significant challenges still remain, including improving the geographic and life‐history spread of research effort and a need for holistic assessments of physiology.

Environmental Drivers of Seagrass-Associated Nekton Abundance Across the Northern Gulf of Mexico - Benjamin A. Belgrad; Kelly M. Correia; Kelly M. Darnell; M. Zachary Darnell; Christian T. Hayes; Margaret O. Hall; Bradley T. Furman; Charles W. Martin; Delbert L. Smee (Estuaries and Coasts, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ethics and governance for internet‐based conservation science research - Ruth M. Thompson; Jordan Hall; Chris Morrison; Nicole R. Palmer; David L. Roberts (Conservation Biology, 2021)
Internet‐based research is increasingly important for conservation science and has wide‐ranging applications and contexts, including culturomics, illegal wildlife trade, and citizen science. However, online research methods pose a range of ethical and legal challenges. Online data may be protected by copyright, database rights, or contract law. Privacy rights may also restrict the use and access of data, as well as ethical requirements from institutions. Online data have real‐world meaning, and the ethical treatment of individuals and communities must not be marginalized when conducting internet‐based research. As ethics frameworks originally developed for biomedical applications are inadequate for these methods, we propose that research activities involving the analysis of preexisting online data be treated analogous to offline social science methods, in particular, nondeceptive covert observation. By treating internet users and their data with respect and due consideration, conservationists can uphold the public trust needed to effectively address real‐world issues.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Biogeochemical status of the Paleo-Pacific Ocean: clues from the early Cambrian of South Australia - P. A. Hall; D. M. McKirdy; G. P. Halverson; J. B. Jago; A. S. Collins (Australian Journal of Earth Sciences, 2021)

Field testing cellulose-water oxygen isotope relations in periphyton for paleohydrological reconstructions - Cory A. M. Savage; Casey R. Remmer; James V. Telford; Mitchell L. Kay; Eva Mehler; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

A remarkable legion of guests: Diversity and host specificity of army ant symbionts - Christoph von Beeren; Nico Blüthgen; Philipp O. Hoenle; Sebastian Pohl; Adrian Brückner; Alexey K. Tishechkin; Munetoshi Maruyama; Brian V. Brown; John M. Hash; W. E. Hall; Daniel J. C. Kronauer (Molecular Ecology, 2021)
Tropical rainforests are among the most diverse biomes on Earth. While species inventories are far from complete for any tropical rainforest, even less is known about the intricate species interactions that form the basis of these ecological communities. One fascinating but poorly studied example are the symbiotic associations between army ants and their rich assemblages of parasitic arthropod guests. Hundreds of these guests, or myrmecophiles, have been taxonomically described. However, because previous work has mainly been based on haphazard collections from disjunct populations, it remains challenging to define species boundaries. We therefore know little about the species richness, abundance and host specificity of most guests in any given population, which is crucial to understand co‐evolutionary and ecological dynamics. Here, we report a quantitative community survey of myrmecophiles parasitizing the six sympatric Eciton army ant species in a Costa Rican rainforest. Combining DNA barcoding with morphological identification of over 2,000 specimens, we discovered 62 species, including 49 beetles, 11 flies, one millipede and one silverfish. At least 14 of these species were new to science. Ecological network analysis revealed a clear signal of host partitioning, and each Eciton species was host to both specialists and generalists. These varying degrees in host specificities translated into a moderate level of network specificity, highlighting the system's level of biotic pluralism in terms of biodiversity and interaction diversity. By providing vouchered DNA barcodes for army ant guest species, this study provides a baseline for future work on co‐evolutionary and ecological dynamics in these species‐rich host–symbiont networks across the Neotropical realm.

Thermal limits in the face of infectious disease: How important are pathogens? - Tobias E. Hector; Carla M. Sgrò; Matthew D. Hall (Global Change Biology, 2021)
The frequency and severity of both extreme thermal events and disease outbreaks are predicted to continue to shift as a consequence of global change. As a result, species persistence will likely be increasingly dependent on the interaction between thermal stress and pathogen exposure. Missing from the intersection between studies of infectious disease and thermal ecology, however, is the capacity for pathogen exposure to directly disrupt a host's ability to cope with thermal stress. Common sources of variation in host thermal performance, which are likely to interact with infection, are also often unaccounted for when assessing either the vulnerability of species or the potential for disease spread during extreme thermal events. Here, we describe how infection can directly alter host thermal limits, to a degree that exceeds the level of variation commonly seen across species large geographic distributions and that equals the detrimental impact of other ecologically relevant stressors. We then discuss various sources of heterogeneity within and between populations that are likely to be important in mediating the impact that infection has on variation in host thermal limits. In doing so we highlight how infection is a widespread and important source of variation in host thermal performance, which will have implications for both the persistence and vulnerability of species and the dynamics and transmission of disease in a more thermally extreme world.

Major loss of coralline algal diversity in response to ocean acidification - Viviana Peña; Ben P. Harvey; Sylvain Agostini; Lucia Porzio; Marco Milazzo; Paulo Horta; Line Le Gall; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Calcified coralline algae are ecologically important in rocky habitats in the marine photic zone worldwide and there is growing concern that ocean acidification will severely impact them. Laboratory studies of these algae in simulated ocean acidification conditions have revealed wide variability in growth, photosynthesis and calcification responses, making it difficult to assess their future biodiversity, abundance and contribution to ecosystem function. Here, we apply molecular systematic tools to assess the impact of natural gradients in seawater carbonate chemistry on the biodiversity of coralline algae in the Mediterranean and the NW Pacific, link this to their evolutionary history and evaluate their potential future biodiversity and abundance. We found a decrease in the taxonomic diversity of coralline algae with increasing acidification with more than half of the species lost in high p CO 2 conditions. Sporolithales is the oldest order (Lower Cretaceous) and diversified when ocean chemistry favoured low Mg calcite deposition; it is less diverse today and was the most sensitive to ocean acidification. Corallinales were also reduced in cover and diversity but several species survived at high p CO 2 ; it is the most recent order of coralline algae and originated when ocean chemistry favoured aragonite and high Mg calcite deposition. The sharp decline in cover and thickness of coralline algal carbonate deposits at high p CO 2 highlighted their lower fitness in response to ocean acidification. Reductions in CO 2 emissions are needed to limit the risk of losing coralline algal diversity.

Simplification, not “tropicalization”, of temperate marine ecosystems under ocean warming and acidification - Sylvain Agostini; Ben P. Harvey; Marco Milazzo; Shigeki Wada; Koetsu Kon; Nicolas Floc’h; Kosei Komatsu; Mayumi Kuroyama; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Ocean warming is altering the biogeographical distribution of marine organisms. In the tropics, rising sea surface temperatures are restructuring coral reef communities with sensitive species being lost. At the biogeographical divide between temperate and tropical communities, warming is causing macroalgal forest loss and the spread of tropical corals, fishes and other species, termed “tropicalization”. A lack of field research into the combined effects of warming and ocean acidification means there is a gap in our ability to understand and plan for changes in coastal ecosystems. Here, we focus on the tropicalization trajectory of temperate marine ecosystems becoming coral‐dominated systems. We conducted field surveys and in situ transplants at natural analogues for present and future conditions under (i) ocean warming and (ii) both ocean warming and acidification at a transition zone between kelp and coral‐dominated ecosystems. We show that increased herbivory by warm‐water fishes exacerbates kelp forest loss and that ocean acidification negates any benefits of warming for range extending tropical corals growth and physiology at temperate latitudes. Our data show that, as the combined effects of ocean acidification and warming ratchet up, marine coastal ecosystems lose kelp forests but do not gain scleractinian corals. Ocean acidification plus warming leads to overall habitat loss and a shift to simple turf‐dominated ecosystems, rather than the complex coral‐dominated tropicalized systems often seen with warming alone. Simplification of marine habitats by increased CO 2 levels cascades through the ecosystem and could have severe consequences for the provision of goods and services.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Cyclical Patterns and a Regime Shift in the Character of Phytoplankton Blooms in a Restricted Sub-Tropical Lagoon, Indian River Lagoon, Florida, United States - Edward J. Phlips; Susan Badylak; Natalie G. Nelson; Lauren M. Hall; Charles A. Jacoby; Margaret A. Lasi; Jean C. Lockwood; Janice D. Miller (Frontiers in Marine Science, 2021)
This paper examines the character of phytoplankton blooms in a restricted sub-tropical lagoon along the Atlantic coast of central Florida. The results of the 23-year study (1997–2020) provide evidence for multiple types of variability in bloom activity, including cyclical patterns, stochastic events, and most prominently a regime shift in composition and intensity. Cyclical patterns (e.g., El Niño/La Niña periods) and stochastic events (e.g., tropical storms) influenced rainfall levels, which in turn impacted nutrient concentrations in the water column and the timing and intensity of blooms. In 2011, a major change occurred in the character of blooms, with a dramatic increase in peak biomass levels of blooms and the appearance of new dominant taxa, including the brown tide species Aureoumbra lagunensis and other nanoplanktonic species. Results of quantitative analyses reveal system behavior indicative of a regime shift. The shift coincided with widespread losses of seagrass community and reduced drift algae biomass. A combination of exceptionally low water temperatures in the winters of 2009/2010 and 2010/2011, hypersaline conditions associated with drought conditions, and high light attenuation caused by blooms appear to have contributed to the widespread and protracted decline in seagrass and drift macroalgal communities in the lagoon, leading to shifts in distribution of internal and external nutrient sources toward phytoplankton.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Dumpsters and other anthropogenic structures as habitat for invasive African rock agama lizards in Florida - Timothy S. Mitchell; Brian Folt; Joshua M. Hall (Biological Invasions, 2021)

Production and diversity of microorganisms associated with sinking particles in the subtropical North Pacific Ocean - Matthew J. Church; Eint Kyi; Robert O. Hall; David M. Karl; Markus Lindh; Alexa Nelson; Emma K. Wear (Limnology and Oceanography, 2021)
Sinking particulate organic matter controls the flux of carbon (C) from the surface ocean to the deep sea. Microorganisms actively colonize particles, but the extent to which microbial metabolism influences particle export remains uncertain. We conducted experiments to quantify rates of bacterial production (derived based on 3 H‐leucine incorporation) and dark C‐fixation (based on 14 C‐bicarbonate assimilation) associated with sinking particles collected from the base of the euphotic zone (175 m) in the subtropical North Pacific Ocean. Seawater was amended with sinking particles and rates of filter size‐fractionated (0.2, 2, and 20 μ m) bacterial production and dark C‐fixation were measured. Sequencing of 16S ribosomal RNA (rRNA) gene amplicons revealed that microorganisms in the particle‐amended treatments differed from those in the unamended seawater controls, with the particle treatments enriched in putative copiotrophic bacteria. The addition of sinking particles increased rates of bacterial production (by 6‐ to 9‐fold), and to a lesser extent dark C‐fixation (by 1.7‐ to 4.6‐fold), relative to unamended controls, with most of the production associated with filter pore sizes μ m. Normalizing production to concentrations of particulate C yielded rates that were statistically indistinguishable between particle‐amended treatments and unamended controls. We then examined possible relationships between sinking particulate C flux attenuation and its supply to the mesopelagic waters, revealing that flux attenuation was positively related to increases in particulate C supply. Together with results from our experiments, we suggest processes that contribute to sinking particle disaggregation both increase flux attenuation and favor microbial mineralization of particle‐derived organic matter.

Efficacy of Targeted ECO/miR-200c Nanoparticles for Modulating Tumor Microenvironment and Treating Triple Negative Breast Cancer as Non-invasively Monitored by MR Molecular Imaging - Andrew L. Schilb; Nadia R. Ayat; Amita M. Vaidya; Laura M. Hertz; Ryan C. Hall; Josef H. Scheidt; Da Sun; Zhanhu Sun; Ramamurthy Gopalakrishnan; Zheng-Rong Lu (Pharmaceutical Research, 2021)

Integrating Literature, Biodiversity Databases, and Citizen-Science to Reconstruct the Checklist of Chondrichthyans in Cyprus (Eastern Mediterranean Sea) - Ioannis Giovos; Fabrizio Serena; Dimitra Katsada; Athanasios Anastasiadis; Adi Barash; Charis Charilaou; Jason M. Hall-Spencer; Fabio Crocetta; Alexander Kaminas; Demetris Kletou; Mary Maximiadi; Vasileios Minasidis; et al. (Fishes, 2021)
Chondrichthyans are apex predators influencing the trophic web through a top-down process thus their depletion will affect the remaining biota. Notwithstanding that, research on chondrichthyans is sparse or data-limited in several biogeographic areas worldwide, including the Levantine Sea. We revise and update the knowledge of chondrichthyans in Cyprus based on a bibliographic review that gains information retrieved from peer-reviewed and grey literature, Global Biodiversity Information Facility (135 records of at least 18 species) and the Ocean Biodiversity Information System (65 records of at least14 species), and the citizen science project Mediterranean Elasmobranchs Citizen Observations (117 records per 23 species). Our updated checklist reports 60 species that account for about 70% of the Mediterranean chondrichthyan biota. The list includes 15 more species than the previous checklist and our study reports three new species for Cyprus waters, namely the blackmouth catshark Dalatias licha, the round fantail stingray Taeniurops grabatus, and the sawback angelshark Squatina aculeata. Our research highlights the need for conservation measures and more studies regarding the highly threatened blackchin guitarfish Glaucostegus cemiculus and the devil ray Mobula mobular, and stresses the importance for training a new generation of observers to strengthen the knowledge and conservation of elasmobranchs in the region.

Impact of Extreme Disturbances on Suspended Sediment in Western Florida Bay: Implications for Seagrass Resilience - Jonathan R. Rodemann; W. Ryan James; Rolando O. Santos; Bradley T. Furman; Zachary W. Fratto; Valentina Bautista; Jan Lara Hernandez; Natasha M. Viadero; Joshua O. Linenfelser; Lulu A. Lacy; Margaret O. Hall; Christopher R. Kelble; et al. (Frontiers in Marine Science, 2021)
Seagrasses are threatened worldwide due to anthropogenic and natural disturbances disrupting the multiple feedbacks needed to maintain these ecosystems. If the disturbance is severe enough, seagrass systems may undergo a regime shift to a degraded system state that is resistant to recovery. In Florida Bay, Florida, United States, two recent, large-scale disturbances (a drought-induced seagrass die-off in 2015 and Hurricane Irma in 2017) have caused 8,777 ha of seagrass beds to degrade into a turbid, unvegetated state, causing a large sediment plume. Using satellite imagery digitization and long-term seagrass cover data, we investigate the expansion of this sediment plume between 2008 and 2020 and the potential interaction of this sediment plume with seagrass recovery in two focal basins in Florida Bay affected by the die-off, Johnson and Rankin. The average size of the sediment plume increased by 37% due to the die-off and Hurricane Irma, increasing from an average of 163.5 km 2 before the disturbances to an average of 223.5 km 2 . The expansion of the plume was basin-specific, expanding into Johnson after the 2015 seagrass die-off with expansive and long-lasting effects, but only expanding into Rankin after Hurricane Irma with less severe and short-term effects. Furthermore, the sediment plume was negatively correlated with seagrass cover in Johnson, but held no relationship with seagrass cover in Rankin. Thus, different disturbances can act upon seagrass ecosystems at varying scales with varying consequences. This study illustrates the advantage of combining satellite imagery with field data to monitor disturbances as well as highlights the importance of investigating disturbances of seagrass ecosystems at various scales to comprehend seagrass resilience in the context of future extreme events.

Low Pufferfish and Lionfish Predation in Their Native and Invaded Ranges Suggests Human Control Mechanisms May Be Necessary to Control Their Mediterranean Abundances - Aylin Ulman; Holden E. Harris; Nikos Doumpas; Hasan Deniz Akbora; Sara A. A Al Mabruk; Ernesto Azzurro; Michel Bariche; Burak Ali Çiçek; Alan Deidun; Nazli Demirel; Alexander Q. Fogg; Stelios Katsavenakis; et al. (Frontiers in Marine Science, 2021)
The silver-cheeked toadfish ( Lagocephalus sceleratus , from the pufferfish family Tetraodontidae) and the Pacific red lionfish ( Pterois miles , family Scorpaenidae) have recently invaded the Mediterranean Sea. Lagocephalus sceleratus has spread throughout this entire sea with the highest concentrations in the eastern basin, while more recently, Pterois miles has spread from the Eastern to the Central Mediterranean Sea. Their effects on local biodiversity and fisheries are cause for management concern. Here, a comprehensive review of predators of these two species from their native Indo-Pacific and invaded Mediterranean and Western Atlantic ranges is presented. Predators of Tetraodontidae in general were reviewed for their native Indo-Pacific and Western Atlantic ranges, as no records were found specifically for L. sceleratus in its native range. Tetraodontidae predators in their native ranges included mantis shrimp (Stomatopoda), lizardfish ( Synodus spp.), tiger shark ( Galeocerdo cuvier ), lemon shark ( Negaprion brevirostris ), sea snakes ( Enhydrina spp.), catfish ( Arius spp.), cobia ( Rachycentron canadum ), skipjack tuna ( Katsuwonus pelamis ), and common octopus ( Octopus vulgaris ). The only reported predator of adult L. sceleratus in the Mediterranean was loggerhead turtle ( Caretta caretta ), whereas juvenile L. sceleratus were preyed by common dolphinfish ( Coryphaena hippurus ) and garfish ( Belone belone ). Conspecific cannibalism of L. sceleratus juveniles was also confirmed in the Mediterranean. Pufferfish predators in the Western Atlantic included common octopus, frogfish (Antennaridae), and several marine birds. Predators of all lionfish species in their native Indo-Pacific range included humpback scorpionfish ( Scorpaenopsis spp.), bobbit worms ( Eunice aphroditois ), moray eels (Muraenidae), and bluespotted cornetfish ( Fistularia commersonii ). Lionfish predators in the Mediterranean included dusky grouper ( Epinephelus marginatus ), white grouper ( Epinephelus aeneus ), common octopus, and L. sceleratus , whereas in the Western Atlantic included the spotted moray ( Gymnothorax moringa ), multiple grouper species (tiger Mycteroperca tigris , Nassau Epinephelus striatus , black Mycteroperca bonaci , red Epinephelus morio , and gag Mycteroperca microleps ; Epinephelidae), northern red snapper ( Lutjanus campechanus ), greater amberjack ( Seriola dumerilli ), and nurse shark ( Ginglymostoma cirratum ). The sparse data found on natural predation for these species suggest that population control via predation may be limited. Their population control may require proactive, targeted human removals, as is currently practiced with lionfish in the Western Atlantic.

Freshwater, Landlocked Grand Lake Strain of Atlantic Salmon (Salmo salar L.) as a Potential Genetic Source of Long Chain Polyunsaturated Fatty Acids Synthesis - Stefanie M. Colombo; Mohamed Emam; Brian C. Peterson; Jennifer R. Hall; Gary Burr; Zeyu Zhang; Matthew L. Rise (Frontiers in Marine Science, 2021)
Selection efforts focused on adaptation to plant-based diets, particularly the ability to synthesize polyunsaturated fatty acids (PUFA), are now emerging in aquaculture. Landlocked salmon (Grand Lake population; GL) may differ from the commercial Saint John River (SJR) strain in terms of PUFA metabolism. The objective of this study was to determine if GL salmon can contribute toward broodstock selection for enhanced PUFA synthesis. Two diets containing either fish oil (FO) or plant-based oil (FO-free) were fed to the SJR and GL strains (∼58 g/fish) for 16 weeks. Growth, liver, and muscle fatty acid (FA) content, and transcript expression of lipid metabolism and inflammation-related genes were evaluated. GL salmon fed the FO diet showed reduced growth compared to SJR salmon (fed either diet); however, GL salmon fed the FO-free diet, growth was not significantly different compared to any group. In liver, SJR salmon fed the FO-free diet had higher levels of n-6 PUFAs (21.9%) compared to GL fed the same diet (15.9%); while GL salmon fed the FO-free diet had higher levels of monounsaturated FAs (48.9%) compared with SJR salmon fed the same diet (35.7%). 20:5n-3 and 22:6n-3 were the same in GL and SJR salmon liver and muscle, respectively, fed the FO-free diet. In liver, GL salmon fed the FO-free diet had higher acac and acly compared to all treatments and had higher fasb compared to both strains fed the FO-diet. GL salmon fed the FO-free diet had higher cd36c and fabp3b in liver compared to GL salmon fed the FO diet and SJR salmon fed either diet. GL salmon fed the FO-free diet had higher lect2a and pgds in liver compared to SJR salmon fed the FO-free diet. In muscle, GL salmon fed the FO-free diet had higher fadsd5 and fadsd6b compared with both strains fed the FO diet. These results suggest there is a genetic basis behind the potential for GL salmon to utilize FO-free diets more efficiently than SJR salmon, with regards to FA metabolism.

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Plasma gamma-aminobutyric acid (GABA) levels and posttraumatic stress disorder symptoms in trauma-exposed women: a preliminary report - Kimberly A. Arditte Hall; Sumaiya E. DeLane; George M. Anderson; Tiffany R. Lago; Rachel Shor; Weiwei Wang; Ann M. Rasmusson; Suzanne L. Pineles (Psychopharmacology, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Hypoactivation in the precuneus and posterior cingulate cortex during ambiguous decision making in individuals with HIV - Shana A. Hall; Sheri L. Towe; M. Tauseef Nadeem; Andrea L. Hobkirk; Bennett W. Hartley; Rosa Li; Scott A. Huettel; Christina S. Meade (Journal of NeuroVirology, 2021)

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

In vivo Validation of Bimolecular Fluorescence Complementation (BiFC) to Investigate Aggregate Formation in Amyotrophic Lateral Sclerosis (ALS) - Emily K. Don; Alina Maschirow; Rowan A. W. Radford; Natalie M. Scherer; Andrés Vidal-Itriago; Alison Hogan; Cindy Maurel; Isabel Formella; Jack J. Stoddart; Thomas E. Hall; Albert Lee; Bingyang Shi; et al. (Molecular Neurobiology, 2021)
Amyotrophic lateral sclerosis (ALS) is a form of motor neuron disease (MND) that is characterized by the progressive loss of motor neurons within the spinal cord, brainstem, and motor cortex. Although ALS clinically manifests as a heterogeneous disease, with varying disease onset and survival, a unifying feature is the presence of ubiquitinated cytoplasmic protein inclusion aggregates containing TDP-43. However, the precise mechanisms linking protein inclusions and aggregation to neuronal loss are currently poorly understood. Bimolecular fluorescence complementation (BiFC) takes advantage of the association of fluorophore fragments (non-fluorescent on their own) that are attached to an aggregation-prone protein of interest. Interaction of the proteins of interest allows for the fluorescent reporter protein to fold into its native state and emit a fluorescent signal. Here, we combined the power of BiFC with the advantages of the zebrafish system to validate, optimize, and visualize the formation of ALS-linked aggregates in real time in a vertebrate model. We further provide in vivo validation of the selectivity of this technique and demonstrate reduced spontaneous self-assembly of the non-fluorescent fragments in vivo by introducing a fluorophore mutation. Additionally, we report preliminary findings on the dynamic aggregation of the ALS-linked hallmark proteins Fus and TDP-43 in their corresponding nuclear and cytoplasmic compartments using BiFC. Overall, our data demonstrates the suitability of this BiFC approach to study and characterize ALS-linked aggregate formation in vivo. Importantly, the same principle can be applied in the context of other neurodegenerative diseases and has therefore critical implications to advance our understanding of pathologies that underlie aberrant protein aggregation.

Ocean acidification locks algal communities in a species‐poor early successional stage - Ben P. Harvey; Koetsu Kon; Sylvain Agostini; Shigeki Wada; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Long‐term exposure to CO 2 ‐enriched waters can considerably alter marine biological community development, often resulting in simplified systems dominated by turf algae that possess reduced biodiversity and low ecological complexity. Current understanding of the underlying processes by which ocean acidification alters biological community development and stability remains limited, making the management of such shifts problematic. Here, we deployed recruitment tiles in reference (pH T 8.137 ± 0.056 SD) and CO 2 ‐enriched conditions (pH T 7.788 ± 0.105 SD) at a volcanic CO 2 seep in Japan to assess the underlying processes and patterns of algal community development. We assessed (i) algal community succession in two different seasons (Cooler months: January–July, and warmer months: July–January), (ii) the effects of initial community composition on subsequent community succession (by reciprocally transplanting preestablished communities for a further 6 months), and (iii) the community production of resulting communities, to assess how their functioning was altered (following 12 months recruitment). Settlement tiles became dominated by turf algae under CO 2 ‐enrichment and had lower biomass, diversity and complexity, a pattern consistent across seasons. This locked the community in a species‐poor early successional stage. In terms of community functioning, the elevated p CO 2 community had greater net community production, but this did not result in increased algal community cover, biomass, biodiversity or structural complexity. Taken together, this shows that both new and established communities become simplified by rising CO 2 levels. Our transplant of preestablished communities from enriched CO 2 to reference conditions demonstrated their high resilience, since they became indistinguishable from communities maintained entirely in reference conditions. This shows that meaningful reductions in p CO 2 can enable the recovery of algal communities. By understanding the ecological processes responsible for driving shifts in community composition, we can better assess how communities are likely to be altered by ocean acidification.

Musclesense: a Trained, Artificial Neural Network for the Anatomical Segmentation of Lower Limb Magnetic Resonance Images in Neuromuscular Diseases - Baris Kanber; Jasper M Morrow; Uros Klickovic; Stephen Wastling; Sachit Shah; Pietro Fratta; Amy R McDowell; Matt G Hall; Chris A Clark; Francesco Muntoni; Mary M Reilly; Michael G Hanna; et al. (Neuroinformatics, 2021)

Foliar and Tuber Symptoms of U.S. Potato Varieties to Multiple Strains and Isolates of Potato virus Y - Jonathan L. Whitworth; Stewart M. Gray; Jason T. Ingram; Darren G. Hall (American Journal of Potato Research, 2021)

The Case of Lionfish (Pterois miles) in the Mediterranean Sea Demonstrates Limitations in EU Legislation to Address Marine Biological Invasions - Periklis Kleitou; Jason M. Hall-Spencer; Ioannis Savva; Demetris Kletou; Margarita Hadjistylli; Ernesto Azzurro; Stelios Katsanevakis; Charalampos Antoniou; Louis Hadjioannou; Niki Chartosia; Maria Christou; Yiannis Christodoulides; et al. (Journal of Marine Science and Engineering, 2021)
The European Regulation (EU) 1143/2014 on Invasive Alien Species entered into force in 2015, with the aim to fulfill regional and international biodiversity goals in a concerted manner. To date, the Regulation listed 66 Invasive Alien Species (IAS) that are subject to legal controls. Only one of these is marine. A recent lionfish (Pterois miles) invasion has been closely monitored in the Mediterranean and a detailed risk assessment was made about the profound impacts that this invasive fish is likely to have on the fisheries and biodiversity of the region. In 2016–21, lionfish rapidly became dominant predators along Eastern Mediterranean coasts, yet the process for their inclusion on the EU IAS list has been lengthy and is ongoing. There is an urgent need to learn from this experience. Here, we recommend improvements to the Regulation 1143/2014 and the risk assessment process to protect marine ecosystems and secure the jobs of people that rely on coastal resources.

Dependence on a human structure influences the extinction of a non-native lizard population after a major environmental change - Daniel A. Warner; Joshua M. Hall; Amélie Fargevieille; Austin C. Hulbert; Sarin Tiatragul; Jenna E. Pruett; Timothy S. Mitchell (Biological Invasions, 2021)

Fully Implanted Prostheses for Musculoskeletal Limb Reconstruction After Amputation: An In Vivo Feasibility Study - Patrick T. Hall; Samantha Z. Bratcher; Caleb Stubbs; Rebecca E. Rifkin; Remi M. Grzeskowiak; Bryce J. Burton; Cheryl B. Greenacre; Stacy M. Stephenson; David E. Anderson; Dustin L. Crouch (Annals of Biomedical Engineering, 2021)

Who is abuzz about bees? Explaining residents’ attitudes in Phoenix, Arizona - Kelli L. Larson; Melissa Fleeger; Susannah B. Lerman; Megan M. Wheeler; Riley Andrade; Jeffrey A. Brown; Sharon J. Hall; Desiree L. Narango (Urban Ecosystems, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

Persistent Contaminants and Herpesvirus OtHV1 Are Positively Associated With Cancer in Wild California Sea Lions (Zalophus californianus) - Frances M. D. Gulland; Ailsa J. Hall; Gina M. Ylitalo; Kathleen M. Colegrove; Tenaya Norris; Pádraig J. Duignan; Barbie Halaska; Karina Acevedo Whitehouse; Linda J. Lowenstine; Alissa C. Deming; Teresa K. Rowles (Frontiers in Marine Science, 2020)
The prevalence of cancer in wild California sea lions ( Zalophus californianus ) is one of the highest amongst mammals, with 18–23% of adult animals examined post-mortem over the past 40 years having urogenital carcinoma. To date, organochlorines, genotype and infection with Otarine herpesvirus-1 (OtHV-1) have been identified in separate studies using distinct animals as associated with this carcinoma. Multi-year studies using large sample sizes to investigate the relative importance of multiple factors on marine mammal health are rare due to logistical and ethical challenges. The objective of this study was to use a case control approach with samples from 394 animals collected over 20 years in a multifactorial analysis to explore the relative importance of distinct factors identified to date as associated with sea lion cancer in the likelihood of sea lion carcinoma. Stepwise regression indicated that the best model to explain carcinoma occurrence included herpesvirus status, contaminant exposure, and blubber depth, but not genotype at a single microsatellite locus, PV11. The odds of carcinoma was 43.57 times higher in sea lions infected with OtHV-1 (95% CI 14.61, 129.96, p < 0.001), and 1.48 times higher for every unit increase in the log e [contaminant concentrations], ng g –1 (an approximate tripling of concentration), in their blubber (95% CI 1.11, 1.97, p < 0.007), after controlling for the effect of blubber depth. These findings demonstrate the importance of contaminant exposure combined with OtHV1 infection, in the potential for cancer occurrence in wild sea lions.

Responses of Intertidal Bacterial Biofilm Communities to Increasing pCO2 - Dorsaf Kerfahi; Ben P. Harvey; Sylvain Agostini; Koetsu Kon; Ruiping Huang; Jonathan M. Adams; Jason M. Hall-Spencer (Marine Biotechnology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

Seagrass of Vasiliko Bay, Eastern Mediterranean: Lost Cause or Priority Conservation Habitat? - Demetris Kletou; Periklis Kleitou; Ioannis Savva; Martin J. Attrill; Stephanos Charalambous; Alexis Loucaides; Jason M. Hall-Spencer (Journal of Marine Science and Engineering, 2020)
Mediterranean coasts are affected by multiple mounting pressures. In Cyprus, marine fish farming has grown rapidly in the past decade and is concentrated in the west side of Vasiliko Bay. The east coast of this bay has ports, a power station, a desalination unit, a cement factory, a major new oil terminal, and gas storage facilities. The bay is earmarked to create the largest hydrocarbon processing, storing, and transport facility in the region. Here, we assess the status of Posidonia oceanica habitat in an understudied region at the upper thermal, and eastern limit, of this Mediterranean endemic seagrass. An extensive ancient seagrass meadow was revealed, covering about 200 ha across 10 km of coastline, over soft substrata at ca 10–30 m depth, and over hard substrata at ca 0–6 m depth. Seagrass shoot density and leaf surface area decreased, both with increasing depth and with proximity to industrial developments; part of the meadow had been destroyed by dredging to build a jetty. Close to fish farms the seagrass had higher epiphytic biomass as well as lower leaf number, mass, and surface area, all of which indicate adverse effects of eutrophication and increased turbidity. Despite these multiple stressors, most of the meadow was in good ecological status, with some of the highest shoot densities ever reported. Furthermore, iconic species like sea turtles, monk seals, and dolphins were seen during sampling. Posidonia oceanica meadows off Cyprus are among the most valuable in the Mediterranean due to their tolerance of high seawater temperatures. Managers of future coastal developments in the region will need to adhere to European legislation and international conventions designed to secure the socioeconomic benefits of seagrass beds.

The effect of variation in moonlight on nocturnal song of a diurnal bird species - Ashton L. Dickerson; Michelle L. Hall; Therésa M. Jones (Behavioral Ecology and Sociobiology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

The short-lived but successful tri-radial body plan: a view from the Ediacaran of Australia - C. M. S. Hall; M. L. Droser; E. C. Clites; J. G. Gehling (Australian Journal of Earth Sciences, 2020)

Flight initiation distance changes across landscapes and habitats in a successful urban coloniser - Matthew J. Hall; Alicia L. Burns; John M. Martin; Dieter F. Hochuli (Urban Ecosystems, 2020)

The extratropical response to a developing MJO: forecast and climate simulations with the DREAM model - Nicholas M. J. Hall; Hong Hanh Le; Stephanie Leroux (Climate Dynamics, 2020)

Acidification in the U.S. Southeast: Causes, Potential Consequences and the Role of the Southeast Ocean and Coastal Acidification Network - Emily R. Hall; Leslie Wickes; Louis E. Burnett; Geoffrey I. Scott; Debra Hernandez; Kimberly K. Yates; Leticia Barbero; Janet J. Reimer; Mohammed Baalousha; Jennifer Mintz; Wei-Jun Cai; J. Kevin Craig; et al. (Frontiers in Marine Science, 2020)

How thermal maturity analysis supports stratigraphic restoration in heavily faulted fluvial outcrops: a case study on Strzelecki Group outcrops, West Gippsland, Victoria, Australia - H. Aghaei; M. Hall; B. Wagstaff (Australian Journal of Earth Sciences, 2020)

Revealing hydrogen peroxide as an external stressor in macrophyte-dominated coastal ecosystems - Isla M. Twigg; Federico Baltar; Jack R. Hall; Christopher D. Hepburn (Oecologia, 2020)

They are here to stay: the biology and ecology of lionfish ( Pterois miles ) in the Mediterranean Sea - Ioannis Savva; Niki Chartosia; Charalampos Antoniou; Periklis Kleitou; Andreas Georgiou; Nir Stern; Louis Hadjioannou; Carlos Jimenez; Vasilis Andreou; Jason M. Hall‐Spencer; Demetris Kletou (Journal of Fish Biology, 2020)
The lionfish, Pterois miles , is one of the most recent Lessepsian immigrants into the Mediterranean Sea, and it poses a serious threat to marine ecosystems in the region. This study assesses the basic biology and ecology of lionfish in the Mediterranean, examining morphometrics, reproduction and diet as well as population structure and distribution. The population density of lionfish has increased dramatically in Cyprus since the first sighting in late 2012; by 2018 aggregations of up to 70 lionfish were found on rocky grounds with complex reefs and artificial reefs in depths of 0–50 m. Lionfish in Cyprus become mature within a year, and adults are capable of spawning year‐round, with peak spawning in summer when the sea‐surface temperature reaches 28.4°C. The Cypriot lionfish grow faster and bigger than in their native range, and females are more common than males. Lionfish are generalist predators in these waters, as also found in their native range, consuming a range of teleost and crustacean prey, some of which are of high economic value ( e.g. , Spicara smaris and Sparisoma cretense ) or have an important role in local trophic webs ( e.g. , Chromis chromis ). Overall, the reproductive patterns, the presence of juveniles and adults throughout the year, the rapid growth rates and the generalist diet indicate that lionfish are thriving and are now already well established in the region and could potentially become the serious nuisance that they are in their temperate and tropical western Atlantic–invasive range.

Associations between sensitivity to antibiotics, disinfectants and heavy metals in natural, clinical and laboratory isolates of Escherichia coli - Anna M. Bischofberger; Michael Baumgartner; Katia R. Pfrunder‐Cardozo; Richard C. Allen; Alex R. Hall (Environmental Microbiology, 2020)
Summary Bacteria in nature often encounter non‐antibiotic antibacterials (NAAs), such as disinfectants and heavy metals, and they can evolve resistance via mechanisms that are also involved in antibiotic resistance. Understanding whether susceptibility to different types of antibacterials is non‐randomly associated across natural and clinical bacteria is therefore important for predicting the spread of resistance, yet there is no consensus about the extent of such associations or underlying mechanisms. We tested for associations between susceptibility phenotypes of 93 natural and clinical Escherichia coli isolates to various NAAs and antibiotics. Across all compound combinations, we detected a small number of non‐random associations, including a trio of positive associations among chloramphenicol, triclosan and benzalkonium chloride. We investigated genetic mechanisms that can explain such associations using genomic information, genetic knockouts and experimental evolution. This revealed some mutations that are selected for by experimental exposure to one compound and confer cross‐resistance to other compounds. Surprisingly, these interactions were asymmetric: selection for chloramphenicol resistance conferred cross‐resistance to triclosan and benzalkonium chloride, but selection for triclosan resistance did not confer cross‐resistance to other compounds. These results identify genetic changes involved in variable cross‐resistance across antibiotics and NAAs, potentially contributing to associations in natural and clinical bacteria.

In Silico Prediction and In Vitro Assessment of Multifunctional Properties of Postbiotics Obtained From Two Probiotic Bacteria - J. E. Aguilar-Toalá; F. G. Hall; U. C. Urbizo-Reyes; H. S. Garcia; B. Vallejo-Cordoba; A. F. González-Córdova; A. Hernández-Mendoza; A. M. Liceaga (Probiotics and Antimicrobial Proteins, 2020)

Flood hazard assessment from storm tides, rain and sea level rise for a tidal river estuary - P. M. Orton; F. R. Conticello; F. Cioffi; T. M. Hall; N. Georgas; U. Lall; A. F. Blumberg; K. MacManus (Natural Hazards, 2020)

Use of human-made structures facilitates persistence of a non-native ectotherm - Austin C. Hulbert; Joshua M. Hall; Timothy S. Mitchell; Daniel A. Warner (Biological Invasions, 2020)

Correction to: Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2020)
Due to an error during the editorial phase, a correction regarding Fig. 2 is added to the original article: “Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis”. Please see below correct Fig. 2.

A precipitous decline in an invasive snail population cannot be explained by a native predator - Daniel J. Greenwood; Robert O. Hall; Teresa M. Tibbets; Amy C. Krist (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Effect of Promiscuous Aggregation on in Vitro Drug Metabolism Assays - Francesco Tres; Maria M. Posada; Stephen D. Hall; Michael A. Mohutsky; Lynne S. Taylor (Pharmaceutical Research, 2019)

Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij-van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2019)
Cognition in absence epilepsy (AE) is generally considered undisturbed. However, reports on cognitive deficits in AE in recent years have suggested otherwise. This review systematically assesses current literature on cognitive performance in children with AE. A systematic literature search was performed in Pubmed, Embase, Cochrane and Web of Science. All studies reporting on cognitive performance in children with AE were considered. In total 33 studies were eligible for inclusion. Neuropsychological tests were classified into the following domains: intelligence; executive function; attention; language; motor & sensory-perceptual examinations; visuoperceptual/visuospatial/visuoconstructional function; memory and learning; achievement. Random-effect meta-analyses were conducted by estimating the pooled mean and/or pooling the mean difference in case-control studies. Full-scale IQ in children with AE was estimated at 96.78 (95%CI:94.46–99.10) across all available studies and in case-control studies IQ was on average 8.03 (95%CI:-10.45- -5.61) lower. Verbal IQ was estimated at 97.98 (95%CI:95.80–100.16) for all studies and 9.01 (95%CI:12.11- -5.90) points lower in case-control studies. Performance IQ was estimated at 97.23 (93.24–101.22) for all available studies and 5.32 (95%CI:-8.27–2.36) points lower in case-control studies. Lower performance was most often reported in executive function (cognitive flexibility, planning, and verbal fluency) and attention (sustained, selective and divided attention). Reports on school difficulties, neurodevelopmental problems, and attentional problems were high. In conclusion, in contrast to common beliefs, lower than average neurocognitive performance was noted in multiple cognitive domains, which may influence academic and psychosocial development.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Internal tide energy flux over a ridge measured by a co-located ocean glider and moored acoustic Doppler current profiler - Rob A. Hall; Barbara Berx; Gillian M. Damerell (Ocean Science, 2019)
Internal tide energy flux is an important diagnostic for the study of energy pathways in the ocean, from large-scale input by the surface tide to small-scale dissipation by turbulent mixing. Accurate calculation of energy flux requires repeated full-depth measurements of both potential density (ρ) and horizontal current velocity (u) over at least a tidal cycle and over several weeks to resolve the internal spring–neap cycle. Typically, these observations are made using full-depth oceanographic moorings that are vulnerable to being “fished out” by commercial trawlers when deployed on continental shelves and slopes. Here we test an alternative approach to minimize these risks, with u measured by a low-frequency acoustic Doppler current profiler (ADCP) moored near the seabed and ρ measured by an autonomous ocean glider holding station by the ADCP. The method is used to measure the semidiurnal internal tide radiating from the Wyville Thomson Ridge in the North Atlantic. The observed energy flux (4.2±0.2 kW m−1) compares favourably with historic observations and a previous numerical model study. Error in the energy flux calculation due to imperfect co-location of the glider and ADCP is estimated by subsampling potential density in an idealized internal tide field along pseudorandomly distributed glider paths. The error is considered acceptable (

Giant ice rings on lakes and field observations of lens‐like eddies in the Middle Baikal (2016–2017) - Alexei V. Kouraev; Elena A. Zakharova; Frédérique Rémy; Andrey G. Kostianoy; Mikhail N. Shimaraev; Nicholas M. J. Hall; Roman E. Zdorovennov; Andrey Ya Suknev (Limnology and Oceanography, 2019)
Giant ice rings (diameter 5–7 km) detected on lakes Baikal (Russia) and Hovsgol (Mongolia) are a surface manifestation of intrathermocline lens‐like eddies under ice cover. By analyzing satellite imagery, we have detected new ice rings in 2016 and very old ones in 1969 for Lake Baikal. We have also discovered a giant ice ring on a new water body—Lake Teletskoye in the Altai Republic (Russia). Our recent field observations in the Middle Baikal have high temporal and spatial resolution and coverage and include temperature and current measurements over a long (1.5 month) period. In 2016, an eddy was detected in February and then an eddy and ice ring were detected in March at the same location. In 2017, another eddy was detected in February. This eddy was not stationary, as it was detected 6 km from its initial position in March, and thus no ice ring formed. The results of our field observations provide new data on the size and shape of the eddies. Indirect and direct measurements of currents and temporal evolution of the temperature field make it possible to estimate the rotation period (3 d) for the eddy in 2016 and assess the timing of movement, position, and displacement speed of the eddy in 2017. Thermal infrared Landsat imagery before ice formation in November–December 2015 shows that the eddy in 2016 was formed by the wind‐induced outflow from the Barguzin bay.

Pathogen exposure disrupts an organism's ability to cope with thermal stress - Tobias E. Hector; Carla M. Sgrò; Matthew D. Hall (Global Change Biology, 2019)
As a result of global climate change, species are experiencing an escalation in the severity and regularity of extreme thermal events. With patterns of disease distribution and transmission predicted to undergo considerable shifts in the coming years, the interplay between temperature and pathogen exposure will likely determine the capacity of a population to persist under the dual threat of global change and infectious disease. In this study, we investigated how exposure to a pathogen affects an individual's ability to cope with extreme temperatures. Using experimental infections of Daphnia magna with its obligate bacterial pathogen Pasteuria ramosa , we measured upper thermal limits of multiple host and pathogen genotype combinations across the dynamic process of infection and under various forms (static and ramping) of thermal stress. We find that pathogens substantially limit the thermal tolerance of their host, with the reduction in upper thermal limits on par with the breadth of variation seen across similar species entire geographical ranges. The precise magnitude of any reduction, however, was specific to the host and pathogen genotype combination. In addition, as thermal ramping rate slowed, upper thermal limits of both healthy and infected individuals were reduced. Our results suggest that the capacity of a population to evolve new thermal limits, when also faced with the threat of infection, will depend not only on a host's genetic variability in warmer environments, but also on the frequency of host and pathogen genotypes. We suggest that pathogen‐induced alterations of host thermal performance should be taken into account when assessing the resilience of any population and its potential for adaptation to global change.

Timing and characteristics of fractures along the Eastern Otway coastline, Great Ocean Road, Victoria - J. Vergunst; S. A. Vollgger; M. Hall; A. R. Cruden (Australian Journal of Earth Sciences, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Using 3D photogrammetry from ROV video to quantify cold-water coral reef structural complexity and investigate its influence on biodiversity and community assemblage - David M. Price; Katleen Robert; Alexander Callaway; Claudio Lo lacono; Rob A. Hall; Veerle A. I. Huvenne (Coral Reefs, 2019)

Electrophysiological and Behavioral Responses of Adult Vine Weevil, Otiorhynchus sulcatus (Coleoptera: Curculionidae), to Host Plant Odors - Joe M. Roberts; Jhaman Kundun; Charlotte Rowley; David R. Hall; Paul Douglas; Tom W. Pope (Journal of Chemical Ecology, 2019)

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.

Effects of shoreline permafrost thaw on nutrient dynamics and diatom ecology in a subarctic tundra pond - M. Q. Morison; O. Volik; R. I. Hall; J. A. Wiklund; M. L. Macrae; R. M. Petrone (Journal of Paleolimnology, 2019)

Primary Care Providers’ Intended Use of Decision Aids for Prostate-Specific Antigen Testing for Prostate Cancer Screening - Sun Hee Rim; Ingrid J. Hall; Greta M. Massetti; Cheryll C. Thomas; Jun Li; Lisa C. Richardson (Journal of Cancer Education, 2019)

Serological evidence of Zika virus infection in non-human primates in Zambia - Christida E. Wastika; Michihito Sasaki; Kentaro Yoshii; Paulina D. Anindita; Bernard M. Hang’ombe; Aaron S. Mweene; Shintaro Kobayashi; Hiroaki Kariwa; Michael J. Carr; William W. Hall; Yuki Eshita; Yasuko Orba; et al. (Archives of Virology, 2019)

Shelving the Coast With Vertipools: Retrofitting Artificial Rock Pools on Coastal Structures as Mitigation for Coastal Squeeze - Alice E. Hall; Roger J. H. Herbert; J. Robert Britton; Ian M. Boyd; Nigel C. George (Frontiers in Marine Science, 2019)

Mummified and skeletal southern elephant seals ( Mirounga leonina ) from the Victoria Land Coast, Ross Sea, Antarctica - Paul L. Koch; Brenda L. Hall; Mark de Bruyn; A. Rus Hoelzel; Carlo Baroni; M. Cristina Salvatore (Marine Mammal Science, 2019)
We report on an accumulation of mummified southern elephant seals ( Mirounga leonina) from Inexpressible Island on the Victoria Land Coast (VLC), western Ross Sea, Antarctica. This accumulation is unusual, as elephant seals typically breed and molt on sub‐Antarctic islands further north and do not currently occupy the VLC. Prior ancient DNA analyses revealed that these seals were part of a large, Antarctic breeding population that crashed ~1,000 yr ago. Radiocarbon dates for Inexpressible Island mummies range from 380 to 3,270 yr before present, too old to have been created by Scott's Northern Party in 1912 and varying too widely in age to represent a catastrophic death assemblage. Skeletal measurements reveal that most Inexpressible Island mummies are adult or subadult males. The presence of male elephant seals on Inexpressible Island until several hundred years ago suggests that, at a minimum, it served as a haul‐out site for the large Antarctic population and may have hosted a breeding colony. The conditions that allowed this Antarctic population to use the Ross Sea, the factors spurring its decline, and the implications for the adaptability and sensitivity of the species to environmental change all merit further study.

Effects of Ocean Acidification on Marine Photosynthetic Organisms Under the Concurrent Influences of Warming, UV Radiation, and Deoxygenation - Kunshan Gao; John Beardall; Donat-P. Häder; Jason M. Hall-Spencer; Guang Gao; David A. Hutchins (Frontiers in Marine Science, 2019)

Ecological determinants of pathogen transmission in communally roosting species - Andrew J. Laughlin; Richard J. Hall; Caz M. Taylor (Theoretical Ecology, 2019)

Microclimate Influences Mangrove Freeze Damage: Implications for Range Expansion in Response to Changing Macroclimate - Michael J. Osland; Arik M. Hartmann; Richard H. Day; Michael S. Ross; Courtney T. Hall; Laura C. Feher; William C. Vervaeke (Estuaries and Coasts, 2019)

Transient contributions to the forcing of the atmospheric annual cycle - Nicholas M. J. Hall; Stephanie Leroux; Tercio Ambrizzi (Climate Dynamics, 2019)

Streamflow regimes and geologic conditions are more important than water temperature when projecting future crayfish distributions - Kevin P. Krause; Huicheng Chien; Darren L. Ficklin; Damon M. Hall; Guenter A. Schuster; Todd M. Swannack; Chris A. Taylor; Jason H. Knouft (Climatic Change, 2019)

Planktonic larval duration, early growth, and the influence of dietary input on the otolith microstructure of Scolopsis bilineatus (Nemipteridae) - A. E. Hall; L. Vitale; M. J. Kingsford (Environmental Biology of Fishes, 2019)

Circuit‐theory applications to connectivity science and conservation - Brett G. Dickson; Christine M. Albano; Ranjan Anantharaman; Paul Beier; Joe Fargione; Tabitha A. Graves; Miranda E. Gray; Kimberly R. Hall; Josh J. Lawler; Paul B. Leonard; Caitlin E. Littlefield; Meredith L. McClure; et al. (Conservation Biology, 2019)
Conservation practitioners have long recognized ecological connectivity as a global priority for preserving biodiversity and ecosystem function. In the early years of conservation science, ecologists extended principles of island biogeography to assess connectivity based on source patch proximity and other metrics derived from binary maps of habitat. From 2006 to 2008, the late Brad McRae introduced circuit theory as an alternative approach to model gene flow and the dispersal or movement routes of organisms. He posited concepts and metrics from electrical circuit theory as a robust way to quantify movement across multiple possible paths in a landscape, not just a single least‐cost path or corridor. Circuit theory offers many theoretical, conceptual, and practical linkages to conservation science. We reviewed 459 recent studies citing circuit theory or the open‐source software Circuitscape. We focused on applications of circuit theory to the science and practice of connectivity conservation, including topics in landscape and population genetics, movement and dispersal paths of organisms, anthropogenic barriers to connectivity, fire behavior, water flow, and ecosystem services. Circuit theory is likely to have an effect on conservation science and practitioners through improved insights into landscape dynamics, animal movement, and habitat‐use studies and through the development of new software tools for data analysis and visualization. The influence of circuit theory on conservation comes from the theoretical basis and elegance of the approach and the powerful collaborations and active user community that have emerged. Circuit theory provides a springboard for ecological understanding and will remain an important conservation tool for researchers and practitioners around the globe.

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Science on the Sideline: Pragmatism and the Yellowstone River Basin Advisory Council - Susan J. Gilbertz; Damon M. Hall; Lucas C. Ward; Matthew B. Anderson (Water Resources Management, 2019)

Alcohol and Cocaine Exposure Modulates ABCB1 and ABCG2 Transporters in Male Alcohol-Preferring Rats - Alaa M. Hammad; Fawaz Alasmari; Youssef Sari; F. Scott Hall; Amit K. Tiwari (Molecular Neurobiology, 2019)

Growth, Photosynthesis, and Cold Tolerance of Eucalyptus benthamii Planted in the Piedmont of North Carolina - John R Butnor; Kurt H Johnsen; Peter H Anderson; Kevin B Hall; Joshua M Halman; Gary J Hawley; Christopher A Maier; Paul G Schaberg (Forest Science, 2019)

Spatial and temporal distribution of mobulid ray species in the eastern Pacific Ocean ascertained from observer data from the tropical tuna purse-seine fishery - N. Lezama-Ochoa; M. Hall; M. Román; N. Vogel (Environmental Biology of Fishes, 2019)

Harbor seal pup dispersal and individual morphology, hematology, and contaminant factors affecting survival - Denise J. Greig; Frances M. D. Gulland; James T. Harvey; Mike Lonergan; Ailsa J. Hall (Marine Mammal Science, 2019)
Understanding the factors affecting individual harbor seal ( Phoca vitulina ) survival is essential for determining population level health risks. We estimated postweaning dispersal, and modeled the effects of morphology, hematology, and blubber contaminants on the survival of recently weaned harbor seal pups using a mark recapture framework. We deployed satellite transmitters on apparently healthy pups captured in San Francisco Bay (SFB, n = 19) and Tomales Bay (TB, n = 7), and pups released after rehabilitation that stranded along the central California coast preweaning ( n = 21). Dispersal distances were further than previously reported for harbor seal pups (maximum = 802 km) which has implications for understanding risks to this vulnerable age class. We found differences in body condition, serum immunoglobulin and thyroxine (T4) concentrations, white blood cell count, and blubber organohalogen contamination (OH) among the three groups. Overall, increased T4, decreased OH, and increased mass were associated with greater survival probabilities; whereas, among stranded seals, greater mass gain, shorter time in rehabilitation, and admission to rehabilitation earlier in the season were associated with greater survival probabilities. Attention to these latter factors may improve the success of rehabilitation efforts. For wild pups, reduction of legacy contaminants and direct causes of mortality, such as ship strike, may enhance pup survival.

The perfect lawn: exploring neighborhood socio-cultural drivers for insect pollinator habitat - Andrea Burr; Damon M. Hall; Nicole Schaeg (Urban Ecosystems, 2018)

Impact of simulated mechanical hedge pruning and wood age on new shoot demography and return flowering in olive trees - Valeria Albarracín; Antonio J. Hall; Peter S. Searles; M. Cecilia Rousseaux (Trees, 2018)

Seasonal dynamics and potential drivers of ranavirus epidemics in wood frog populations - Emily M. Hall; C. S. Goldberg; J. L. Brunner; E. J. Crespi (Oecologia, 2018)

Outlier SNPs detect weak regional structure against a background of genetic homogeneity in the Eastern Rock Lobster, Sagmariasus verreauxi - Laura N. Woodings; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; Geoffrey W. Liggins; Bridget S. Green; Ira R. Cooke; James J. Bell; Jan M. Strugnell (Marine Biology, 2018)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

On the relationship between body condition and parasite infection in wildlife: a review and meta‐analysis - Cecilia A. Sánchez; Daniel J. Becker; Claire S. Teitelbaum; Paola Barriga; Leone M. Brown; Ania A. Majewska; Richard J. Hall; Sonia Altizer (Ecology Letters, 2018)
Body condition metrics are widely used to infer animal health and to assess costs of parasite infection. Since parasites harm their hosts, ecologists might expect negative relationships between infection and condition in wildlife, but this assumption is challenged by studies showing positive or null condition–infection relationships. Here, we outline common condition metrics used by ecologists in studies of parasitism, and consider mechanisms that cause negative, positive, and null condition–infection relationships in wildlife systems. We then perform a meta‐analysis of 553 condition–infection relationships from 187 peer‐reviewed studies of animal hosts, analysing observational and experimental records separately, and noting whether authors measured binary infection status or intensity. Our analysis finds substantial heterogeneity in the strength and direction of condition–infection relationships, a small, negative average effect size that is stronger in experimental studies, and evidence for publication bias towards negative relationships. The strongest predictors of variation in study outcomes are host thermoregulation and the methods used to evaluate body condition. We recommend that studies aiming to assess parasite impacts on body condition should consider host–parasite biology, choose condition measures that can change during the course of infection, and employ longitudinal surveys or manipulate infection status when feasible.

Dissolution: The Achilles’ Heel of the Triton Shell in an Acidifying Ocean - Ben P. Harvey; Sylvain Agostini; Shigeki Wada; Kazuo Inaba; Jason M. Hall-Spencer (Frontiers in Marine Science, 2018)

Soil multifunctionality and drought resistance are determined by plant structural traits in restoring grassland - Ellen L. Fry; Joanna Savage; Amy L. Hall; Simon Oakley; W. J. Pritchard; Nicholas J. Ostle; Richard F. Pywell; James M. Bullock; Richard D. Bardgett (Ecology, 2018)
It is increasingly recognized that belowground responses to vegetation change are closely linked to plant functional traits. However, our understanding is limited concerning the relative importance of different plant traits for soil functions and of the mechanisms by which traits influence soil properties in the real world. Here we test the hypothesis that taller species, or those with complex rooting structures, are associated with high rates of nutrient and carbon (C) cycling in grassland. We further hypothesized that communities dominated by species with deeper roots may be more resilient to drought. These hypotheses were tested in a 3‐yr grassland restoration experiment on degraded ex‐arable land in southern England. We sowed three trait‐based plant functional groups, assembled using database derived values of plant traits, and their combinations into bare soil. This formed a range of plant trait syndromes onto which we superimposed a simulated drought 2 yr after initial establishment. We found strong evidence that community weighted mean ( CWM ) of plant height is negatively associated with soil nitrogen cycling and availability and soil multifunctionality. We propose that this was due to an exploitative resource capture strategy that was inappropriate in shallow chalk soils. Further, complexity of root architecture was positively related to soil multifunctionality throughout the season, with fine fibrous roots being associated with greater rates of nutrient cycling. Drought resistance of soil functions including ecosystem respiration, mineralization, and nitrification were positively related to functional divergence of rooting depth, indicating that, in shallow chalk soils, a range of water capture strategies is necessary to maintain functions. Finally, after 3 yr of the experiment, we did not detect any links between the plant traits and microbial communities, supporting the finding that traits based on plant structure and resource foraging capacity are the main variables driving soil function in the early years of grassland conversion. We suggest that screening recently restored grassland communities for potential soil multifunctionality and drought resilience may be possible based on rooting architecture and plant height. These results indicate that informed assembly of plant communities based on plant traits could aid in the restoration of functioning in degraded soil.

Research Priorities to Support Effective Manta and Devil Ray Conservation - Joshua D. Stewart; Fabrice R. A. Jaine; Amelia J. Armstrong; Asia O. Armstrong; Michael B. Bennett; Katherine B. Burgess; Lydie I. E. Couturier; Donald A. Croll; Melissa R. Cronin; Mark H. Deakos; Christine L. Dudgeon; Daniel Fernando; et al. (Frontiers in Marine Science, 2018)

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Parasite rearing and infection temperatures jointly influence disease transmission and shape seasonality of epidemics - Marta S. Shocket; Daniela Vergara; Andrew J. Sickbert; Jason M. Walsman; Alexander T. Strauss; Jessica L. Hite; Meghan A. Duffy; Carla E. Cáceres; Spencer R. Hall (Ecology, 2018)
Seasonal epidemics erupt commonly in nature and are driven by numerous mechanisms. Here, we suggest a new mechanism that could determine the size and timing of seasonal epidemics: rearing environment changes the performance of parasites. This mechanism arises when the environmental conditions in which a parasite is produced impact its performance—independently from the current environment. To illustrate the potential for “rearing effects”, we show how temperature influences infection risk (transmission rate) in a Daphnia ‐fungus disease system through both parasite rearing temperature and infection temperature. During autumnal epidemics, zooplankton hosts contact (eat) fungal parasites (spores) reared in a gradually cooling environment. To delineate the effect of rearing temperature from temperature at exposure and infection, we used lab experiments to parameterize a mechanistic model of transmission rate. We also evaluated the rearing effect using spores collected from epidemics in cooling lakes. We found that fungal spores were more infectious when reared at warmer temperatures (in the lab and in two of three lakes). Additionally, the exposure (foraging) rate of hosts increased with warmer infection temperatures. Thus, both mechanisms cause transmission rate to drop as temperature decreases over the autumnal epidemic season (from summer to winter). Simulations show how these temperature‐driven changes in transmission rate can induce waning of epidemics as lakes cool. Furthermore, via thermally dependent transmission, variation in environmental cooling patterns can alter the size and shape of epidemics. Thus, the thermal environment drives seasonal epidemics through effects on hosts (exposure rate) and the infectivity of parasites (a rearing effect). Presently, the generality of parasite rearing effects remains unknown. Our results suggest that they may provide an important but underappreciated mechanism linking temperature to the seasonality of epidemics.

Fast Tracking of Fluid Invasion Using Time-Resolved Neutron Tomography - C. Jailin; M. Etxegarai; E. Tudisco; S. A. Hall; S. Roux (Transport in Porous Media, 2018)

Low salinity as a biosecurity tool for minimizing biofouling on ship sea chests - Maria Cecilia T. de Castro; Thomas Vance; Anna L. E. Yunnie; Timothy W. Fileman; Jason M. Hall-Spencer (Ocean Science, 2018)
Biofouling is a major vector in the transfer of non-native species around the world. Species can be transported on virtually all submerged areas of ships (e.g. hulls, sea chests, propellers) and so antifouling systems are used to reduce fouling. However, with increased regulation of biocides used in antifoulants (e.g. the International Maritime Organization tributyltin ban in 2008), there is a need to find efficient and sustainable alternatives. Here, we tested the hypothesis that short doses of low salinity water could be used to kill fouling species in sea chests. Settlement panels were suspended at 1.5 m depth in a Plymouth marina for 24 months by which time they had developed mature biofouling assemblages. We exposed these panels to three different salinities (7, 20 and 33) for 2 hours using a model sea chest placed in the marina and flushed with freshwater. Fouling organism diversity and abundance were assessed before panels were treated, immediately after treatment, and then 1 week and 1 month later. Some native ascidian Dendrodoa grossularia survived, but all other macrobenthos were killed by the salinity 7 treatment after 1 week. The salinity 20 treatment was not effective at killing the majority of fouling organisms. On the basis of these results, we propose that sea chests be flushed with freshwater for at least 2 hours before ships leave port. This would not cause unnecessary delays or costs and could be a major step forward in improving biosecurity.

Opportunistic seaweeds replace Cystoseira forests on an industrialised coast in Cyprus - DEMETRIS KLETOU; IOANNIS SAVVA; KONSTANTINOS TSIAMIS; JASON M. HALL-SPENCER (Mediterranean Marine Science, 2018)
Seaweeds are affected by humans worldwide, although no studies have assessed this in Cyprus. The Water Framework Directive requires ecological assessments of European coastal waters with biological indicators. We investigated macroalgal community metrics in the upper subtidal across ca 10 km of shoreline, encompassing undeveloped areas with limited human access as well as the most industrialised and impacted coast of Cyprus (Vasiliko Bay). Quadrats (20 x 20cm) were used to survey the algal communities in summer 2012 and spring 2013. Of the 51 taxa, we recorded, Cladophora nigrescens and Laurencia caduciramulosa (a non-native species) are new records for Cyprus. Brown algae of the genus Cystoseira, e.g., Cystoseira barbatula, formed dense forests covering rocky substrata on shorelines with limited human access. Cystoseira decreased in abundance around bathing waters and was very rare in heavily industrialised parts of the bay. In impacted areas, fleshy and filamentous opportunistic species such as opportunistic Ulva and Chaetomorpha species with lower biomass than perennial species, proliferated in spring. The Ecological Evaluation Index (EEI-c) we used was a robust biotic index reflecting anthropogenic stress. Without improved management, the Marine Strategy Framework Directive targets may not be met on some coastlines of Cyprus since seaweed forests are in decline and are further threatened by imminent development.

Design and placement of synthetic sex pheromone traps for cacao mirids in Ghana - J. E. Sarfo; C. A. M. Campbell; D. R. Hall (International Journal of Tropical Insect Science, 2018)

Female investment in offspring size and number shifts seasonally in a lizard with single-egg clutches - Timothy S. Mitchell; Joshua M. Hall; Daniel A. Warner (Evolutionary Ecology, 2018)

Shifting stream planform state decreases stream productivity yet increases riparian animal production - Michael P. Venarsky; David M. Walters; Robert O. Hall; Bridget Livers; Ellen Wohl (Oecologia, 2018)

Drought neutralises plant–soil feedback of two mesic grassland forbs - Ellen L. Fry; Giles N. Johnson; Amy L. Hall; W. James Pritchard; James M. Bullock; Richard D. Bardgett (Oecologia, 2018)

Information Seeking and Satisfaction with Information Sources Among Spouses of Men with Newly Diagnosed Local-Stage Prostate Cancer - Aasthaa Bansal; Lisel M. Koepl; Catherine R. Fedorenko; Chunyu Li; Judith Lee Smith; Ingrid J. Hall; David F. Penson; Scott D. Ramsey (Journal of Cancer Education, 2018)

Listening in the bog: I. Acoustic interactions and spacing between males of Sphagniana sphagnorum - Glenn K. Morris; Aaron M. Hall; Heiner Römer (Journal of Comparative Physiology A, 2018)

Diets of reef‐dwelling labrids ( Choerodon species) vary with body size, season and habitat: influence of foraging ability, specialization and opportunism - E. Lek; M. E. Platell; D. V. Fairclough; N. G. Hall; I. C. Potter (Journal of Fish Biology, 2018)
Contemporary multivariate statistics were used to test the hypotheses that the dietary compositions of three populations of labrids on the west Australian coast are related to body size and undergo seasonal changes and to elucidate the relative extents and basis for any dietary differences within and between those populations. Gut content analyses determined the dietary compositions of Choerodon rubescens in marine waters of the outer reefs in the World Heritage Area of Shark Bay (26° S; 114° E) and of Choerodon schoenleinii in inner protected reefs of that large embayment. The dietary compositions of C. rubescens and C. schoenleinii differed significantly among length classes, progressed serially with increasing body size, both overall and almost invariably in each season and were more closely related to body size than season, whose effect was at best minimal. The size‐related dietary change in C. rubescens involved, in particular, a shift from crustaceans and non‐mytilid bivalves to mytilid bivalves and echinoid echinoderms. Although the diet of C. schoenleinii followed similar size‐related changes, it contained a greater volume of gastropods when the fish were small and mytilids when large and only a small volume of echinoids. The dietary composition of C. rubescens in the Abrolhos Islands, 300 km to the south of Shark Bay, was related both to length class and season and differed from that of this labrid in Shark Bay with the ingestion of lesser volumes of mytilids and greater volumes of echinoids. The size‐related changes in diet imply that these species shift from foraging over soft substrata to over reefs as their very well‐developed jaws become sufficiently strong to remove attached and larger prey. The dietary compositions of C. rubescens and C. schoenleinii in Shark Bay and of C. rubescens at the Abrolhos Islands were related far more to habitat–locational differences than to length class and season. The above intraspecific and interspecific differences in diet are consistent with qualitative accounts of the relative abundances of the main prey in their respective environments, supporting the view that, despite specializations in their feeding apparatus, these labrids can feed opportunistically to a certain extent and could thus potentially respond to moderate changes in the composition of their prey caused by climate change and other anthropogenic effects.

Shelf sea tidal currents and mixing fronts determined from ocean glider observations - Peter M. F. Sheehan; Barbara Berx; Alejandro Gallego; Rob A. Hall; Karen J. Heywood; Sarah L. Hughes; Bastien Y. Queste (Ocean Science, 2018)
Tides and tidal mixing fronts are of fundamental importance to understanding shelf sea dynamics and ecosystems. Ocean gliders enable the observation of fronts and tide-dominated flows at high resolution. We use dive-average currents from a 2-month (12 October–2 December 2013) glider deployment along a zonal hydrographic section in the north-western North Sea to accurately determine M2 and S2 tidal velocities. The results of the glider-based method agree well with tidal velocities measured by current meters and with velocities extracted from the TPXO tide model. The method enhances the utility of gliders as an ocean-observing platform, particularly in regions where tide models are known to be limited. We then use the glider-derived tidal velocities to investigate tidal controls on the location of a front repeatedly observed by the glider. The front moves offshore at a rate of 0.51 km day−1. During the first part of the deployment (from mid-October until mid-November), results of a one-dimensional model suggest that the balance between surface heat fluxes and tidal stirring is the primary control on frontal location: as heat is lost to the atmosphere, full-depth mixing is able to occur in progressively deeper water. In the latter half of the deployment (mid-November to early December), a front controlled solely by heat fluxes and tidal stirring is not predicted to exist, yet a front persists in the observations. We analyse hydrographic observations collected by the glider to attribute the persistence of the front to the boundary between different water masses, in particular to the presence of cold, saline, Atlantic-origin water in the deeper portion of the section. We combine these results to propose that the front is a hybrid front: one controlled in summer by the local balance between heat fluxes and mixing and which in winter exists as the boundary between water masses advected to the north-western North Sea from diverse source regions. The glider observations capture the period when the front makes the transition from its summertime to wintertime state. Fronts in other shelf sea regions with oceanic influence may exhibit similar behaviour, with controlling processes and locations changing over an annual cycle. These results have implications for the thermohaline circulation of shelf seas.

Potential role of botanic garden collections in predicting hosts at risk globally from invasive pests: a case study using Scirtothrips dorsalis - A. S. Scott-Brown; J. Hodgetts; J. Hall; M. J. S. Simmonds; D. W. Collins (Journal of Pest Science, 2018)

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Early growth fault activity: new evidence for extension in the upper Cambrian Owen Group, Proprietary Peak, western Tasmania, Australia - M. J. O'Mara; S. A. Mahmud; M. Hall (Australian Journal of Earth Sciences, 2018)

Understanding the Factors that Influence Perceptions of Post-Wildfire Landscape Recovery Across 25 Wildfires in the Northwestern United States - C. Kooistra; T. E. Hall; T. Paveglio; M. Pickering (Environmental Management, 2018)

Shallow-level differentiation of phonolitic lavas from Sumaco Volcano, Ecuador - Jennifer M. Garrison; Kenneth W. W. Sims; Gene M. Yogodzinski; Ricardo D. Escobar; Sean Scott; Patricia Mothes; Minard L. Hall; Patricio Ramon (Contributions to Mineralogy and Petrology, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Natural acidification changes the timing and rate of succession, alters community structure, and increases homogeneity in marine biofouling communities - Norah E. M. Brown; Marco Milazzo; Samuel P. S. Rastrick; Jason M. Hall‐Spencer; Thomas W. Therriault; Christopher D. G. Harley (Global Change Biology, 2018)
Ocean acidification may have far‐reaching consequences for marine community and ecosystem dynamics, but its full impacts remain poorly understood due to the difficulty of manipulating p CO 2 at the ecosystem level to mimic realistic fluctuations that occur on a number of different timescales. It is especially unclear how quickly communities at various stages of development respond to intermediate‐scale p CO 2 change and, if high p CO 2 is relieved mid‐succession, whether past acidification effects persist, are reversed by alleviation of p CO 2 stress, or are worsened by departures from prior high p CO 2 conditions to which organisms had acclimatized. Here, we used reciprocal transplant experiments along a shallow water volcanic p CO 2 gradient to assess the importance of the timing and duration of high p CO 2 exposure (i.e., discrete events at different stages of successional development vs. continuous exposure) on patterns of colonization and succession in a benthic fouling community. We show that succession at the acidified site was initially delayed (less community change by 8 weeks) but then caught up over the next 4 weeks. These changes in succession led to homogenization of communities maintained in or transplanted to acidified conditions, and altered community structure in ways that reflected both short‐ and longer‐term acidification history. These community shifts are likely a result of interspecific variability in response to increased p CO 2 and changes in species interactions. High p CO 2 altered biofilm development, allowing serpulids to do best at the acidified site by the end of the experiment, although early (pretransplant) negative effects of p CO 2 on recruitment of these worms were still detectable. The ascidians Diplosoma sp. and Botryllus sp. settled later and were more tolerant to acidification. Overall, transient and persistent acidification‐driven changes in the biofouling community, via both past and more recent exposure, could have important implications for ecosystem function and food web dynamics.

Long-term precipitation-driven salinity change in a saline, peat-forming wetland in the Athabasca Oil Sands Region, Canada: a diatom-based paleolimnological study - Olena Volik; Richard M. Petrone; Roland I. Hall; Merrin L. Macrae; Corey M. Wells; Matthew C. Elmes; Jonathan S. Price (Journal of Paleolimnology, 2017)

Diversity of two widespread Indo-Pacific demosponge species revisited - Dirk Erpenbeck; Ratih Aryasari; Sarah Benning; Cécile Debitus; Emilie Kaltenbacher; Ali M. Al-Aidaroos; Peter Schupp; Kathryn Hall; John N. A. Hooper; Oliver Voigt; Nicole J. de Voogd; Gert Wörheide (Marine Biodiversity, 2017)

Inhibition of the receptor for advanced glycation end-products (RAGE) protects from secondhand smoke (SHS)-induced intrauterine growth restriction IUGR in mice - Joshua B. Lewis; Camilo Mejia; Clinton Jordan; Troy D. Monson; Jared S. Bodine; Todd M. Dunaway; Kaleb M. Egbert; Adam L. Lewis; Tanner J. Wright; K. Connor Ogden; Dallin S. Broberg; Parker D. Hall; et al. (Cell and Tissue Research, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Discovery of new orbiviruses and totivirus from Anopheles mosquitoes in Eastern Australia - Agathe M. G. Colmant; Kayvan Etebari; Cameron E. Webb; Scott A. Ritchie; Cassie C. Jansen; Andrew F. van den Hurk; Helle Bielefeldt-Ohmann; Jody Hobson-Peters; Sassan Asgari; Roy A. Hall (Archives of Virology, 2017)

Sensory Qualities of Oysters Unaltered by a Short Exposure to Combined Elevated pCO2 and Temperature - Anaëlle J. Lemasson; Victor Kuri; Jason M. Hall-Spencer; Stephen Fletcher; Roy Moate; Antony M. Knights (Frontiers in Marine Science, 2017)

Mule deer and energy development—Long‐term trends of habituation and abundance - Hall Sawyer; Nicole M. Korfanta; Ryan M. Nielson; Kevin L. Monteith; Dale Strickland (Global Change Biology, 2017)
As the extent and intensity of energy development in North America increases, so do disturbances to wildlife and the habitats they rely upon. Impacts to mule deer are of particular concern because some of the largest gas fields in the USA overlap critical winter ranges. Short‐term studies of 2–3 years have shown that mule deer and other ungulates avoid energy infrastructure; however, there remains a common perception that ungulates habituate to energy development, and thus, the potential for a demographic effect is low. We used telemetry data from 187 individual deer across a 17‐year period, including 2 years predevelopment and 15 years during development, to determine whether mule deer habituated to natural gas development and if their response to disturbance varied with winter severity. Concurrently, we measured abundance of mule deer to indirectly link behavior with demography. Mule deer consistently avoided energy infrastructure through the 15‐year period of development and used habitats that were an average of 913 m further from well pads compared with predevelopment patterns of habitat use. Even during the last 3 years of study, when most wells were in production and reclamation efforts underway, mule deer remained >1 km away from well pads. The magnitude of avoidance behavior, however, was mediated by winter severity, where aversion to well pads decreased as winter severity increased. Mule deer abundance declined by 36% during the development period, despite aggressive onsite mitigation efforts (e.g. directional drilling and liquid gathering systems) and a 45% reduction in deer harvest. Our results indicate behavioral effects of energy development on mule deer are long term and may affect population abundance by displacing animals and thereby functionally reducing the amount of available habitat.

Allocation, not male resistance, increases male frequency during epidemics: a case study in facultatively sexual hosts - Jessica L. Hite; Rachel M. Penczykowski; Marta S. Shocket; Katherine A. Griebel; Alexander T. Strauss; Meghan A. Duffy; Carla E. Cáceres; Spencer R. Hall (Ecology, 2017)
Why do natural populations vary in the frequency of sexual reproduction? Virulent parasites may help explain why sex is favored during disease epidemics. To illustrate, we show a higher frequency of males and sexually produced offspring in natural populations of a facultative parthenogenetic host during fungal epidemics. In a multi‐year survey of 32 lakes, the frequency of males (an index of sex) was higher in populations of zooplankton hosts with larger epidemics. A lake mesocosm experiment established causality: experimental epidemics produced a higher frequency of males relative to disease‐free controls. One common explanation for such a pattern involves Red Queen ( RQ ) dynamics. However, this particular system lacks key genetic specificity mechanisms required for the RQ , so we evaluated two other hypotheses. First, individual females, when stressed by infection, could increase production of male offspring vs. female offspring (a tenant of the “Abandon Ship” theory). Data from a life table experiment supports this mechanism. Second, higher male frequency during epidemics could reflect a purely demographic process (illustrated with a demographic model): males could resist infection more than females (via size‐based differences in resistance and mortality). However, we found no support for this resistance mechanism. A size‐based model of resistance, parameterized with data, revealed why: higher male susceptibility negated the lower exposure (a size‐based advantage) of males. These results suggest that parasite‐mediated increases in allocation to sex by individual females, rather than male resistance, increased the frequency of sex during larger disease epidemics.

Antifungal genes expressed in transgenic pea (Pisum sativum L.) do not affect root colonization of arbuscular mycorrhizae fungi - Jagroop Gill Kahlon; Hans-Jörg Jacobsen; James F. Cahill; Linda M. Hall (Mycorrhiza, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Fracture controls on valley persistence: the Cairngorm Granite pluton, Scotland - A. M. Hall; M. R. Gillespie (International Journal of Earth Sciences, 2017)

Cyprinid herpesvirus 3 as a potential biological control agent for carp ( Cyprinus carpio ) in Australia: susceptibility of non‐target species - K A McColl; A Sunarto; J Slater; K Bell; M Asmus; W Fulton; K Hall; P Brown; D Gilligan; J Hoad; L M Williams; M St J Crane (Journal of Fish Diseases, 2017)
Carp ( Cyprinus carpio L.) is a pest species in Australian waterways, and cyprinid herpesvirus 3 (Cy HV ‐3) is being considered as a potential biological control (biocontrol) agent. An important consideration for any such agent is its target specificity. In this study, the susceptibility to Cy HV ‐3 of a range of non‐target species ( NTS ) was tested. The NTS were as follows: 13 native Australian, and one introduced, fish species; a lamprey species; a crustacean; two native amphibian species (tadpole and mature stages); two native reptilian species; chickens; and laboratory mice. Animals were exposed to 100–1000 times the approximate minimum amount of Cy HV ‐3 required to cause disease in carp by intraperitoneal and/or bath challenge, and then examined clinically each day over the course of 28 days post‐challenge. There were no clinical signs, mortalities or histological evidence consistent with a viral infection in a wide taxonomic range of NTS . Furthermore, there was no molecular evidence of infection with Cy HV ‐3, and, in particular, all RT ‐ PCR s for viral mRNA were negative. As a consequence, the results encourage further investigation of Cy HV ‐3 as a potential biocontrol agent that is specific for carp.

Hydrological hazards in Russia: origin, classification, changes and risk assessment - N. L. Frolova; M. B. Kireeva; D. V. Magrickiy; M. B. Bologov; V. N. Kopylov; J. Hall; V. A. Semenov; A. E. Kosolapov; E. V. Dorozhkin; E. A. Korobkina; E. P. Rets; Y. Akutina; et al. (Natural Hazards, 2017)

Novel Bio-Logging Tool for Studying Fine-Scale Behaviors of Marine Turtles in Response to Sound - Reny B. Tyson; Wendy E. D. Piniak; Camila Domit; David Mann; Michael Hall; Douglas P. Nowacek; Mariana M. P. B. Fuentes (Frontiers in Marine Science, 2017)

Climate change‐induced vegetation shifts lead to more ecological droughts despite projected rainfall increases in many global temperate drylands - Britta Tietjen; Daniel R. Schlaepfer; John B. Bradford; William K. Lauenroth; Sonia A. Hall; Michael C. Duniway; Tamara Hochstrasser; Gensuo Jia; Seth M. Munson; David A. Pyke; Scott D. Wilson (Global Change Biology, 2017)
Drylands occur worldwide and are particularly vulnerable to climate change because dryland ecosystems depend directly on soil water availability that may become increasingly limited as temperatures rise. Climate change will both directly impact soil water availability and change plant biomass, with resulting indirect feedbacks on soil moisture. Thus, the net impact of direct and indirect climate change effects on soil moisture requires better understanding. We used the ecohydrological simulation model SOILWAT at sites from temperate dryland ecosystems around the globe to disentangle the contributions of direct climate change effects and of additional indirect, climate change‐induced changes in vegetation on soil water availability. We simulated current and future climate conditions projected by 16 GCM s under RCP 4.5 and RCP 8.5 for the end of the century. We determined shifts in water availability due to climate change alone and due to combined changes of climate and the growth form and biomass of vegetation. Vegetation change will mostly exacerbate low soil water availability in regions already expected to suffer from negative direct impacts of climate change (with the two RCP scenarios giving us qualitatively similar effects). By contrast, in regions that will likely experience increased water availability due to climate change alone, vegetation changes will counteract these increases due to increased water losses by interception. In only a small minority of locations, climate change‐induced vegetation changes may lead to a net increase in water availability. These results suggest that changes in vegetation in response to climate change may exacerbate drought conditions and may dampen the effects of increased precipitation, that is, leading to more ecological droughts despite higher precipitation in some regions. Our results underscore the value of considering indirect effects of climate change on vegetation when assessing future soil moisture conditions in water‐limited ecosystems.

Drivers and potential predictability of summer time North Atlantic polar front jet variability - Richard J. Hall; Julie M. Jones; Edward Hanna; Adam A. Scaife; Róbert Erdélyi (Climate Dynamics, 2017)

Ecophysiological responses to elevated CO2 and temperature in Cystoseira tamariscifolia (Phaeophyceae) - Paula S. M. Celis-Plá; Brezo Martínez; Nathalie Korbee; Jason M. Hall-Spencer; Félix L. Figueroa (Climatic Change, 2017)

Social-ecological system resonance: a theoretical framework for brokering sustainable solutions - Damon M. Hall; Andrea Feldpausch-Parker; Tarla Rai Peterson; Jennie C. Stephens; Elizabeth J. Wilson (Sustainability Science, 2017)

Sublethal effects of angling and release on golden perch Macquaria ambigua : implications for reproduction and fish health - K. C. Hall; M. K. Broadhurst; P. A. Butcher; L. Cameron; S. J. Rowland; R. B. Millar (Journal of Fish Biology, 2017)
The present study tested the hypothesis of no delayed sublethal effects of mild angling and release on the feeding, growth, somatic condition and gonadal development of golden perch Macquaria ambigua during gametogenesis. Subsamples of adult M. ambigua ( n = 17–21 of 207), originally captured from the wild and stocked into ten 0·1 ha earthen ponds, were angled and released during early and late gametogenesis. Wild samples that were concurrently collected throughout the experiment underwent rapid and synchronous gonadal development and many spawned. While no spawning occurred in the ponds, most M. ambigua underwent normal gonadal development to maturity, including the angled fish. Angled fish also fed, maintained condition and actually grew faster than non‐angled captive controls. Although females that were angled during late gametogenesis more readily ingested and retained baited hooks, neither their subsequent condition nor gonadal development was significantly affected. The predominance of null results was attributed to the combined effects of the flexible reproductive strategy of M. ambigua , the benignness of mouth hooking and immediate release, and possible methodological issues arising from differential hooking success of more aggressive and resilient individuals. The findings support earlier catch‐and‐release research, but contrast with reports of acute reproductive effects following capture and handling for aquaculture broodstock. This discrepancy highlights the need for research to specifically address welfare questions relevant to recreational fisheries across various species and angling scenarios.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Epipodial Tentacle Gene Expression and Predetermined Resilience to Summer Mortality in the Commercially Important Greenlip Abalone, Haliotis laevigata - Brett P. Shiel; Nathan E. Hall; Ira R. Cooke; Nicholas A. Robinson; Jan M. Strugnell (Marine Biotechnology, 2017)

Impact of the observed extratropics on climatological simulations of the MJO in a tropical channel model - Nicholas M. J. Hall; Séverin Thibaut; Patrick Marchesiello (Climate Dynamics, 2017)

Generation of Paramoeba perurans clonal cultures using flow cytometry and confirmation of virulence - C Collins; M Hall; D Bruno; J Sokolowska; L Duncan; R Yuecel; U McCarthy; M J Fordyce; C C Pert; R McIntosh; Z MacKay (Journal of Fish Diseases, 2017)
Amoebic gill disease ( AGD ) in farmed Atlantic salmon is caused by the amoeba Paramoeba perurans . The recent establishment of in vitro culture techniques for P. perurans has provided a valuable tool for studying the parasite in detail. In this study, flow cytometry was used to generate clonal cultures from single‐sorted amoeba, and these were used to successfully establish AGD in experimental Atlantic salmon. The clonal cultures displayed differences in virulence, based on gill scores. The P. perurans load on gills, determined by qPCR analysis, showed a positive relationship with gill score, and with clonal virulence, indicating that the ability of amoebae to proliferate and/or remain attached on gills may play a role in virulence. Gill scores based on gross signs and histopathological analysis were in agreement. No association between level of gill score and specific gill arch was observed. It was found that for fish with lower gill scores based on histopathological examination, gross examination and qPCR analysis of gills from the same fish were less successful in detecting lesions and amoebae, respectively.

Stratigraphic reconstruction of the Strzelecki Group outcrops in west Gippsland: new data on the present-day thickness and amount of erosion - H. Aghaei; M. Hall; B. Wagstaff; A. Tait (Australian Journal of Earth Sciences, 2017)

Middle to Late Devensian glaciation of north‐east Scotland: implications for the north‐eastern quadrant of the last British–Irish ice sheet - Jon W. Merritt; E. Rodger Connell; Adrian M. Hall (Journal of Quaternary Science, 2017)
We present a review of over 175 years of research into the Middle to Late Devensian (Weichselian) glaciation of NE Scotland based crucially on both its lithostratigraphic and geomorphic records. The location of the region, and surrounding seabed, makes this unusually detailed record significant for deciphering the former interactions and dynamics of Scottish and Scandinavian ice within the North Sea Basin (NSB), which continue to be controversial. A 12‐stage event stratigraphy is proposed based on a parsimonious interpretation of stratigraphic relationships, till lithology and regional clast fabrics, striae, subglacial bedforms, ice‐marginal features and published geochronometry at critical sites. The record of regional glaciation supports converging evidence that the north‐eastern quadrant of the last British and Irish Ice Sheet reached its maximum spatial extent in the late Middle to early Late Devensian and later re‐expanded following widespread internal glacial reorganizations, marine transgression and partial retreat from the central NSB. Retreat was interrupted by several glacial readvances of limited extent. Field‐captured data help to identify important events that are not clearly resolved from remote sensing alone, particularly regarding growth phases of the last glaciation.

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Digging Deep: Managing Social and Policy Dimensions of Geoduck Aquaculture Conflict in Puget Sound, Washington - C. M. Ryan; P. S. McDonald; D. S. Feinberg; L. W. Hall; J. G. Hamerly; C. W. Wright (Coastal Management, 2017)

Examining the historical and present energy metabolism of a Rust Belt City: Syracuse, NY 1840–2005 - Stephen Balogh; Charles A. S. Hall; Drew V. Gamils; Alexander M. Popov; Ryan T. Rose (Urban Ecosystems, 2016)

Temporal and spatial dynamics of a “Rust-Belt” urban stream: Metabolic and water quality responses to hardened land - K. E. Limburg; D. P. Swaney; M. H. Hall (Urban Ecosystems, 2016)

Variation in the population demographics of Scolopsis bilineatus in response to predators - A. E. Hall; M. J. Kingsford (Coral Reefs, 2016)

Cross-pressuring conservative Catholics? Effects of Pope Francis’ encyclical on the U.S. public opinion on climate change - Nan Li; Joseph Hilgard; Dietram A. Scheufele; Kenneth M. Winneg; Kathleen Hall Jamieson (Climatic Change, 2016)

Outlier SNPs enable food traceability of the southern rock lobster, Jasus edwardsii - Cecilia Villacorta-Rath; Irina Ilyushkina; Jan M. Strugnell; Bridget S. Green; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; James J. Bell (Marine Biology, 2016)

Reopening of a Remote Tidal Inlet Increases Recruitment of Estuarine-Dependent Nekton - Quentin A. Hall; Megan M. Reese Robillard; Jason A. Williams; Matthew J. Ajemian; Gregory W. Stunz (Estuaries and Coasts, 2016)

Late readvance and rapid final deglaciation of the last ice sheet in the Grampian Mountains, Scotland - Adrian M. Hall; Steven A. Binnie; David Sugden; Tibor J. Dunai; Christina Wood (Journal of Quaternary Science, 2016)
Towards the end of the last glaciation, ice sourced from the western Grampian Mountains of Scotland flowed down Strath Spey to encroach on the northern flanks of the Cairngorm Mountains. The maximum of this late advance and its subsequent retreat is recorded by moraines, ice‐marginal meltwater channels, and kame terraces that can be traced for 60 km along Strath Spey. New cosmogenic 10 Be exposure ages from moraines indicate deglaciation at 15.1 ± 1.1 ka. This timing matches closely the recalibrated mean ages of 14.7 ± 0.7 and 15.2 ± 0.7 ka for the Wester Ross Readvance in the North‐West Highlands. A synchronous readvance of the British–Irish Ice Sheet (BIIS) towards the end of Greenland Stadial 2a (GS‐2a) (16.9–14.7 ka) is indicated. Thereafter active ice retreat from the flanks of Strath Spey was rapid, occurring within the ∼1 ka uncertainty of the cosmogenic exposure ages. We suggest the advance followed the collapse of the marine parts of the BIIS at ∼16 ka due to conditions of increased precipitation occurring at a time of low temperatures. The rapidity of deglaciation may reflect enhanced Föhn effects caused by the ice dome in the western Grampians.

Clinical Phenotype of Adult Fragile X Gray Zone Allele Carriers: a Case Series - Sarah M. Debrey; Maureen A. Leehey; Olga Klepitskaya; Christopher M. Filley; Raj C. Shah; Benzi Kluger; Elizabeth Berry-Kravis; Elaine Spector; Flora Tassone; Deborah A. Hall (The Cerebellum, 2016)

Discovery and complete genome sequence of a novel circovirus-like virus in the endangered rowi kiwi, Apteryx rowi - Daniel J. White; Richard J. Hall; Jing Wang; Nicole E. Moore; Duckchul Park; Kate McInnes; Brett D. Gartrell; Daniel M. Tompkins (Virus Genes, 2016)

Contrasting soil nitrogen dynamics across a montane meadow and urban lawn in a semi-arid watershed - Steven J. Hall; Michelle A. Baker; Scott B. Jones; John M. Stark; David R. Bowling (Urban Ecosystems, 2016)

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

The biodiversity of the United Kingdom’s Overseas Territories: a stock take of species occurrence and assessment of key knowledge gaps - Thomas Churchyard; M. A. Eaton; S. Havery; J. Hall; J. Millett; A. Farr; R. J. Cuthbert; C. Stringer; J. A. Vickery (Biodiversity and Conservation, 2016)

Genome‐wide set of SNP s reveals evidence for two glacial refugia and admixture from postglacial recolonization in an alpine ungulate - Zijian Sim; Jocelyn C. Hall; Bill Jex; Troy M. Hegel; David W. Coltman (Molecular Ecology, 2016)
Past glaciation events have played a major role in shaping the genetic diversity and distribution of wild sheep in North America. The advancement of glaciers can isolate populations in ice‐free refugia, where they can survive until the recession of ice sheets. The major Beringian refugium is thought to have held thinhorn sheep ( Ovis dalli ) populations during times of glacial advance. While isolation in the major refugium can account for much of the genetic and morphological diversity seen in extant thinhorn sheep populations, mounting evidence suggests the persistence of populations in smaller minor refugia. We investigated the refugial origins of thinhorn sheep using ~10 000 SNP s obtained via a cross‐species application of the domestic sheep ovine HD BeadChip to genotype 52 thinhorn sheep and five bighorn sheep ( O. canadensis ) samples. Phylogenetic inference revealed a distinct lineage of thinhorn sheep inhabiting British Columbia, which is consistent with the survival of a group of thinhorn sheep in a minor refugium separate from the Beringian refugium. Isolation in separate glacial refugia probably mediated the evolution of the two thinhorn sheep subspecies, the white Dall's sheep ( O. d. dalli ), which persisted in Beringia, and the dark Stone's sheep ( O. d. stonei ), which utilized the minor refugium. We also found the first genetic evidence for admixture between sheep from different glacial refugia in south‐central Yukon as a consequence of post glacial expansion and recolonization. These results show that glaciation events can have a major role in the evolution of species inhabiting previously glaciated habitats and the need to look beyond established refugia when examining the evolutionary history of such species.

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Localization and regulation of PML bodies in the adult mouse brain - Małgorzata H. Hall; Adriana Magalska; Monika Malinowska; Błażej Ruszczycki; Iwona Czaban; Satyam Patel; Magdalena Ambrożek-Latecka; Ewa Zołocińska; Hanna Broszkiewicz; Kamil Parobczak; Rajeevkumar R. Nair; Marcin Rylski; et al. (Brain Structure and Function, 2016)

Rumen Microorganisms Decrease Bioavailability of Inorganic Selenium Supplements - M. L. Galbraith; W. R. Vorachek; C. T. Estill; P. D. Whanger; G. Bobe; T. Z. Davis; J. A. Hall (Biological Trace Element Research, 2016)

Plant nitrogen concentration and isotopic composition in residential lawns across seven US cities - T. L. E. Trammell; D. E. Pataki; J. Cavender-Bares; P. M. Groffman; S. J. Hall; J. B. Heffernan; S. E. Hobbie; J. L. Morse; C. Neill; K. C. Nelson (Oecologia, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Giant ice rings on lakes B aikal and H ovsgol: Inventory, associated water structure and potential formation mechanism - Alexei V. Kouraev; Elena A. Zakharova; Frédérique Rémy; Andrey G. Kostianoy; Michail N. Shimaraev; Nicholas M. J. Hall; Andrey Ya. Suknev (Limnology and Oceanography, 2016)
Observations of giant ice rings on Lake Baikal (Russia) have recently sparked scientific and public interest. However, there is still no clear consensus on their origins. Here, we provide an inventory of the ice rings based on satellite imagery and photography for 1974–2014. We have identified 45 rings on Lake Baikal (compared with 13 previously known) and also for the first time four rings for the neighbouring Lake Hovsgol (Mongolia). The results of our hydrographic surveys beneath the ice rings in Lake Baikal in 2012–2014 and in Lake Hovsgol in 2015 show the presence of warm double‐convex lens‐like eddies before and during manifestation of ice rings. We suggest that these eddies are the driving factor for the formation of ice rings in these lakes. We reassess the existing hypotheses of ice ring formation and discuss the potential mechanisms of eddy formation.

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

Effects of individual, community, and landscape drivers on the dynamics of a wildland forest epidemic - Sarah E. Haas; J. Hall Cushman; Whalen W. Dillon; Nathan E. Rank; David M. Rizzo; Ross K. Meentemeyer (Ecology, 2016)
The challenges posed by observing host–pathogen–environment interactions across large geographic extents and over meaningful time scales limit our ability to understand and manage wildland epidemics. We conducted a landscape‐scale, longitudinal study designed to analyze the dynamics of sudden oak death (an emerging forest disease caused by Phytophthora ramorum ) across hierarchical levels of ecological interactions, from individual hosts up to the community and across the broader landscape. From 2004 to 2011, we annually assessed disease status of 732 coast live oak, 271 black oak, and 122 canyon live oak trees in 202 plots across a 275‐km 2 landscape in central California. The number of infected oak stems steadily increased during the eight‐year study period. A survival analysis modeling framework was used to examine which level of ecological heterogeneity best predicted infection risk of susceptible oak species, considering variability at the level of individuals (species identity, stem size), the community (host density, inoculum load, and species richness), and the landscape (seasonal climate variability, habitat connectivity, and topographic gradients). After accounting for unobserved risk shared among oaks in the same plot, survival models incorporating heterogeneity across all three levels better predicted oak infection than did models focusing on only one level. We show that larger oak trees (especially coast live oak) were more susceptible, and that interannual variability in inoculum production by the highly infectious reservoir host, California bay laurel, more strongly influenced disease risk than simply the density of this important host. Concurrently, warmer and wetter rainy‐season conditions in consecutive years intensified infection risk, presumably by creating a longer period of inoculum build‐up and increased probability of pathogen spillover from bay laurel to oaks. Despite the presence of many alternate host species, we found evidence of pathogen dilution, where less competent hosts in species‐rich communities reduce pathogen transmission and overall risk of oak infection. These results identify key parameters driving the dynamics of emerging infectious disease in California woodlands, while demonstrating how multiple levels of ecological heterogeneity jointly determine epidemic trajectories in wildland settings.

Competition‐mediated feedbacks in experimental multispecies epizootics - Tad Dallas; Richard J. Hall; John M. Drake (Ecology, 2016)
Competition structures ecological communities and alters host–pathogen interactions. In environmentally transmitted pathogens, an infection‐resistant competitor may influence infection dynamics in a susceptible species through the negative impacts of competition (e.g., by reducing host density or causing nutritional stress that increases susceptibility to infection) and/or the positive impacts of reducing transmission efficiency (e.g., by removing environmental pathogen stages). Thus, a non‐susceptible competitor may enhance, reduce, or have no net effect on susceptible host density and infection prevalence. Here, we couple an epidemiological model with experimental epidemics to test how resource competition with a non‐susceptible competitor ( Daphnia pulicaria ) influences fungal microparasite ( Metschnikowia bicuspidata ) infection dynamics in a susceptible host species ( D. dentifera ). Our model and experiments suggest that competitor density can mediate the direction and magnitude of the effect of competition on infection dynamics, with a peak in infection prevalence occurring at intermediate competitor densities. At low densities, the non‐susceptible competitor D. pulicaria may reduce infection prevalence in the susceptible host by removing fungal spores from the environment through feeding. However, when competitor density is increased and resources become limiting, D. pulicaria negatively impacts the susceptible host by increasing susceptible host feeding rates, and therefore fungal spore intake, and further by reducing susceptible host population size as it is driven toward competitive exclusion. In conclusion, these results show that a tradeoff between the competitor as a consumer of pathogen, which serves to reduce epidemic size, and as a modifier of susceptible host foraging ecology, which influences infection rates, may alternately enhance or dampen the magnitude of local epidemics.

Effect of Zinc Intake on Growth in Infants: A Meta-analysis - M. Nissensohn; A. Sánchez-Villegas; D. Fuentes Lugo; P. Henríquez Sánchez; J. Doreste Alonso; L. Peña Quintana; C. Ruano; N. L. Lowe; V. Hall Moran; A. L. Skinner; M. Warthon-Medina; L. Serra-Majem (Critical Reviews in Food Science and Nutrition, 2016)

The variation of crustal stretching and different modes of rifting along the Australian southern continental margin - N. Kharazizadeh; W. P. Schellart; J. C. Duarte; M. Hall (Australian Journal of Earth Sciences, 2016)

Adoption of a national antimicrobial guide (SWAB-ID) in the Netherlands - Emelie C. Schuts; Caroline M. van den Bosch; Inge C. Gyssens; Bart-Jan Kullberg; Maurine A. Leverstein-van Hall; Stephanie Natsch; Fre Sebens; Martha B. Adams; Richard Drew; Jan M. Prins (European Journal of Clinical Pharmacology, 2016)

Photo‐identification as a simple tool for studying invasive lionfish Pterois volitans populations - L. C. T. Chaves; J. Hall; J. L. L. Feitosa; I. M. Côté (Journal of Fish Biology, 2016)
Photo‐tagging, i.e. using a specific software to match colour patterns on photographs, was tested as a means to identify individual Indo‐Pacific Pterois volitans to assist with population and movement studies of this invasive species. The stripe pattern on the flank of adult P. volitans ( n = 48) was the most individually distinctive of three body regions tested, leading to correct individual identification on 68 and 82% of tests with a single and two images of the reference individual, respectively. Photo‐tagging is inexpensive, logistically simple and can involve citizen scientists, making it a viable alternative to traditional tagging to provide information on P. volitans distribution, movement patterns and recolonization rates after removals.

Parasites destabilize host populations by shifting stage‐structured interactions - Jessica L. Hite; Rachel M. Penczykowski; Marta S. Shocket; Alexander T. Strauss; Paul A. Orlando; Meghan A. Duffy; Carla E. Cáceres; Spencer R. Hall (Ecology, 2016)
Should parasites stabilize or destabilize consumer–resource dynamics? Recent theory suggests that parasite‐enhanced mortality may confer underappreciated stability to their hosts. We tested this hypothesis using disease in zooplankton. Across both natural and experimental epidemics, bigger epidemics correlated with larger—not smaller—host fluctuations. Thus, we tested two mechanistic hypotheses to explain destabilization or apparent destabilization by parasites. First, enrichment could, in principle, simultaneously enhance both instability and disease prevalence. In natural epidemics, destabilization was correlated with enrichment (indexed by total phosphorous). However, an in situ (lake enclosure) experiment did not support these links. Instead, field and experimental results point to a novel destabilizing mechanism involving host stage structure. Epidemics pushed hosts from relatively more stable host dynamics with less‐synchronized juveniles and adults to less stable dynamics with more‐synchronized juveniles and adults. Our results demonstrate how links between host stage structure and disease can shape host/consumer–resource stability.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Sustainable development education, practice, and research: an indigenous model of sustainable development at the College of Menominee Nation, Keshena, WI, USA - Michael J. Dockry; Katherine Hall; William Van Lopik; Christopher M. Caldwell (Sustainability Science, 2016)

Sex differences and endocrine regulation of auditory-evoked, neural responses in African clawed frogs (Xenopus) - Ian C. Hall; Sarah M. N. Woolley; Ursula Kwong-Brown; Darcy B. Kelley (Journal of Comparative Physiology A, 2016)

Forest restoration following surface mining disturbance: challenges and solutions - S. Ellen Macdonald; Simon M. Landhäusser; Jeff Skousen; Jennifer Franklin; Jan Frouz; Sarah Hall; Douglass F. Jacobs; Sylvie Quideau (New Forests, 2015)

Structural evolution of the Early Cretaceous depocentres, Otway Basin, Victoria - D. Briguglio; M. Hall; J. Keetley (Australian Journal of Earth Sciences, 2015)

Evaluation of fluorophore-tethered platinum complexes to monitor the fate of cisplatin analogs - Justin C. Jagodinsky; Agnieszka Sulima; Yiqi Cao; Joanna E. Poprawski; Burchelle N. Blackman; John R. Lloyd; Rolf E. Swenson; Michael M. Gottesman; Matthew D. Hall (JBIC Journal of Biological Inorganic Chemistry, 2015)

Behavioral Assay on Asian Citrus Psyllid Attraction to Orange Jasmine - David G. Hall; Matthew G. Hentz; Joseph M. Patt (Journal of Insect Behavior, 2015)

The strength of the tropical inversion and its response to climate change in 18 CMIP5 models - Xin Qu; Alex Hall; Stephen A. Klein; Peter M. Caldwell (Climate Dynamics, 2015)

Drivers of North Atlantic Polar Front jet stream variability - Richard Hall; Róbert Erdélyi; Edward Hanna; Julie M. Jones; Adam A. Scaife (International Journal of Climatology, 2015)
Polar front jet stream variability is responsible for instances of extreme weather and is crucial for regional climate change. The North Atlantic Polar Front jet stream is of particular significance to the heavily populated areas of western Europe and eastern North America as storm track variability, atmospheric modes of variability such as the North Atlantic Oscillation (NAO), temperature and rainfall are all intimately linked with jet stream changes. Although seasonal and interannual variability are often attributed to internal variability, there are several possible drivers of polar front jet stream changes that are reviewed in this study. Cryospheric effects from sea‐ice extent and snow cover, oceanic effects from North Atlantic sea‐surface temperatures and tropical influences such as the El‐Niño Southern Oscillation, and stratospheric effects due to stratospheric circulation variability, solar variability, volcanic eruptions and the Quasi‐Biennial Oscillation are all identified in the literature as factors that impact on the Atlantic Polar Front jet stream. These drivers of jet stream variability can oppose or reinforce one another, and there are some indications of possible nonlinear interactions between them. We also review the modelling of jet stream variability. While a consensus has now been reached that some observed drivers can be reproduced in climate models, we conclude that improved understanding of more recently identified drivers of the Atlantic extratropical jet stream is crucial for making progress in regional climate predictions on all timescales from months to decades ahead.

A survey of wild marine fish identifies a potential origin of an outbreak of viral haemorrhagic septicaemia in wrasse, L abridae, used as cleaner fish on marine A tlantic salmon, S almo salar L ., farms - I S Wallace; K Donald; L A Munro; W Murray; C C Pert; H Stagg; M Hall; N Bain (Journal of Fish Diseases, 2015)
Viral haemorrhagic septicaemia virus ( VHSV ) was isolated from five species of wrasse ( L abridae) used as biological controls for parasitic sea lice predominantly, Lepeophtheirus salmonis ( K røyer, 1837), on marine A tlantic salmon, S almo salar L ., farms in S hetland. As part of the epidemiological investigation, 1400 wild marine fish were caught and screened in pools of 10 for VHSV using virus isolation. Eleven pools (8%) were confirmed VHSV positive from: grey gurnard, E utrigla gurnardus L .; A tlantic herring, C lupea harengus L .; N orway pout, T risopterus esmarkii ( N ilsson); plaice, P leuronectes platessa L .; sprat, S prattus sprattus L . and whiting, M erlangius merlangus L . The isolation of VHSV from grey gurnard is the first documented report in this species. Nucleic acid sequencing of the partial nucleocapsid ( N ) and glycoprotein ( G ) genes was carried out for viral characterization. Sequence analysis confirmed that all wild isolates were genotype III the same as the wrasse and there was a close genetic similarity between the isolates from wild fish and wrasse on the farms. Infection from these local wild marine fish is the most likely source of VHSV isolated from wrasse on the fish farms.

Calcification is not the Achilles’ heel of cold‐water corals in an acidifying ocean - Riccardo Rodolfo‐Metalpa; Paolo Montagna; Stefano Aliani; Mireno Borghini; Simonepietro Canese; Jason M. Hall‐Spencer; Andy Foggo; Marco Milazzo; Marco Taviani; Fanny Houlbrèque (Global Change Biology, 2015)
Ocean acidification is thought to be a major threat to coral reefs: laboratory evidence and CO 2 seep research has shown adverse effects on many coral species, although a few are resilient. There are concerns that cold‐water corals are even more vulnerable as they live in areas where aragonite saturation (Ω ara ) is lower than in the tropics and is falling rapidly due to CO 2 emissions. Here, we provide laboratory evidence that net (gross calcification minus dissolution) and gross calcification rates of three common cold‐water corals, Caryophyllia smithii , Dendrophyllia cornigera, and Desmophyllum dianthus, are not affected by p CO 2 levels expected for 2100 ( p CO 2 1058 μatm, Ω ara 1.29), and nor are the rates of skeletal dissolution in D. dianthus . We transplanted D. dianthus to 350 m depth ( pH T 8.02; p CO 2 448 μatm, Ω ara 2.58) and to a 3 m depth CO 2 seep in oligotrophic waters ( pH T 7.35; p CO 2 2879 μatm, Ω ara 0.76) and found that the transplants calcified at the same rates regardless of the p CO 2 confirming their resilience to acidification, but at significantly lower rates than corals that were fed in aquaria. Our combination of field and laboratory evidence suggests that ocean acidification will not disrupt cold‐water coral calcification although falling aragonite levels may affect other organismal physiological and/or reef community processes.

Macroalgal responses to ocean acidification depend on nutrient and light levels - Paula S. M. Celis-PlÃ¡; Jason M. Hall-Spencer; Paulo Antunes Horta; Marco Milazzo; Nathalie Korbee; Christopher E. Cornwall; FÃ©lix L. Figueroa (Frontiers in Marine Science, 2015)

From Red Tides to Green and Brown Tides: Bloom Dynamics in a Restricted Subtropical Lagoon Under Shifting Climatic Conditions - Edward J. Phlips; Susan Badylak; Margaret A. Lasi; Robert Chamberlain; Whitney C. Green; Lauren M. Hall; Jane A. Hart; Jean C. Lockwood; Janice D. Miller; Lori J. Morris; Joel S. Steward (Estuaries and Coasts, 2015)

Microplastic ingestion by scleractinian corals - N. M. Hall; K. L. E. Berry; L. Rintoul; M. O. Hoogenboom (Marine Biology, 2015)

De Novo Characterisation of the Greenlip Abalone Transcriptome (Haliotis laevigata) with a Focus on the Heat Shock Protein 70 (HSP70) Family - Brett P. Shiel; Nathan E. Hall; Ira R. Cooke; Nicholas A. Robinson; Jan M. Strugnell (Marine Biotechnology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Trace elements and major ions in atmospheric wet and dry deposition across central Illinois, USA - Mary M. Lynam; J. Timothy Dvonch; Naima L. Hall; Masako Morishita; James A. Barres (Air Quality, Atmosphere & Health, 2015)

Estimating the prevalence of Renibacterium salmoninarum ‐infected salmonid production sites - L M Hall; S Duguid; I S Wallace; A G Murray (Journal of Fish Diseases, 2015)

Fragmented Tasmania: the transition from Rodinia to Gondwana - D. H. Moore; P. G. Betts; M. Hall (Australian Journal of Earth Sciences, 2015)

Scaling categorical spatial data for earth systems models - Jaclyn M. Hall; Caroline G. Staub; Matthew P. Marsik; Forrest R. Stevens; Michael W. Binford (Global Change Biology, 2015)

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Nutritional enhancement of leaves by a psyllid through senescence-like processes: insect manipulation or plant defence? - M. J. Steinbauer; A. E. Burns; A. Hall; M. Riegler; G. S. Taylor (Oecologia, 2014)

Phoma stem canker disease on oilseed rape (Brassica napus) in China is caused by Leptosphaeria biglobosa ‘brassicae’ - Ze Liu; Akinwunmi O. Latunde-Dada; Avice M. Hall; Bruce D. L. Fitt (European Journal of Plant Pathology, 2014)

The diversity of seaweeds on maerl in the NE Atlantic - V. Peña; I. Bárbara; J. Grall; C. A. Maggs; J. M. Hall-Spencer (Marine Biodiversity, 2014)

Ecological and Social Outcomes of a New Protected Area in Tanzania - JACLYN M. HALL; NEIL D. BURGESS; SALLA RANTALA; HEINI VIHEMÄKI; GEORGE JAMBIYA; ROY E. GEREAU; FORTUNATUS MAKONDA; FADHILI NJILIMA; PETER SUMBI; ADAM KIZAJI (Conservation Biology, 2014)
Balancing ecological and social outcomes of conservation actions is recognized in global conservation policy but is challenging in practice. Compensation to land owners or users for foregone assets has been proposed by economists as an efficient way to mitigate negative social impacts of human displacement from protected areas. Joint empirical assessments of the conservation and social impacts of protected area establishment involving compensation payments are scarce. We synthesized social and biological studies related to the establishment of the Derema forest corridor in Tanzania's biodiverse East Usambara Mountains. This lengthy conservation process involved the appropriation of approximately 960 ha of native canopy agroforest and steep slopes for the corridor and monetary compensation to more than 1100 claimants in the surrounding villages. The overarching goals from the outset were to conserve ecological processes while doing no harm to the local communities. We evaluated whether these goals were achieved by analyzing 3 indicators of success: enhancement of forest connectivity, improvement of forest condition, and mitigation of negative impacts on local people's livelihoods. Indicators of forest connectivity and conditions were enhanced through reductions of forest loss and exotic species and increases in native species and canopy closure. Despite great efforts by national and international organizations, the intervention failed to mitigate livelihood losses especially among the poorest people. The Derema case illustrates the challenges of designing and implementing compensation schemes for conservation‐related displacement of people. Resultados Ecológicos y Sociales de un Área Protegida Nueva en Tanzania

Catalytic enantioselective diversity-oriented synthesis of a small library of polyhydroxylated pyrans inspired from thiomarinol antibiotics - Raed M. Al-Zoubi; Dennis G. Hall (Molecular Diversity, 2014)

Cu(I)Cl-promoted synthesis of novel N-alkylated isatin analogs with an extension toward isatin-4-aminoquinoline conjugates: in vitro analysis against Trichomonas vaginalis - Nisha; Richard Tran; Donald Yang; Dominique Hall; Melissa J. Hopper; Lisa A. Wrischnik; Kirkwood M. Land; Vipan Kumar (Medicinal Chemistry Research, 2014)

Seaweed chemical diversity: an additional and efficient tool for coastal evaluation - Cintia D. L. Martins; Cintia Lhullier; Fernanda Ramlov; José Carlos Simonassi; Lidiane P. Gouvea; Mauricio Noernberg; Marcelo Maraschin; Pio Colepicolo; Jason M. Hall-Spencer; Paulo A. Horta (Journal of Applied Phycology, 2014)

Reach and Grasp reconfigurations reveal that proprioception assists reaching and hapsis assists grasping in peripheral vision - Lauren A. Hall; Jenni M. Karl; Brittany L. Thomas; Ian Q. Whishaw (Experimental Brain Research, 2014)

Prior infections are associated with increased mortality from subsequent blood-stream infections among patients with hematological malignancies - J. A. Greenberg; M. Z. David; D. L. Pitrak; J. B. Hall; J. P. Kress (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Optimizing nitrogen use efficiency in wheat and potatoes: interactions between genotypes and agronomic practices - Eleanor Y. Swain; Leonidas Rempelos; Caroline H. Orr; Gavin Hall; Rachel Chapman; Mftah Almadni; Elizabeth A. Stockdale; Jonathan Kidd; Carlo Leifert; Julia M. Cooper (Euphytica, 2014)

Establishment and Short-term Productivity of Annual and Perennial Bioenergy Crops Across a Landscape Gradient - Danielle M. Wilson; Emily A. Heaton; Lisa A. Schulte; Theodore P. Gunther; Monika E. Shea; Richard B. Hall; William Landon Headlee; Kenneth J. Moore; Nicholas N. Boersma (BioEnergy Research, 2014)

Root lodging tolerance in Helianthus annuus (L.): associations with morphological and mechanical attributes of roots - M. E. Manzur; A. J. Hall; C. A. Chimenti (Plant and Soil, 2014)

Shrubs as ecosystem engineers across an environmental gradient: effects on species richness and exotic plant invasion - Andrew R. Kleinhesselink; Susan M. Magnoli; J. Hall Cushman (Oecologia, 2014)

Synthesis and preliminary in vitro activity of mono- and bis-1H-1,2,3-triazole-tethered β-lactam–isatin conjugates against the human protozoal pathogen Trichomonas vaginalis - Raghu Raj; Vaishali Sharma; Melissa J. Hopper; Neal Patel; Dominique Hall; Lisa A. Wrischnik; Kirkwood M. Land; Vipan Kumar (Medicinal Chemistry Research, 2014)

Phenolic Acid Sorption to Biochars from Mixtures of Feedstock Materials - K. E. Hall; M. J. Calderon; K. A. Spokas; L. Cox; W. C. Koskinen; J. Novak; K. Cantrell (Water, Air, & Soil Pollution, 2014)

Environmental Factors Affecting Germination and Seedling Survival of Carolina Willow (Salix Caroliniana) - Luz M. Castro-Morales; Pedro F. Quintana-Ascencio; John E. Fauth; Kimberli J. Ponzio; Dianne L. Hall (Wetlands, 2014)

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Effects of ocean acidification on sponge communities - Claire Goodwin; Riccardo Rodolfo‐Metalpa; Bernard Picton; Jason M. Hall‐Spencer (Marine Ecology, 2014)
The effects of ocean acidification on lower invertebrates such as sponges may be pronounced because of their low capacity for acid–base regulation. However, so far, most studies have focused on calcifiers. We present the first study of the effects of ocean acidification on the P orifera. Sponge species composition and cover along pH gradients at CO 2 vents off I schia ( T yrrhenian S ea, I taly) was measured at sites with normal p H (8.1–8.2), lowered p H (mean 7.8–7.9, min 7.4–7.5) and extremely low p H (6.6). There was a strong correlation between p H and both sponge cover and species composition. C rambe crambe was the only species present in any abundance in the areas with mean p H 6.6, seven species were present at mean p H 7.8–7.9 and four species ( P horbas tenacior , P etrosia ficiformis , C hondrilla nucula and H emimycale columella ) were restricted to sites with normal p H . Sponge percentage cover decreased significantly from normal to acidified sites. No significant effect of increasing CO 2 levels and decreasing p H was found on spicule form in C rambe crambe . This study indicates that increasing CO 2 concentrations will likely affect sponge community composition as some demosponge species appear to be more vulnerable than others. Further research into the mechanisms by which acidification affects sponges would be useful in predicting likely effects on sessile marine communities.

On the spread of changes in marine low cloud cover in climate model simulations of the 21st century - Xin Qu; Alex Hall; Stephen A. Klein; Peter M. Caldwell (Climate Dynamics, 2014)

Sea urchin response to rising pCO2 shows ocean acidification may fundamentally alter the chemistry of marine skeletons - L. BRAY; M.A. PANCUCCI-PAPADOPOULOU; J. M. HALL-SPENCER (Mediterranean Marine Science, 2014)
Ocean acidification caused by an increase in pCO2 is expected to drastically affect marine ecosystem composition, yet there is much uncertainty about the mechanisms through which ecosystems may be affected. Here we studied sea urchins that are common and important grazers in the Mediterranean (Paracentrotus lividus and Arbacia lixula). Our study included a natural CO2 seep plus reference sites in the Aegean Sea off Greece. The distribution of A. lixula was unaffected by the low pH environment, whereas densities of P. lividus were much reduced. There was skeletal degradation in both species living in acidified waters compared to reference sites and remarkable increases in skeletal manganese levels (P. lividus had a 541% increase, A. lixula a 243% increase), presumably due to changes in mineral crystalline structure. Levels of strontium and zinc were also altered. It is not yet known whether such dramatic changes in skeletal chemistry will affect coastal systems but our study reveals a mechanism that may alter inter-species interactions.

Differential trends in mercury concentrations in double-crested cormorant populations of the Canadian Prairies - Britt D. Hall; Jennifer L. Doucette; Lara M. Bates; Aleksandra Bugajski; Som Niyogi; Christopher M. Somers (Ecotoxicology, 2014)

Spatial patterns in wet and dry deposition of atmospheric mercury and trace elements in central Illinois, USA - Mary M. Lynam; J. Timothy Dvonch; Naima L. Hall; Masako Morishita; James A. Barres (Environmental Science and Pollution Research, 2014)

The ventral pallidum and orbitofrontal cortex support food pleasantness inferences - W. Kyle Simmons; Kristina M. Rapuano; John E. Ingeholm; Jason Avery; Seth Kallman; Kevin D. Hall; Alex Martin (Brain Structure and Function, 2014)

Habitat structure and ecological drivers of disease - Rachel M. Penczykowski; Spencer R. Hall; David J. Civitello; Meghan A. Duffy (Limnology and Oceanography, 2014)
Habitat can influence disease directly, through effects on hosts and parasites, or indirectly, through effects on ecological drivers of disease. We illustrated direct and indirect connections between habitat and outbreaks using a case study in the plankton. We sampled yeast epidemics in 18 populations of the lake zooplankter Daphnia dentifera . Lake size drove variation in two types of habitat structure, size of predation refuges and strength of stratification. Those habitat factors, in turn, indirectly linked to epidemics through two pathways involving nonhost species. In the first pathway, larger lakes had larger hypolimnetic refuges from vertebrate predation and greater densities of Daphnia pulicaria , a completely resistant species that can reduce disease risk for D. dentifera hosts by removing parasite spores from the environment. In lakes with more D. pulicaria , epidemics started later in autumn and remained smaller. In the second pathway, smaller lakes had shallower penetration of light, which correlated with stronger thermal stratification and higher densities of an invertebrate predator ( Chaoborus ) that spreads disease by releasing spores from infected hosts. Lakes with weaker stratification had fewer of these predators and smaller epidemics. In the second pathway, deeper light penetration may also decrease disease by imposing direct mortality on spores. Thus, this case study shows how habitat structure could influence epidemics through direct and indirect effects on the host—parasite system. Understanding these multiple mechanisms can enhance prediction of disease outbreaks as habitat modification continues in lakes and other ecosystems worldwide.

Clinical signs of barotrauma in golden perch, M acquaria ambigua ( R ichardson), and associated effects on post‐release mortality and health - K C Hall; M K Broadhurst; P A Butcher (Journal of Fish Diseases, 2014)
This study assessed the effects of different retrieval depths (2, 10 or 20 m), surface intervals (none or 15 min) and release methods (untreated, vented or recompressed) on the incidence of external and internal clinical signs of barotrauma ( ECSB and ICSB ) and post‐release mortality in golden perch, Macquaria ambigua (Richardson). Fish were assessed for ECSB before and after surface intervals and either monitored for mortality over 3 days in two deep cages or killed for internal examination. When all fish were left untreated, short‐term mortality increased with retrieval depth from 0% and 4.2% among 2 and 10‐m fish, respectively, to 19.2% among 20‐m fish; while surface interval only affected the incidence of two ECSB (excess buoyancy and a prolapsed cloaca). Mortality was also greater among 20‐m fish that were subjected to a 15‐min surface interval and left untreated (22.2%) or vented (22.2%) than those that were recompressed (5.6%). Of the ECSB , only exophthalmia was associated with increased mortality, with half of the affected fish dying. However, many fish retrieved from 10 and 20 m also sustained numerous ICSB , including compressed gonads or vital organs and ruptured or collapsed, haemorrhaging swimbladders that remained deflated for up to 3 days after release.

Responses to invasion and invader removal differ between native and exotic plant groups in a coastal dune - Susan M. Magnoli; Andrew R. Kleinhesselink; J. Hall Cushman (Oecologia, 2013)

Effects of Feeding Selenium-Enriched Alfalfa Hay on Immunity and Health of Weaned Beef Calves - Jean A. Hall; Gerd Bobe; William R. Vorachek; Hugejiletu; M. Elena Gorman; Wayne D. Mosher; Gene J. Pirelli (Biological Trace Element Research, 2013)

Evaluation of the Oxoid Brilliance™ CRE Agar for the detection of carbapenemase-producing Enterobacteriaceae - J. Cohen Stuart; G. Voets; W. Rottier; S. Voskuil; J. Scharringa; K. Dijk; A. C. Fluit; M. Leverstein-Van Hall (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Detailed paleogeographic evolution of the Bass Basin: Late Cretaceous to present - D. Briguglio; J. Kowalczyk; J. D. Stilwell; M. Hall; A. Coffa (Australian Journal of Earth Sciences, 2013)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Meeting the food and nutrition needs of the poor: the role of fish and the opportunities and challenges emerging from the rise of aquaculture a - M. C. M. Beveridge; S. H. Thilsted; M. J. Phillips; M. Metian; M. Troell; S. J. Hall (Journal of Fish Biology, 2013)
People who are food and nutrition insecure largely reside in Asia and Sub‐Saharan Africa and for many, fish represents a rich source of protein, micronutrients and essential fatty acids. The contribution of fish to household food and nutrition security depends upon availability, access and cultural and personal preferences. Access is largely determined by location, seasonality and price but at the individual level it also depends upon a person's physiological and health status and how fish is prepared, cooked and shared among household members. The sustained and rapid expansion of aquaculture over the past 30 years has resulted in >40% of all fish now consumed being derived from farming. While aquaculture produce increasingly features in the diets of many Asians, it is much less apparent among those living in Sub‐Saharan Africa. Here, per capita fish consumption has grown little and despite the apparently strong markets and adequate biophysical conditions, aquaculture has yet to develop. The contribution of aquaculture to food and nutrition security is not only just an issue of where aquaculture occurs but also of what is being produced and how and whether the produce is as accessible as that from capture fisheries. The range of fish species produced by an increasingly globalized aquaculture industry differs from that derived from capture fisheries. Farmed fishes are also different in terms of their nutrient content, a result of the species being grown and of rearing methods. Farmed fish price affects access by poor consumers while the size at which fish is harvested influences both access and use. This paper explores these issues with particular reference to Asia and Africa and the technical and policy innovations needed to ensure that fish farming is able to fulfil its potential to meet the global population's food and nutrition needs.

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Causes and methods to estimate cryptic sources of fishing mortality a - E. Gilman; P. Suuronen; M. Hall; S. Kennelly (Journal of Fish Biology, 2013)
Cryptic, not readily detectable, components of fishing mortality are not routinely accounted for in fisheries management because of a lack of adequate data, and for some components, a lack of accurate estimation methods. Cryptic fishing mortalities can cause adverse ecological effects, are a source of wastage, reduce the sustainability of fishery resources and, when unaccounted for, can cause errors in stock assessments and population models. Sources of cryptic fishing mortality are (1) pre‐catch losses, where catch dies from the fishing operation but is not brought onboard when the gear is retrieved, (2) ghost‐fishing mortality by fishing gear that was abandoned, lost or discarded, (3) post‐release mortality of catch that is retrieved and then released alive but later dies as a result of stress and injury sustained from the fishing interaction, (4) collateral mortalities indirectly caused by various ecological effects of fishing and (5) losses due to synergistic effects of multiple interacting sources of stress and injury from fishing operations, or from cumulative stress and injury caused by repeated sub‐lethal interactions with fishing operations. To fill a gap in international guidance on best practices, causes and methods for estimating each component of cryptic fishing mortality are described, and considerations for their effective application are identified. Research priorities to fill gaps in understanding the causes and estimating cryptic mortality are highlighted.

Review of the NURE Assessment of the U.S. Gulf Coast Uranium Province - Susan M. Hall (Natural Resources Research, 2013)
Historic exploration and development were used to evaluate the reliability of domestic uranium reserves and potential resources estimated by the U.S. Department of Energy national uranium resource evaluation (NURE) program in the U.S. Gulf Coast Uranium Province. NURE estimated 87 million pounds of reserves in the $30/lb U 3 O 8 cost category in the Coast Plain uranium resource region, most in the Gulf Coast Uranium Province. Since NURE, 40 million pounds of reserves have been mined, and 38 million pounds are estimated to remain in place as of 2012, accounting for all but 9 million pounds of U 3 O 8 in the reserve or production categories in the NURE estimate. Considering the complexities and uncertainties of the analysis, this study indicates that the NURE reserve estimates for the province were accurate. An unconditional potential resource of 1.4 billion pounds of U 3 O 8 , 600 million pounds of U 3 O 8 in the forward cost category of $30/lb U 3 O 8 (1980 prices), was estimated in 106 favorable areas by the NURE program in the province. Removing potential resources from the non-productive Houston embayment, and those reserves estimated below historic and current mining depths reduces the unconditional potential resource 33% to about 930 million pounds of U 3 O 8 , and that in the $30/lb cost category 34% to 399 million pounds of U 3 O 8 . Based on production records and reserve estimates tabulated for the region, most of the production since 1980 is likely from the reserves identified by NURE. The potential resource predicted by NURE has not been developed, likely due to a variety of factors related to the low uranium prices that have prevailed since 1980.

Increased competition does not lead to increased phylogenetic overdispersion in a native grassland - Jonathan A. Bennett; Eric G. Lamb; Jocelyn C. Hall; Warren M. Cardinal‐McTeague; James F. Cahill (Ecology Letters, 2013)
That competition is stronger among closely related species and leads to phylogenetic overdispersion is a common assumption in community ecology. However, tests of this assumption are rare and field‐based experiments lacking. We tested the relationship between competition, the degree of relatedness, and overdispersion among plants experimentally and using a field survey in a native grassland. Relatedness did not affect competition, nor was competition associated with phylogenetic overdispersion. Further, there was only weak evidence for increased overdispersion at spatial scales where plants are likely to compete. These results challenge traditional theory, but are consistent with recent theories regarding the mechanisms of plant competition and its potential effect on phylogenetic structure. We suggest that specific conditions related to the form of competition and trait conservatism must be met for competition to cause phylogenetic overdispersion. Consequently, overdispersion as a result of competition is likely to be rare in natural communities.

Towards improved socio-economic assessments of ocean acidification’s impacts - Nathalie Hilmi; Denis Allemand; Sam Dupont; Alain Safa; Gunnar Haraldsson; Paulo A. L. D. Nunes; Chris Moore; Caroline Hattam; Stéphanie Reynaud; Jason M. Hall-Spencer; Maoz Fine; Carol Turley; et al. (Marine Biology, 2013)

Responses of marine benthic microalgae to elevated CO2 - V. R. Johnson; C. Brownlee; R. E. M. Rickaby; M. Graziano; M. Milazzo; J. M. Hall-Spencer (Marine Biology, 2013)

Differences in the antibiotic susceptibility of human Escherichia coli with poultry-associated and non-poultry-associated extended-spectrum beta-lactamases - T. N. Platteel; M. A. Leverstein-Van Hall; J. W. Cohen Stuart; G. M. Voets; M. P. Munckhof; J. Scharringa; N. Sande; A. C. Fluit; M. J. M. Bonten (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Molecular markers as a complementary tool in risk assessments: quantifying interspecific gene flow from triticale to spring wheat and durum wheat - Vanessa B. Kavanagh; Melissa J. Hills; Aakash Goyal; Harpinder S. Randhawa; A. Keith Topinka; Francois Eudes; Linda M. Hall (Transgenic Research, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

Future climate of the Caribbean from a super-high-resolution atmospheric general circulation model - Trevor C. Hall; Andrea M. Sealy; Tannecia S. Stephenson; Shoji Kusunoki; Michael A. Taylor; A. Anthony Chen; Akio Kitoh (Theoretical and Applied Climatology, 2013)

Whole exome sequencing in dominant cataract identifies a new causative factor, CRYBA2, and a variety of novel alleles in known genes - Linda M. Reis; Rebecca C. Tyler; Sanaa Muheisen; Victor Raggio; Leonardo Salviati; Dennis P. Han; Deborah Costakos; Hagith Yonath; Sarah Hall; Patricia Power; Elena V. Semina (Human Genetics, 2013)

Cerebellar vermis volume in major depressive disorder - Kaan Yucel; Anthony Nazarov; Valerie H. Taylor; Kathryn Macdonald; Geoffrey B. Hall; Glenda M. MacQueen (Brain Structure and Function, 2013)

Selenium Supplementation Alters Gene Expression Profiles Associated with Innate Immunity in Whole-Blood Neutrophils of Sheep - Hugejiletu Hugejiletu; Gerd Bobe; William R. Vorachek; M. Elena Gorman; Wayne D. Mosher; Gene J. Pirelli; Jean A. Hall (Biological Trace Element Research, 2013)

Effects of multiple stressors on lakes in south-central Ontario: 15 years of change in lakewater chemistry and sedimentary diatom assemblages - Kristopher R. Hadley; Andrew M. Paterson; Roland I. Hall; John P. Smol (Aquatic Sciences, 2013)

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Global environmental changes: setting priorities for Latin American coastal habitats - Alexander Turra; Aldo Cróquer; Alvar Carranza; Andrés Mansilla; Arsenio J. Areces; Camilo Werlinger; Carlos Martínez‐Bayón; Cristina Aparecida Gomes Nassar; Estela Plastino; Evangelina Schwindt; Fabrizio Scarabino; Fungyi Chow; et al. (Global Change Biology, 2013)
As the effects of the Global Climate Changes on the costal regions of Central and South Americas advance, there is proportionally little research being made to understand such impacts. This commentary puts forward a series of propositions of strategies to improve performance of Central and South American science and policy making in order to cope with the future impacts of the Global Climate Changes in their coastal habitats.

Water-use efficiency and whole-plant performance of nine tropical tree species at two sites with contrasting water availability in Panama - D. Craven; J. S. Hall; M. S. Ashton; G. P. Berlyn (Trees, 2013)

Macroparasites at peripheral sites of infection are major and dynamic modifiers of systemic antimicrobial pattern recognition responses - I. M. Friberg; S. Little; C. Ralli; A. Lowe; A. Hall; J. A. Jackson; J. E. Bradley (Molecular Ecology, 2013)
Immune defences and the maintenance of immunological homeostasis in the face of pathogenic and commensal microbial exposures are channelled by innate antimicrobial pattern recognition receptors ( PRR s) such as toll‐like receptors ( TLR s). Whilst PRR ‐mediated response programmes are the result of long‐term host‐pathogen or host–commensal co‐evolutionary dynamics involving microbes, an additional possibility is that macroparasitic co‐infections may be a significant modifier of such interactions. We demonstrate experimentally that macroparasites (the model gastrointestinal nematode, H eligmosomoides ) at peripheral sites of infection cause substantial alteration of the expression and function of TLR s at a systemic level (in cultured splenocytes), predominantly up‐regulating TLR 2, TLR 4 and TLR 9‐mediated cytokine responses at times of high standing worm burdens. We consistently observed such effects in BALB /c and C57 BL /6 mice under single‐pulse and trickle exposures to H eligmosomoides larvae and in SWR and CBA mice under single‐pulse exposures. A complementary long‐term survey of TLR 2‐mediated tumour necrosis factor‐alpha responses in wild wood mice ( A podemus sylvaticus ) was consistent with substantial effects of macroparasites under some environmental conditions. A general pattern, though, was for the associations of macroparasites with TLR function to be temporally dynamic and context‐dependent: varying with different conditions of infection exposure in the field and laboratory and with host genetic strain in the laboratory. These results are compelling evidence that macroparasites are a major and dynamic modifier of systemic innate antimicrobial responsiveness in naturally occurring mammals and thus likely to be an important influence on the interaction between microbial exposures and the immune system.

Bird and Plant Diversity in Tropical Landscape Mosaics in East Usambaras, Tanzania - Heini Vihemäki; Jaclyn M. Hall; Charles Leonard; Moses Mwangoka; Victor Mkongewa (Small-scale Forestry, 2013)

Spatial variation of phytoplankton assemblages and biomass in the New Zealand sector of the Southern Ocean during the late austral summer 2008 - F. Hoe Chang; Michael J. M. Williams; Jill N. Schwarz; Julie A. Hall; Elizabeth W. Maas; Rob Stewart (Polar Biology, 2013)

Different responses of selected hormones to three types of exercise in young men - Keith A. Stokes; Kate L. Gilbert; George M. Hall; Robert C. Andrews; Dylan Thompson (European Journal of Applied Physiology, 2013)

Hypermorphic expression of centromeric retroelement-encoded small RNAs impairs CENP-A loading - Dawn M. Carone; Chu Zhang; Laura E. Hall; Craig Obergfell; Benjamin R. Carone; Michael J. O’Neill; Rachel J. O’Neill (Chromosome Research, 2013)

Using a Process-Based Model (3-PG) to Predict and Map Hybrid Poplar Biomass Productivity in Minnesota and Wisconsin, USA - William L. Headlee; Ronald S. Zalesny; Deahn M. Donner; Richard B. Hall (BioEnergy Research, 2013)

Predator guild does not influence orangutan alarm call rates and combinations - Adriano R. Lameira; Han de Vries; Madeleine E. Hardus; Cedric P. A. Hall; Tatang Mitra-Setia; Berry M. Spruijt; Arik Kershenbaum; Elisabeth H. M. Sterck; Maria van Noordwijk; Carel van Schaik; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Trill performance components vary with age, season, and motivation in the banded wren - S. L. Vehrencamp; J. Yantachka; M. L. Hall; S. R. de Kort (Behavioral Ecology and Sociobiology, 2013)

Potassium stimulates fungal epidemics in Daphnia by increasing host and parasite reproduction - David J. Civitello; Rachel M. Penczykowski; Jessica L. Hite; Meghan A. Duffy; Spencer R. Hall (Ecology, 2013)
As natural enemies, parasites can dramatically harm host populations, and even catalyze their decline. Thus, identifying factors that promote disease spread is paramount. Environmental factors can drive epidemics by altering traits involved in disease spread. For example, nutrients (such as nitrogen and phosphorus) can stimulate reproduction of both hosts and parasites or alter rates of disease transmission by stimulating productivity and nutrition of food resources of hosts. Here, we demonstrate nutrient–trait–epidemic connections between the greatly understudied macronutrient potassium (K) and fungal disease ( Metschnikowia bicuspidata ) in a zooplankton host ( Daphnia dentifera ). In a three‐year survey, epidemics grew larger in lakes with more potassium. In laboratory assays, potassium enrichment of low‐K lake water enhanced both host and parasite reproduction. Parameterized with these data, a model predicted that potassium addition catalyzes disease spread. We confirmed this prediction with an experiment in large mesocosms (6000 L) in a low K‐lake: potassium enrichment caused larger epidemics in replicated Daphnia populations. Consequently, the model–data combination mechanistically explained the field pattern and revealed a novel ecological role for the nutrient potassium. Furthermore, our findings highlight the need for further development of theory for nutrient limitation of epidemics. Such theory could help to explain heterogeneous eruptions of disease in space, connect these outbreaks to natural or anthropogenic enrichment of ecosystems, predict the ecological consequences of these outbreaks, and reveal novel strategies for disease management.

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values - Nicola M. Lowe; Fiona C. Dykes; Anna-Louise Skinner; Sujata Patel; Marisol Warthon-Medina; Tamás Decsi; Katalin Fekete; Olga W. Souverein; Carla Dullemeijer; Adriënne E. Cavelaars; Lluis Serra-Majem; Mariela Nissensohn; et al. (Critical Reviews in Food Science and Nutrition, 2013)

Disease-Driven Amphibian Declines Alter Ecosystem Processes in a Tropical Stream - M. R. Whiles; R. O. Hall; W. K. Dodds; P. Verburg; A. D. Huryn; C. M. Pringle; K. R. Lips; S. S. Kilham; C. Colón-Gaud; A. T. Rugenski; S. Peterson; S. Connelly (Ecosystems, 2013)

Tobacco pollen: archaeological and forensic applications - Vaughn M. Bryant; Sarah M. Kampbell; Jerome Lynn Hall (Palynology, 2012)

A comparative gradient approach as a tool for understanding and managing urban ecosystems - Christopher G. Boone; Elizabeth Cook; Sharon J. Hall; Marcia L. Nation; Nancy B. Grimm; Carol B. Raish; Deborah M. Finch; Abigail M. York (Urban Ecosystems, 2012)

Observations on the entomopathogenic fungus Hirsutella citriformis attacking adult Diaphorina citri (Hemiptera: Psyllidae) in a managed citrus grove - David G. Hall; Matthew G. Hentz; Jason M. Meyer; Alissa B. Kriss; Tim R. Gottwald; Drion G. Boucias (BioControl, 2012)

Sea anemones may thrive in a high CO 2 world - David J. Suggett; Jason M. Hall‐Spencer; Riccardo Rodolfo‐Metalpa; Toby G. Boatman; Ross Payton; D. Tye Pettay; Vivienne R. Johnson; Mark E. Warner; Tracy Lawson (Global Change Biology, 2012)
Increased seawater p CO 2 , and in turn ‘ocean acidification’ (OA), is predicted to profoundly impact marine ecosystem diversity and function this century. Much research has already focussed on calcifying reef‐forming corals (Class: Anthozoa) that appear particularly susceptible to OA via reduced net calcification. However, here we show that OA‐like conditions can simultaneously enhance the ecological success of non‐calcifying anthozoans, which not only play key ecological and biogeochemical roles in present day benthic ecosystems but also represent a model organism should calcifying anthozoans exist as less calcified (soft‐bodied) forms in future oceans. Increased growth (abundance and size) of the sea anemone ( Anemonia viridis ) population was observed along a natural CO 2 gradient at Vulcano, Italy. Both gross photosynthesis ( P G ) and respiration (R) increased with p CO 2 indicating that the increased growth was, at least in part, fuelled by bottom up (CO 2 stimulation) of metabolism. The increase of P G outweighed that of R and the genetic identity of the symbiotic microalgae ( Symbiodinium spp.) remained unchanged (type A19) suggesting proximity to the vent site relieved CO 2 limitation of the anemones' symbiotic microalgal population. Our observations of enhanced productivity with p CO 2 , which are consistent with previous reports for some calcifying corals, convey an increase in fitness that may enable non‐calcifying anthozoans to thrive in future environments, i.e. higher seawater p CO 2 . Understanding how CO 2 ‐enhanced productivity of non‐ (and less‐) calcifying anthozoans applies more widely to tropical ecosystems is a priority where such organisms can dominate benthic ecosystems, in particular following localized anthropogenic stress.

Peralkaline magma evolution and the tephra record in the Ethiopian Rift - Tyrone O. Rooney; William K. Hart; Chris M. Hall; Dereje Ayalew; Mark S. Ghiorso; Paulo Hidalgo; Gezahegn Yirgu (Contributions to Mineralogy and Petrology, 2012)

Culture as a means to contextualize policy - Damon M. Hall; Susan J. Gilbertz; Cristi C. Horton; Tarla Rai Peterson (Journal of Environmental Studies and Sciences, 2012)

Temperate and tropical brown macroalgae thrive, despite decalcification, along natural CO 2 gradients - Vivienne R. Johnson; Bayden D. Russell; Katharina E. Fabricius; Colin Brownlee; Jason M. Hall‐Spencer (Global Change Biology, 2012)
Predicting the impacts of ocean acidification on coastal ecosystems requires an understanding of the effects on macroalgae and their grazers, as these underpin the ecology of rocky shores. Whilst calcified coralline algae (Rhodophyta) appear to be especially vulnerable to ocean acidification, there is a lack of information concerning calcified brown algae (Phaeophyta), which are not obligate calcifiers but are still important producers of calcium carbonate and organic matter in shallow coastal waters. Here, we compare ecological shifts in subtidal rocky shore systems along CO 2 gradients created by volcanic seeps in the Mediterranean and Papua New Guinea, focussing on abundant macroalgae and grazing sea urchins. In both the temperate and tropical systems the abundances of grazing sea urchins declined dramatically along CO 2 gradients. Temperate and tropical species of the calcifying macroalgal genus Padina (Dictyoaceae, Phaeophyta) showed reductions in Ca CO 3 content with CO 2 enrichment. In contrast to other studies of calcified macroalgae, however, we observed an increase in the abundance of Padina spp. in acidified conditions. Reduced sea urchin grazing pressure and significant increases in photosynthetic rates may explain the unexpected success of decalcified Padina spp. at elevated levels of CO 2 . This is the first study to provide a comparison of ecological changes along CO 2 gradients between temperate and tropical rocky shores. The similarities we found in the responses of Padina spp. and sea urchin abundance at several vent systems increases confidence in predictions of the ecological impacts of ocean acidification over a large geographical range .

Central leptin replacement enhances chemorespiratory responses in leptin-deficient mice independent of changes in body weight - Mirian Bassi; Humberto Giusti; Cristiane Mota Leite; Janete A. Anselmo-Franci; Jussara M. do Carmo; Alexandre A. da Silva; John E. Hall; Eduardo Colombari; Mogens L. Glass (Pflügers Archiv - European Journal of Physiology, 2012)

Geochemical constraints on blueschist- and amphibolite-facies rocks of the Central Cordillera of Colombia: the Andean Barragán region - Andres Bustamante; Caetano Juliani; Eric J. Essene; Chris M. Hall; Thaís Hyppolito (International Geology Review, 2012)

Adding pieces to the puzzle: episodic crustal growth and a new terrane in the northeast Yilgarn Craton, Western Australia - M. J. Pawley; M. T. D. Wingate; C. L. Kirkland; S. Wyche; C. E. Hall; S. S. Romano; M. P. Doublier (Australian Journal of Earth Sciences, 2012)

Pleistocene biogeochemical record in the south‐west Pacific Ocean (images site MD97‐2114, Chatham Rise) - M. Cobianchi; V. Luciani; C. Lupi; N. Mancin; F. Lirer; N. Pelosi; I. Trattenero; M. Bordiga; I. R. Hall; M. Sprovieri (Journal of Quaternary Science, 2012)
Through a multidisciplinary approach based on novel micropaleontological and geochemical analyses, the main paleoceanographic and paleoclimate changes that have influenced the surface‐ and deep‐water circulation in the SW Pacific Ocean (Chatham Rise, eastern New Zealand) during the last million years are reconstructed. This region represents a key area for investigating the climate evolution during the Pleistocene because here the largely wind‐driven Antarctic Circumpolar Current interacts with the west Pacific Ocean circulation via the Deep Western Boundary Current, the major source of deep water for the whole Pacific Ocean. To understand coupling or decoupling events between sea surface and bottom waters, a continuous marine sedimentary succession since 1.1 Ma, recovered by the IMAGES (International Marine Past Global Change Study) cruise in the SW Pacific Ocean (Core MD97‐2114), has been investigated based on calcareous planktonic and benthic microfossil content and C and O isotope record performed on planktonic and benthic foraminiferal tests. Results show the occurrence of long‐ and short‐term patterns of climate and ocean circulation in the last million years as the result of the interplay of ice‐sheet dynamics, surface tropical versus polar water inflow, and trophic status of the surface water. Copyright © 2012 John Wiley & Sons, Ltd.

Global habitat suitability of cold‐water octocorals - Chris Yesson; Michelle L. Taylor; Derek P. Tittensor; Andrew J. Davies; John Guinotte; Amy Baco; Julie Black; Jason M. Hall‐Spencer; Alex D. Rogers (Journal of Biogeography, 2012)
Aim Three‐quarters of Octocorallia species are found in deep waters. These cold‐water octocoral colonies can form a major constituent of structurally complex habitats. The global distribution and the habitat requirements of deep‐sea octocorals are poorly understood given the expense and difficulties of sampling at depth. Habitat suitability models are useful tools to extrapolate distributions and provide an understanding of ecological requirements. Here, we present global habitat suitability models and distribution maps for seven suborders of Octocorallia: Alcyoniina, Calcaxonia, Holaxonia, Scleraxonia, Sessiliflorae, Stolonifera and Subselliflorae. Location Global. Methods We use maximum entropy modelling to predict octocoral distribution using a database of 12,508 geolocated octocoral specimens and 32 environmental grids resampled to 30 arc‐second (approximately 1 km 2 ) resolution. Additionally, a meta‐analysis determined habitat preferences and niche overlap between the different suborders of octocorals. Results Suborder Sessiliflorae had the widest potential habitat range, but all records for all suborders implied a habitat preference for continental shelves and margins, particularly the North and West Atlantic and Western Pacific Rim. Temperature, salinity, broad scale slope, productivity, oxygen and calcite saturation state were identified as important factors for determining habitat suitability. Less than 3% of octocoral records were found in waters undersaturated for calcite, but this result is affected by a shallow‐water sampling bias. Main conclusions The logistical difficulties, expense and vast areas associated with deep‐sea sampling leads to a gap in the knowledge of faunal distributions that is difficult to fill without predictive modelling. Global distribution estimates are presented, highlighting many suitable areas which have yet to be studied. We suggest that approximately 17% of oceans are suitable for at least one suborder but 3.5% may be suitable for all seven. This is the first global habitat suitability modelling study on the distribution of octocorals and forms a useful resource for researchers, managers and conservationists.

Translational Rodent Models of Korsakoff Syndrome Reveal the Critical Neuroanatomical Substrates of Memory Dysfunction and Recovery - Lisa M. Savage; Joseph M. Hall; Leticia S. Resende (Neuropsychology Review, 2012)

Angiotensin converting enzyme 2 abrogates bleomycin-induced lung injury - G. J. Rey-Parra; A. Vadivel; L. Coltan; A. Hall; F. Eaton; M. Schuster; H. Loibner; J. M. Penninger; Z. Kassiri; G. Y. Oudit; B. Thébaud (Journal of Molecular Medicine, 2012)

Evaluation of lipid-enriched Artemia on the reproductive performance of the white-striped cleaner shrimp, Lysmata amboinensis - V. Tziouveli; M. Hall; G. G. Smith (Aquaculture International, 2012)

Residential landscapes as social-ecological systems: a synthesis of multi-scalar interactions between people and their home environment - Elizabeth M. Cook; Sharon J. Hall; Kelli L. Larson (Urban Ecosystems, 2012)

Developing biomonitoring protocols for shallow Arctic lakes using diatoms and artificial substrate samplers - Lauren A. MacDonald; Ann M. Balasubramaniam; Roland I. Hall; Brent B. Wolfe; Jon N. Sweetman (Hydrobiologia, 2012)

Resilience of inshore, juvenile snapper Pagrus auratus to angling and release - M. K. Broadhurst; P. A. Butcher; K. C. Hall; B. R. Cullis; S. P. McGrath (Journal of Fish Biology, 2012)
This study assessed the mortality of 157 snapper Pagrus auratus (9–29 cm, total length, L T ) after being conventionally angled and then released into cages (along with 48 controls) for 4 days off south‐eastern Australia. Fatalities were restricted to 12 angled fish (7·6%) and mostly attributed to the ingestion of hooks and especially their subsequent removal, which caused substantial blood loss and immediate death. Hook ingestion was significantly biased towards smaller fish ( L T ) and attributed to a lower chance of anglers initially detecting these individuals on the line (allowing them to consume more of the baits). While mortalities might be reduced in future via (1) choosing terminal rigs that promote mouth hooking and (2) cutting the line on any‐hook ingested fish, the results nevertheless validate releasing unwanted angled inshore juvenile P. auratus as a means for managing their exploitation.

Population genetic diversity and structure of two rare vernal pool grasses in central California - Sarah P. Gordon; Christina M. Sloop; Heather G. Davis; J. Hall Cushman (Conservation Genetics, 2012)

Post‐release mortality of angled golden perch Macquaria ambigua and Murray cod Maccullochella peelii - K. C. HALL; M. K. BROADHURST; P. A. BUTCHER (Fisheries Management and Ecology, 2012)
Short‐term (≤4 days) post‐release mortalities of two large, culturally and ecologically important Australian freshwater teleosts golden perch Macquaria ambigua (Richardson) and Murray cod Maccullochella peelii (Mitchell) were investigated. There was no angler‐induced mortality among golden perch that were immediately released in winter and spring, but 24% of this species and 15% of Murray cod died after delayed release in summer. Significant predictors of mortality were limited to times caught and total length for golden perch, and restraint methods and recovery times for Murray cod, but other parameters were also implicated as cumulative influences. The estimated mortalities may be sufficient to produce population‐level impacts for these two long‐lived species but could be considerably reduced through revisions of tournament regulations.

Deep Bed Filtration Modelling of Formation Damage Due to Particulate Invasion from Drilling Fluids - Edo S. Boek; Christopher Hall; Philippe M. J. Tardy (Transport in Porous Media, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Heterogeneous Rates of Molecular Evolution Among Cryptic Species of the Ciliate Morphospecies Chilodonella uncinata - Laura A. Katz; Jennifer DeBerardinis; Meaghan S. Hall; Alexandra M. Kovner; Micah Dunthorn; Spencer V. Muse (Journal of Molecular Evolution, 2011)

Wind forcing of salinity anomalies in the Denmark Strait overflow - S. Hall; S. R. Dye; K. J. Heywood; M. R. Wadley (Ocean Science, 2011)
The overflow of dense water from the Nordic Seas to the North Atlantic through Denmark Strait is an important part of the global thermohaline circulation. The salinity of the overflow plume has been measured by an array of current meters across the continental slope off the coast of Angmagssalik, southeast Greenland since September 1998. During 2004 the salinity of the overflow plume changed dramatically; the entire width of the array (70 km) freshened between January 2004 and July 2004, with a significant negative salinity anomaly of about 0.06 in May. The event in May represents a fresh anomaly of over 3 standard deviations from the mean since recording began in 1998. The OCCAM 1/12° Ocean General Circulation Model not only reproduces the 2004 freshening event (r=0.96, p

Tropical influence on boreal summer mid-latitude stationary waves - Hervé Douville; S. Bielli; C. Cassou; M. Déqué; N. M. J. Hall; S. Tyteca; A. Voldoire (Climate Dynamics, 2011)

Effects of barotrauma and mitigation methods on released Australian bass Macquaria novemaculeata - J. P. Roach; K. C. Hall; M. K. Broadhurst (Journal of Fish Biology, 2011)
The effects of barotrauma on the short‐term mortality and physical condition of Australian bass Macquaria novemaculeata were investigated after being: (1) conventionally angled and released during two tournaments in deep impoundments and (2) released untreated or subjected to venting or recompression during a manipulative experiment. All fish were released into two 20 m deep bathy‐cages and monitored for 3 days. Of 238 M. novemaculeata angled during the tournaments, 43 (18·1%) had clinical signs of barotrauma or were vented and five of these later died (11·6% mortality). Catch histories varied significantly between both barotrauma and non‐barotrauma fish and tournaments, but only hook ingestion significantly influenced mortality ( P M. novemaculeata suffering barotrauma should be immediately released with no treatment. Fish that are unable to resubmerge should be recompressed, while those held in live wells and released in shallow water should be vented.

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

The Tyndall coastal simulator - Mustafa Mokrech; Susan Hanson; Robert J. Nicholls; Judith Wolf; Mike Walkden; Corentin M. Fontaine; Sophie Nicholson-Cole; Simon R. Jude; James Leake; Peter Stansby; Andrew R. Watkinson; Mark D. A. Rounsevell; et al. (Journal of Coastal Conservation, 2011)

Physiological consequences of military high-speed boat transits - Stephen D. Myers; Trevor D. Dobbins; Stuart King; Benjamin Hall; Ruth M. Ayling; Sharon R. Holmes; Tom Gunston; Rosemary Dyson (European Journal of Applied Physiology, 2011)

Modelling tide–surge interaction effects using finite volume and finite element models of the Irish Sea - Jiuxing Xing; Eric Jones; Alan M. Davies; Philip Hall (Ocean Dynamics, 2011)

Comparison of Agroforests and Protected Forests in the East Usambara Mountains, Tanzania - Jaclyn M. Hall; Thomas W. Gillespie; Moses Mwangoka (Environmental Management, 2011)

The stimulating effects of ethanol on ventral tegmental area dopamine neurons projecting to the ventral pallidum and medial prefrontal cortex in female Wistar rats: regional difference and involvement of serotonin-3 receptors - Zheng-Ming Ding; Scott M. Oster; Sarah R. Hall; Eric A. Engleman; Sheketha R. Hauser; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2011)

The relationship between land cover and the urban heat island in northeastern Puerto Rico - David J. Murphy; Myrna H. Hall; Charles A. S. Hall; Gordon M. Heisler; Stephen V. Stehman; Carlos Anselmi‐Molina (International Journal of Climatology, 2011)
Throughout the tropics, population movements, urban growth, and industrialization are causing conditions that result in elevated temperatures within urban areas when compared with that in surrounding rural areas, a phenomenon known as the urban heat island (UHI). One such example is the city of San Juan, Puerto Rico. Our objective in this study was to quantify the UHI created by the San Juan Metropolitan Area over space and time using temperature data collected by mobile‐ and fixed‐station measurements. We also used the fixed‐station measurements to examine the relationship between average temperature at a given location and the density of remotely sensed vegetation located upwind. We then regressed temperatures against regional upwind land cover to predict future temperature with projected urbanization. Our data from the fixed stations show that the average nighttime UHI calculated between the urban reference and rural stations (Δ T CBD–rural ) was 2.15 °C during the usually wet season and 1.78 °C during the usually dry season. The maximum UHI value for San Juan was calculated as 4.7 °C between the urban and forest sites and 3.9 °C between the urban and an open, rural site. Comparisons of diurnal temperature trends at urban, grassland, and forested sites indicate that canopy cover reduced daytime warming. Temperature was predicted best ( r 2 = 0.94) by vegetation in upwind easterly directions, especially that within 180 m of the sensor. Results from the mobile measurements show that the UHI has reached the base of the Luquillo Mountains. Predictions of future development and temperatures suggest that if the present pattern of development continues, over 140 km 2 of land that showed no signs of UHI in 2000 will have an average annual UHI between + 0.4 and + 1.55 °C by 2050. Furthermore, more than 130 km 2 of land area with a current UHI between + 0.4 and + 1.4 °C in 2000 will have an average UHI greater than + 1.55 °C by 2050. Copyright © 2010 Royal Meteorological Society

Characterisation of the Poly-(Vinylpyrrolidone)-Poly-(Vinylacetate-Co-Crotonic Acid) (PVP:PVAc-CA) Interpolymer Complex Matrix Microparticles Encapsulating a Bifidobacterium lactis Bb12 Probiotic Strain - C. I. Mamvura; F. S. Moolman; L. Kalombo; A. N. Hall; M. S. Thantsha (Probiotics and Antimicrobial Proteins, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Quantity and quality: unifying food web and ecosystem perspectives on the role of resource subsidies in freshwaters - Amy M. Marcarelli; Colden V. Baxter; Madeleine M. Mineau; Robert O. Hall (Ecology, 2011)
Although the study of resource subsidies has emerged as a key topic in both ecosystem and food web ecology, the dialogue over their role has been limited by separate approaches that emphasize either subsidy quantity or quality. Considering quantity and quality together may provide a simple, but previously unexplored, framework for identifying the mechanisms that govern the importance of subsidies for recipient food webs and ecosystems. Using a literature review of >90 studies of open‐water metabolism in lakes and streams, we show that high‐flux, low‐quality subsidies can drive freshwater ecosystem dynamics. Because most of these ecosystems are net heterotrophic, allochthonous inputs must subsidize respiration. Second, using a literature review of subsidy quality and use, we demonstrate that animals select for high‐quality food resources in proportions greater than would be predicted based on food quantity, and regardless of allochthonous or autochthonous origin. This finding suggests that low‐flux, high‐quality subsidies may be selected for by animals, and in turn may disproportionately affect food web and ecosystem processes (e.g., animal production, trophic energy or organic matter flow, trophic cascades). We then synthesize and review approaches that evaluate the role of subsidies and explicitly merge ecosystem and food web perspectives by placing food web measurements in the context of ecosystem budgets, by comparing trophic and ecosystem production and fluxes, and by constructing flow food webs. These tools can and should be used to address future questions about subsidies, such as the relative importance of subsidies to different trophic levels and how subsidies may maintain or disrupt ecosystem stability and food web interactions.

Paleoredox status and thermal alteration of the lower Cambrian (Series 2) Emu Bay Shale Lagerstätte, South Australia - D. M. McKirdy; P. A. Hall; C. Nedin; G. P. Halverson†; B. H. Michaelsen; J. B. Jago; J. G. Gehling; R. J. F. Jenkins (Australian Journal of Earth Sciences, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

Water-saturated magmas in the Panama Canal region: a precursor to adakite-like magma generation? - Tyrone O. Rooney; Pastora Franceschi; Chris M. Hall (Contributions to Mineralogy and Petrology, 2011)

Atmospheric inversion strength over polar oceans in winter regulated by sea ice - Tamlin M. Pavelsky; Julien Boé; Alex Hall; Eric J. Fetzer (Climate Dynamics, 2011)

The analysis of immunological profiles in wild animals: a case study on immunodynamics in the field vole, Microtus agrestis - JOSEPH A. JACKSON; MICHAEL BEGON; RICHARD BIRTLES; STEVE PATERSON; IDA M. FRIBERG; AMY HALL; ANN LOWE; CATRIONA RALLI; ANDREW TURNER; MALGORZATA ZAWADZKA; JANETTE E. BRADLEY (Molecular Ecology, 2011)
A revolutionary advance in ecological immunology is that postgenomic technologies now allow molecular mediators defined in laboratory models to be measured at the mRNA level in field studies of many naturally occurring species. Here, we demonstrate the application of such an approach to generate meaningful immunological profiles for wild mammals. We sampled a natural field vole population across the year ( n = 307) and developed a battery of cellular assays in which functionally different pro‐ and anti‐inflammatory signalling responses (transcription factors and cytokines) were activated and quantified by Q‐PCR. Temporal trends were the strongest feature in the expression data, although some life history stages (mating vs. nonmating males and pregnant females) were also associated with significant variation. There was a striking set of significant negative associations between inflammatory mediators and condition indices reflecting packed erythrocyte volume and relative liver size, spleen size and splenocyte count. Grouped (principal component) measures of inflammatory and anti‐inflammatory expression were high in winter, with minima in the breeding season that occurred earlier for grouped anti‐inflammatory responses than for grouped inflammatory responses. Some individual immunological mediators also showed patterns unrelated to the breeding season or annual periodic cues. For example, interferon regulatory factor 5 (IRF5) expression declined throughout the study period, indicating a systematic trend in antimicrobial defences. Pinpointing the causes and consequences of such variation may help identify underlying environmental drivers of individual fitness and demographic fluctuation.

Late Pleistocene snowline fluctuations at Nevado Coropuna (15°S), southern Peruvian Andes - Gordon R.M. Bromley; Brenda L. Hall; Kurt M. Rademaker; Claire E. Todd; Adina E. Racovteanu (Journal of Quaternary Science, 2011)
Deposits preserved on peaks in the southern Peruvian Andes are evidence for past glacial fluctuations and, therefore, serve as a record of both the timing and magnitude of past climate change. Moraines corresponding to the last major expansion of ice on Nevado Coropuna date to 20‐25 ka, during the last glacial maximum. We reconstructed the snowline at Coropuna for this period using a combined geomorphic‐numeric approach to provide a first‐order estimate of the magnitude of late‐Pleistocene climate change. Our reconstructions show that snowline was approximately 550‐770 m lower during the last glacial maximum than during the late Holocene maximum, which ended in the 19 th century, and ∼750 m lower than today. While these values are similar to data from nearby Nevado Solimana, reconstructions from the neighbouring peak of Nevado Firura reveal a smaller snowline depression, suggesting the glacial response to climate forcing in the tropics is strongly influenced by non‐climatic factors. These data constitute some of the first directly dated palaeo‐snowline data from the arid tropics and suggest that the magnitude of the last glaciation in at least parts of the tropical Andes was similar to late‐Pleistocene events at higher latitudes. Copyright © 2011 John Wiley & Sons, Ltd.

Biology of Salpa thompsoni in waters adjacent to the Ross Sea, Southern Ocean, during austral summer 2008 - E. A. Pakhomov; J. Hall; M. J. M. Williams; B. P. V. Hunt; C. J. Stevens (Polar Biology, 2011)

Interpreting spatial language in image captions - Mark M. Hall; Philip D. Smart; Christopher B. Jones (Cognitive Processing, 2011)

Glacier fluctuations in the southern Peruvian Andes during the late‐glacial period, constrained with cosmogenic 3 He - Gordon R.M. Bromley; Brenda L. Hall; Joerg M. Schaefer; Gisela Winckler; Claire E. Todd; Kurt M. Rademaker (Journal of Quaternary Science, 2011)
The occurrence of pronounced climate reversals during the last glacial termination has long been recognised in palaeoclimate records from both hemispheres and from high to low latitudes. Accurate constraint of both the timing and magnitude of events, such as the Younger Dryas and Antarctic Cold Reversal, is vital in order to test different hypotheses for the causes and propagation of abrupt climate change. However, in contrast to higher‐latitude regions, well‐dated records from the Tropics are rare and the structure of late‐glacial tropical climate remains uncertain. As a step toward addressing this problem, we present an in situ cosmogenic 3 He surface exposure chronology from Nevado Coropuna, southern Peru, documenting a significant fluctuation of the ice margin during the late‐glacial period. Ten tightly clustered ages from a pair of moraines located halfway between the modern glacier and the Last Glacial Maximum terminus range from 11.9 to 13.9 ka and give an arithmetic mean age of 12.8 ± 0.7 ka (1 σ ). These data constitute direct evidence for a readvance, or prolonged stillstand, of glaciers in the arid Andes of southwestern Peru. Copyright © 2011 John Wiley & Sons, Ltd.

Active tectonic morphology and submarine deformation of the northern Gulf of Eilat/Aqaba from analyses of multibeam data - Gideon Tibor; Tina M. Niemi; Zvi Ben-Avraham; Abdallah Al-Zoubi; Ronnie A. Sade; John K. Hall; Gal Hartman; Emad Akawi; Abdelrahmem Abueladas; Rami Al-Ruzouq (Geo-Marine Letters, 2010)

Effects of ocean acidification on invertebrate settlement at volcanic CO2 vents - M. Cigliano; M. C. Gambi; R. Rodolfo-Metalpa; F. P. Patti; J. M. Hall-Spencer (Marine Biology, 2010)

Seamounts as refugia from ocean acidification for cold‐water stony corals - Derek P. Tittensor; Amy R. Baco; Jason M. Hall‐Spencer; James C. Orr; Alex D. Rogers (Marine Ecology, 2010)
Cold‐water stony corals create habitat for a diverse range of deep‐water species but are thought to be threatened by ocean acidification due to oceanic uptake of anthropogenic CO 2 . Knowledge of the severity of this threat is hampered by our limited understanding of the distribution and habitat requirements of these corals. Here we estimate the global acidification threat to these organisms using a global database of cold‐water stony coral records and a species distribution modelling approach. We parameterised the models using present‐day environmental data, and then replaced these data with future projections of ocean chemistry from the year 2099. We found suitable coral habitat to be very heterogeneously distributed, being concentrated in the northern North Atlantic and around New Zealand. Projected changes in ocean chemistry induced a pronounced reduction in habitat suitability in the North Atlantic, and a low‐to‐moderate impact elsewhere under both the IPCC IS92a and S650 scenarios. Seamount summits are impacted by these changes, but consistently provide more suitable habitat than the surrounding seafloor, with around 98% of seamount summits having higher suitability in both future scenarios; this is because they lie in shallower waters with a higher aragonite saturation state. These results suggest that anthropogenic‐induced changes in ocean chemistry are likely to severely impact cold‐water stony coral habitat in the deep‐sea of the North Atlantic, and that impacts will be less severe elsewhere. We predict that coral communities on the summits and upper slopes of seamounts will be less susceptible to ocean acidification during this century than those on the surrounding seafloor, and thus that seamounts may serve as temporary refugia.

Effects of ocean acidification and high temperatures on the bryozoan Myriapora truncata at natural CO 2 vents - Riccardo Rodolfo‐Metalpa; Chiara Lombardi; Silvia Cocito; Jason M. Hall‐Spencer; Maria Cristina Gambi (Marine Ecology, 2010)
There are serious concerns that ocean acidification will combine with the effects of global warming to cause major shifts in marine ecosystems, but there is a lack of field data on the combined ecological effects of these changes due to the difficulty of creating large‐scale, long‐term exposures to elevated CO 2 and temperature. Here we report the first coastal transplant experiment designed to investigate the effects of naturally acidified seawater on the rates of net calcification and dissolution of the branched calcitic bryozoan Myriapora truncata (Pallas, 1766). Colonies were transplanted to normal (pH 8.1), high (mean pH 7.66, minimum value 7.33) and extremely high CO 2 conditions (mean pH 7.43, minimum value 6.83) at gas vents off Ischia Island (Tyrrhenian Sea, Italy). The net calcification rates of live colonies and the dissolution rates of dead colonies were estimated by weighing after 45 days (May–June 2008) and after 128 days (July–October) to examine the hypothesis that high CO 2 levels affect bryozoan growth and survival differently during moderate and warm water conditions. In the first observation period, seawater temperatures ranged from 19 to 24 °C; dead M. truncata colonies dissolved at high CO 2 levels (pH 7.66), whereas live specimens maintained the same net calcification rate as those growing at normal pH. In extremely high CO 2 conditions (mean pH 7.43), the live bryozoans calcified significantly less than those at normal pH. Therefore, established colonies of M. truncata seem well able to withstand the levels of ocean acidification predicted in the next 200 years, possibly because the soft tissues protect the skeleton from an external decrease in pH. However, during the second period of observation a prolonged period of high seawater temperatures (25–28 °C) halted calcification both in controls and at high CO 2 , and all transplants died when high temperatures were combined with extremely high CO 2 levels. Clearly, attempts to predict the future response of organisms to ocean acidification need to consider the effects of concurrent changes such as the Mediterranean trend for increased summer temperatures in surface waters. Although M. truncata was resilient to short‐term exposure to high levels of ocean acidification at normal temperatures, our field transplants showed that its ability to calcify at higher temperatures was compromised, adding it to the growing list of species now potentially threatened by global warming.

Phosphorus-mediated changes in life history traits of the invasive New Zealand mudsnail (Potamopyrgus antipodarum) - Teresa M. Tibbets; Amy C. Krist; Robert O. Hall; Leslie A. Riley (Oecologia, 2010)

Is local adaptation in Mimulus guttatus caused by trade‐offs at individual loci? - M. C. HALL; D. B. LOWRY; J. H. WILLIS (Molecular Ecology, 2010)
Local adaptation is considered to be the result of fitness trade‐offs for particular phenotypes across different habitats. However, it is unclear whether such phenotypic trade‐offs exist at the level of individual genetic loci. Local adaptation could arise from trade‐offs of alternative alleles at individual loci or by complementary sets of loci with different fitness effects of alleles in one habitat but selective neutrality in the alternative habitat. To evaluate the genome‐wide basis of local adaptation, we performed a field‐based quantitative trait locus (QTL) mapping experiment on recombinant inbred lines (RILs) created from coastal perennial and inland annual races of the yellow monkeyflower ( Mimulus guttatus ) grown reciprocally in native parental habitats. Overall, we detected 19 QTLs affecting one or more of 16 traits measured in two environments, most of small effect. We identified 15 additional QTL effects at two previously identified candidate QTLs [ DIV ERGENCE ( DIV )]. Significant QTL by environment interactions were detected at the DIV loci, which was largely attributable to genotypic differences at a single field site. We found no detectable evidence for trade‐offs for any one component of fitness, although DIV2 showed a trade‐off involving different fitness traits between sites, suggesting that local adaptation is largely controlled by non‐overlapping loci. This is surprising for an outcrosser, implying that reduced gene flow prevents the evolution of individuals adapted to multiple environments. We also determined that native genotypes were not uniformly adaptive, possibly reflecting fixed mutational load in one of the populations.

Widespread dispersal of Icelandic tephra: how does the Eyjafjöll eruption of 2010 compare to past Icelandic events? - Siwan M. Davies; Gudrun Larsen; Stefan Wastegård; Chris S. M. Turney; Valerie A. Hall; Lisa Coyle; Thor Thordarson (Journal of Quaternary Science, 2010)
The Eyjafjöll AD 2010 eruption is an extraordinary event in that it led to widespread and unprecedented disruption to air travel over Europe – a region generally considered to be free from the hazards associated with volcanic eruptions. Following the onset of the eruption, satellite imagery demonstrated the rapid transportation of ash by westerly winds over mainland Europe, eventually expanding to large swathes of the North Atlantic Ocean and the eastern seaboard of Canada. This small‐to‐intermediate size eruption and the dispersal pattern observed are not particularly unusual for Icelandic eruptions within a longer‐term perspective. Indeed, the Eyjafjöll eruption is a relatively modest eruption in comparison to some of the 20 most voluminous eruptions that have deposited cryptotephra in sedimentary archives in mainland Europe, such as the mid Younger Dryas Vedde Ash and the mid Holocene Hekla 4 tephra. The 2010 eruption, however, highlights the critical role that weather patterns play in the distribution of a relatively small amount of ash and also highlights the spatially complex dispersal trajectories of tephra in the atmosphere. Whether or not the preservation of the Eyjafjöll 2010 tephra in European proxy archives will correspond to the extensive distributions mapped in the atmosphere remains to be seen. The Eyjafjöll 2010 event highlights our increased vulnerability to natural hazards rather than the unparalleled explosivity of the event. Copyright © 2010 John Wiley & Sons, Ltd.

Administration of a Sigma Receptor Agonist Delays MCAO-Induced Neurodegeneration and White Matter Injury - Christopher C. Leonardo; Aaron A. Hall; Lisa A. Collier; Suzanne M. Green; Alison E. Willing; Keith R. Pennypacker (Translational Stroke Research, 2010)

Sprouty1 inhibits angiogenesis in association with up-regulation of p21 and p27 - Sangjin Lee; Tri M. Bui Nguyen; Dmitry Kovalenko; Neeta Adhikari; Suzanne Grindle; Sean P. Polster; Robert Friesel; Sundaram Ramakrishnan; Jennifer L. Hall (Molecular and Cellular Biochemistry, 2010)

Birth weight, breast cancer susceptibility loci, and breast cancer risk - Rulla M. Tamimi; Pagona Lagiou; Kamila Czene; Jianjun Liu; Anders Ekbom; Chung-Cheng Hsieh; Hans-Olov Adami; Dimitrios Trichopoulos; Per Hall (Cancer Causes & Control, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

Idealized tracer transport models with time-varying transport: applications to ocean boundary currents - F. Terenzi; Timothy M. Hall (Environmental Fluid Mechanics, 2010)

Poisson’s Ratio and Strain Rate Dependency of the Constitutive Behavior of Spinal Dura Mater - Cecilia Persson; Sam Evans; Rainy Marsh; Jon L. Summers; Richard M. Hall (Annals of Biomedical Engineering, 2010)

Reduction of fumarate, mesaconate and crotonate by Mfr, a novel oxygen‐regulated periplasmic reductase in Campylobacter jejuni - Edward Guccione; Andrew Hitchcock; Stephen J. Hall; Francis Mulholland; Neil Shearer; Arnoud H. M. Van Vliet; David J. Kelly (Environmental Microbiology, 2010)
Summary Methylmenaquinol : fumarate reductase (Mfr) is a newly recognized type of fumarate reductase present in some ε‐proteobacteria, where the active site subunit (MfrA) is localized in the periplasm, but for which a physiological role has not been identified. We show that the Campylobacter jejuni mfrABE operon is transcribed from a single promoter, with the mfrA gene preceded by a small open reading‐frame ( mfrX ) encoding a C. jejuni ‐specific polypeptide of unknown function. The growth characteristics and enzyme activities of mutants in the mfrA and menaquinol : fumarate reductase A ( frdA ) genes show that the cytoplasmic facing Frd enzyme is the major fumarate reductase under oxygen limitation. The Mfr enzyme is shown to be necessary for maximal rates of growth by fumarate respiration and rates of fumarate reduction in intact cells measured by both viologen assays and 1 H‐NMR were slower in an mfrA mutant. As periplasmic fumarate reduction does not require fumarate/succinate antiport, Mfr may allow more efficient adaptation to fumarate‐dependent growth. However, a further rationale for the periplasmic location of Mfr is suggested by the observation that the enzyme also reduces the fumarate analogues mesaconate and crotonate; fermentation products of anaerobes with which C. jejuni shares its gut environment, that are unable to be transported into the cell. Both MfrA and MfrB subunits were localized in the periplasm by immunoblotting and 2D‐gel electrophoresis, but an mfrE mutant accumulated unprocessed MfrA in the cytoplasm, suggesting a preassembled MfrABE holoenzyme has to be recognized by the TAT system for translocation to occur. Gene expression studies in chemostat cultures following an aerobic‐anaerobic shift showed that mfrA is highly upregulated by oxygen limitation, as would be experienced in vivo . Our results indicate that in addition to a role in fumarate respiration, Mfr allows C. jejuni to reduce analogous substrates specifically present in the host gut environment.

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Obscuring Ecosystem Function with Application of the Ecosystem Services Concept - MARKUS J. PETERSON; DAMON M. HALL; ANDREA M. FELDPAUSCH‐PARKER; TARLA RAI PETERSON (Conservation Biology, 2010)
Conservationists commonly have framed ecological concerns in economic terms to garner political support for conservation and to increase public interest in preserving global biodiversity. Beginning in the early 1980s, conservation biologists adapted neoliberal economics to reframe ecosystem functions and related biodiversity as ecosystem services to humanity. Despite the economic success of programs such as the Catskill/Delaware watershed management plan in the United States and the creation of global carbon exchanges, today's marketplace often fails to adequately protect biodiversity. We used a Marxist critique to explain one reason for this failure and to suggest a possible, if partial, response. Reframing ecosystem functions as economic services does not address the political problem of commodification. Just as it obscures the labor of human workers, commodification obscures the importance of the biota (ecosystem workers) and related abiotic factors that contribute to ecosystem functions. This erasure of work done by ecosystems impedes public understanding of biodiversity. Odum and Odum's radical suggestion to use the language of ecosystems (i.e., emergy or energy memory) to describe economies, rather than using the language of economics (i.e., services) to describe ecosystems, reverses this erasure of the ecosystem worker. Considering the current dominance of economic forces, however, implementing such solutions would require social changes similar in magnitude to those that occurred during the 1960s. Niklas Luhmann argues that such substantive, yet rapid, social change requires synergy among multiple societal function systems (i.e., economy, education, law, politics, religion, science), rather than reliance on a single social sphere, such as the economy. Explicitly presenting ecosystem services as discreet and incomplete aspects of ecosystem functions not only allows potential economic and environmental benefits associated with ecosystem services, but also enables the social and political changes required to ensure valuation of ecosystem functions and related biodiversity in ways beyond their measurement on an economic scale.

An inter-comparison of tidal solutions computed with a range of unstructured grid models of the Irish and Celtic Sea Regions - John Eric Jones; Philip Hall; Alan M. Davies (Ocean Dynamics, 2009)

Reactivation of BK polyomavirus in patients with multiple sclerosis receiving natalizumab therapy - Roisin M Lonergan; Michael J Carr; Cillian F De Gascun; Lisa F Costelloe; Allison Waters; Suzie Coughlan; Marguerite Duggan; Katie Doyle; Sinead Jordan; Michael W Hutchinson; William W Hall; Niall J Tubridy (Journal of NeuroVirology, 2009)

Characterizing dispersal patterns in a threatened seabird with limited genetic structure - LAURIE A. HALL; PER J. PALSBØLL; STEVEN R. BEISSINGER; JAMES T. HARVEY; MARTINE BÉRUBÉ; MARTIN G. RAPHAEL; S. KIM NELSON; RICHARD T. GOLIGHTLY; LAURA MCFARLANE‐TRANQUILLA; SCOTT H. NEWMAN; M. ZACHARIAH PEERY (Molecular Ecology, 2009)
Genetic assignment methods provide an appealing approach for characterizing dispersal patterns on ecological time scales, but require sufficient genetic differentiation to accurately identify migrants and a large enough sample size of migrants to, for example, compare dispersal between sexes or age classes. We demonstrate that assignment methods can be rigorously used to characterize dispersal patterns in a marbled murrelet ( Brachyramphus marmoratus ) population from central California that numbers approximately 600 individuals and is only moderately differentiated ( F ST ∼ 0.03) from larger populations to the north. We used coalescent simulations to select a significance level that resulted in a low and approximately equal expected number of type I and II errors and then used this significance level to identify a population of origin for 589 individuals genotyped at 13 microsatellite loci. The proportion of migrants in central California was greatest during winter when 83% of individuals were classified as migrants compared to lower proportions during the breeding (6%) and post‐breeding (8%) seasons. Dispersal was also biased toward young and female individuals, as is typical in birds. Migrants were rarely members of parent‐offspring pairs, suggesting that they contributed few young to the central California population. A greater number of migrants than expected under equilibrium conditions, a lack of individuals with mixed ancestry, and a small number of potential source populations (two), likely allowed us to use assignment methods to rigorously characterize dispersal patterns for a population that was larger and less differentiated than typically thought required for the identification of migrants.

Effects of angling on post‐release mortality, gonadal development and somatic condition of Australian bass Macquaria novemaculeata - K. C. Hall; M. K. Broadhurst; P. A. Butcher; S. J. Rowland (Journal of Fish Biology, 2009)
This study assessed the protracted effects of two angling treatments (mild and harsh) on the post‐release mortality, gonadal development and somatic condition of Australian bass Macquaria novemaculeata in a pond‐based experiment. Angled fish were destructively sampled (along with controls) three times: immediately before, and 1 or 4 weeks after release into cages. Compared with the other groups, harshly angled fish had similar, low immediate and short‐term mortalities (≤5%), but significant delayed mortality (25%) and fed only minimally. None of these fish ejected ingested hooks. Forty‐six per cent of captive fish (across all groups) and 20% of wild fish had non‐ripening gonads (stage I) prior to, or during, the experiment. In females with ripening ovaries (stages II or III), neither angling treatment significantly reduced standardized gonadal mass. The mean per cent of atretic oocytes increased among females in all groups, but was significantly greater in those that were harshly angled. The results demonstrated that the gonadal development of M. novemaculeata could be suppressed or impaired (by angling, handling and confinement), and that further research is warranted. In particular, the timing and severity of angling in relation to the stage of gonadal development could have important implications for the introduction of temporal restrictions to angling.

Estimating habitat selection when GPS fix success is less than 100% - Ryan M. Nielson; Bryan F. J. Manly; Lyman L. McDonald; Hall Sawyer; Trent L. McDonald (Ecology, 2009)
Inferences about habitat selection by animals derived from sequences of relocations obtained with global positioning system (GPS) collars can be influenced by GPS fix success. Environmental factors such as dense canopy cover or rugged terrain can reduce GPS fix success, making subsequent modeling problematic if fix success depends on the selected habitat. Ignoring failed fix attempts may affect estimates of model coefficients and lead to incorrect conclusions about habitat selection. Here, we present a habitat selection model that accounts for missing locations due to habitat‐induced data losses, called a resource selection function (RSF) for GPS fix success. The model's formulation is similar to adjusting estimates of probability of occupancy when detection is less than 100% in patch occupancy sampling. We demonstrate use of the model with GPS data collected from an adult female mule deer ( Odocoileus hemionus ) and discuss how to analyze data from multiple animals. In the simulations presented, our habitat selection model was generally unbiased for GPS data sets missing up to 50% of the locations.

Genetic analysis of resistance to soil-borne wheat mosaic virus derived from Aegilops tauschii - M. D. Hall; G. Brown-Guedira; A. Klatt; A. K. Fritz (Euphytica, 2009)

Characterization of Broad Spectrum Potato Virus Y Resistance in a Solanum tuberosum ssp. andigena-Derived Population and Select Breeding Clones Using Molecular Markers, Grafting, and Field Inoculations - Jonathan L. Whitworth; Richard G. Novy; Darren G. Hall; James M. Crosslin; Charles R. Brown (American Journal of Potato Research, 2009)

Integrated analysis of risks of coastal flooding and cliff erosion under scenarios of long term change - R. J. Dawson; M. E. Dickson; R. J. Nicholls; J. W. Hall; M. J. A. Walkden; P. K. Stansby; M. Mokrech; J. Richards; J. Zhou; J. Milligan; A. Jordan; S. Pearson; et al. (Climatic Change, 2009)

Short‐term mortality of Australian bass, Macquaria novemaculeata , after catch‐and‐release angling - K. C. HALL; P. A. BUTCHER; M. K. BROADHURST (Fisheries Management and Ecology, 2009)
Australian bass, Macquaria novemaculeata Steindachner, is angled in large numbers from coastal impoundments and rivers throughout south‐eastern Australia. Many are released in the belief that most survive with few negative short‐term impacts. This assumption was investigated in three experiments involving a range of conventional angling scenarios. A total of 313 Australian bass were angled and then released along with appropriate controls into either land‐based tanks or floating cages, where they were monitored for up to 5 days. No controls died. Short‐term mortalities of angled fish were low (0–6%) and attributed to the effects of bait type, hook location and fish size ( P 0.05). Specifically, fish that ingested hooks or were caught with natural baits were more likely to die than those that were mouth‐hooked or caught on lures. Mortality negatively correlated with fish size. The results supported previous assertions that Australian bass is a resilient, hardy species that should tolerate short‐term impacts associated with catch‐and‐release angling. However, other sublethal physiological impacts that could contribute towards delayed mortalities or reduced reproductive output warrant further investigation, particularly in relation to native populations in coastal rivers that form gauntlet fisheries during their annual spawning season.

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Sigma1 receptor antagonists determine the behavioral pattern of the methamphetamine-induced stereotypy in mice - J. Kitanaka; N. Kitanaka; T. Tatsuta; F. S. Hall; G. R. Uhl; K. Tanaka; N. Nishiyama; Y. Morita; M. Takemura (Psychopharmacology, 2009)

Granulocytic differentiation of HL-60 promyelocytic leukemia cells is associated with increased expression of Cul5 - Shaneen S. Baxter; Lauren A. Carlson; Alejandro M. S. Mayer; Mary L. Hall; Michael J. Fay (In Vitro Cellular & Developmental Biology - Animal, 2009)

The effect of temperature on the coupling between phosphorus and growth in lacustrine bacterioplankton communities - Edward K. Hall; Andrew R. Dzialowski; Samuel M. Stoxen; James B. Cotner (Limnology and Oceanography, 2009)
Phosphorus (P) routinely limits microbial growth in freshwater ecosystems. The growth rate hypothesis (GRH) relates growth to biomass P content mechanistically through changes in ribosomal ribonucleic acid (rRNA). Although the GRH has been shown in cultured bacteria, less well understood is how GRH relationships are affected by interactions with environmental parameters such as temperature. To address this, we evaluated the relationship between bacterial biomass P, RNA: deoxyribonucleic acid (DNA) ratio, and growth rate in 47 northern temperate lakes. Although RNA:DNA ratio was positively correlated with bacterial biomass P : carbon (C), we found no correlation between growth rate and RNA:DNA or between growth rate and biomass P : C. There was, however, a significant effect of temperature on biomass P : C. We investigated the effect of temperature more directly using filter‐separated bacterial communities from two lakes during two seasons while experimentally manipulating temperature and resources. For the summer communities, bacterial production (BP) and biomass P were positively correlated, and the slope of that relationship increased with increasing temperature. In winter communities, BP and biomass P were again positively correlated; however, the slope of that relationship decreased with increasing temperature. The slope of the relationship between BP and biomass P is a metric of nutrient use efficiency and was strongly influenced by temperature. More importantly, bacterioplankton demonstrated seasonal acclimation or adaptation to in situ temperature, suggesting that studies evaluating multiple communities in time and space fail to find a clear relationship between temperature and bacterial metabolism because bacterial communities are locally adapted to in situ temperature.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Potential for seed-mediated gene flow in agroecosystems from transgenic safflower (Carthamus tinctorius L.) intended for plant molecular farming - Marc A. McPherson; Rong-Cai Yang; Allen G. Good; Ryan L. Nielson; Linda M. Hall (Transgenic Research, 2009)

Trace Element Concentrations in Wintering Waterfowl from the Great Salt Lake, Utah - J. L. Vest; M. R. Conover; C. Perschon; J. Luft; J. O. Hall (Archives of Environmental Contamination and Toxicology, 2009)

Live imaging early immune cell ontogeny and function in zebrafish Danio rerio - C. J. Hall; M. V. Flores; K. E. Crosier; P. S. Crosier (Journal of Fish Biology, 2008)
The success of a robust vertebrate inflammatory response is in part because of the migratory potential of its haematopoietic components. Once these cells converge at an inflammatory site, they interact with each other as well as non‐immune tissues and infectious agents to help manage both the scale and the duration of any ensuing response. Exactly how these blood cells, that constitute the innate and adaptive immune systems, contribute to such immune responses remain largely unknown. Traditionally, assessing these contributions relied upon histological analysis of fixed tissue sections complemented with in vitro dynamic data. Although informative, translating results from these studies into the multicellular whole‐animal setting remain difficult. Recently, non‐invasive live imaging of the immune system in animal models is providing significant insights into how immune cells function within their intact natural environment. Although the majority of these studies have been conducted within mice, another vertebrate, the zebrafish Danio rerio is being recognized as an ideal platform for non‐invasive live imaging applications. The optical transparency, rapid development, genetic tractability and highly conserved innate and adaptive immune systems of this well‐established developmental model have been exploited in a number of recent studies evaluating the immunocompetence of fluorescently tagged blood cells. In addition, similar live imaging studies are helping to dissect the ontogeny of blood‐cell development by tracking various haematopoietic precursor cells to assess their contribution to different blood lineages. This review will examine some recent advances that have helped D. rerio emerge as a live imaging platform as well as its potential to offer valuable insights into the genetics behind diseases associated with immune cell dysfunction.

Induction of conchospore release: ecotypic variation in northeast Pacific species of Porphyra - Sandra C. Lindstrom; Jan M. Conitz; Sharon Hall; Michael S. Stekoll (Journal of Applied Phycology, 2008)

Fuzzy-logic modeling of land suitability for hybrid poplar across the Prairie Provinces of Canada - B. N. Joss; R. J. Hall; D. M. Sidders; T. J. Keddy (Environmental Monitoring and Assessment, 2008)

Six new recombinant inbred populations for the study of quantitative traits in Arabidopsis thaliana - Carmel M. O’Neill; Colin Morgan; Jane Kirby; Hendrik Tschoep; Polo Xiaoyi Deng; Mahon Brennan; Ulises Rosas; Fiona Fraser; Caroline Hall; Samantha Gill; Ian Bancroft (Theoretical and Applied Genetics, 2008)

Six new recombinant inbred populations for the study of quantitative traits in Arabidopsis thaliana - Carmel M. O’Neill; Colin Morgan; Jane Kirby; Hendrik Tschoep; Polo Xiaoyi Deng; Mahon Brennan; Ulises Rosas; Fiona Fraser; Caroline Hall; Samantha Gill; Ian Bancroft (Theoretical and Applied Genetics, 2008)

A New Test for Selection Applied to Codon Usage in Drosophila simulans and D. mauritiana - Ana Llopart; Aelén Mabillé; Jennifer R. Peters-Hall; Josep M. Comeron; Richard M. Kliman (Journal of Molecular Evolution, 2008)

Second Generation Biofuels: High-Efficiency Microalgae for Biodiesel Production - Peer M. Schenk; Skye R. Thomas-Hall; Evan Stephens; Ute C. Marx; Jan H. Mussgnug; Clemens Posten; Olaf Kruse; Ben Hankamer (BioEnergy Research, 2008)

Extent of the last ice sheet in northern Scotland tested with cosmogenic 10 Be exposure ages - William M. Phillips; Adrian M. Hall; Colin K. Ballantyne; Steven Binnie; Peter W. Kubik; Stewart Freeman (Journal of Quaternary Science, 2008)
The extent of the last British–Irish Ice Sheet (BIIS) in northern Scotland is disputed. A restricted ice sheet model holds that at the global Last Glacial Maximum (LGM; ca. 23–19 ka) the BIIS terminated on land in northern Scotland, leaving Buchan, Caithness and the Orkney Islands ice‐free. An alternative model implies that these three areas were ice‐covered at the LGM, with the BIIS extending offshore onto the adjacent shelves. We test the two models using cosmogenic 10 Be surface exposure dating of erratic boulders and glacially eroded bedrock from the three areas. Our results indicate that the last BIIS covered all of northern Scotland during the LGM, but that widespread deglaciation of Caithness and Orkney occurred prior to rapid warming at ca. 14.5 ka. Copyright © 2008 John Wiley & Sons, Ltd.

A comparison of amphetamine- and methamphetamine-induced locomotor activity in rats: evidence for qualitative differences in behavior - Darien A. Hall; Jessica J. Stanis; Hector Marquez Avila; Joshua M. Gulley (Psychopharmacology, 2007)

A three-dimensional finite-element model of wind effects upon higher harmonics of the internal tide - Philip Hall; Alan M. Davies (Ocean Dynamics, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Impaired fear recognition in regular recreational cocaine users - L. Kemmis; J. K. Hall; R. Kingston; M. J. Morgan (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Characterization of the active site of catalytically inactive forms of [NiFe] hydrogenases by density functional theory - Alejandro Pardo; Antonio L. De Lacey; Víctor M. Fernández; Yubo Fan; Michael B. Hall (JBIC Journal of Biological Inorganic Chemistry, 2007)

Rapid detection of Panton–Valentine leukocidin-positive Staphylococcus aureus by real-time PCR targeting the lukS-PV gene - U. Reischl; M. J. Tuohy; G. S. Hall; G. W. Procop; N. Lehn; H. Linde (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

The impacts of the 2004 hurricanes on hydrology, water quality, and seagrass in the Central Indian River Lagoon, Florida - Joel S. Steward; Robert W. Virnstein; Margaret A. Lasi; Lori J. Morris; Janice D. Miller; Lauren M. Hall; Wendy A. Tweedale (Estuaries and Coasts, 2006)

Glacial modification of granite tors in the Cairngorms, Scotland - A. M. Hall; W. M. Phillips (Journal of Quaternary Science, 2006)
A range of evidence indicates that many granite tors in the Cairngorms have been modified by the flow of glacier ice during the Pleistocene. Comparisons with SW England and the use of a space–time transformation across 38 tor groups in the Cairngorms allow a model to be developed for progressive glacial modification. Tors with deeply etched surfaces and no, or limited, block removal imply an absence of significant glacial modification. The removal of superstructure and blocks, locally forming boulder trains, and the progressive reduction of tors to stumps and basal slabs represent the more advanced stages of modification. Recognition of some slabs as tor stumps from which glacial erosion has removed all superstructure allows the original distribution of tors to be reconstructed for large areas of the Cairngorms. Unmodified tors require covers of non‐erosive, cold‐based ice during all of the cold stages of the Middle and Late Pleistocene. Deformation beneath cold‐based glacier ice is capable of the removal of blocks but advanced glacial modification requires former wet‐based glacier ice. The depth of glacial erosion at former tor sites remains limited largely to the partial or total elimination of the upstanding tor form. Cosmogenic nuclide exposure ages (Phillips et al. , 2006) together with data from weathering pit depths (Hall and Phillips, 2006), from the surfaces of tors and large erratic blocks require that the glacial entrainment of blocks from tors occurred in Marine Isotope Stages (MIS) 4–2, 6 and, probably, at least one earlier phase. The occurrence of glacially modified tors on or close to, the main summits of the Cairngorms requires full ice cover over the mountains during these Stages. Evidence from the Cairngorms indicates that tor morphology can be regarded as an important indicator of former ice cover in many formerly glaciated areas, particularly where other evidence of ice cover is sparse. Recognition of the glacial modification of tors is important for debates about the former existence of nunataks and refugia. Copyright © 2006 John Wiley & Sons, Ltd.

Cairo-East Bank effluent re-use study 3 — Effect of field crop irrigation with secondary treated wastewater on biological and chemical properties of soil and groundwater - Ezzat M. Abd El Lateef; Jeremy E. Hall; Peter C. Lawrence; Mohamed S. Negm (Biologia, 2006)

Sleep disruption in PTSD: A pilot study with home-based polysomnography - Anne GERMAIN; Martica HALL; M Katherine SHEAR; Eric A NOFZINGER; Daniel J BUYSSE (Sleep and Biological Rhythms, 2006)

Iron Uptake and Release by Macrophages is Sensitive to Propranolol - Andrei M. Komarov; Jonathon M. Hall; Joanna J. Chmielinska; William B. Weglicki (Molecular and Cellular Biochemistry, 2006)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Density functional study of the catalytic cycle of nickel–iron [NiFe] hydrogenases and the involvement of high-spin nickel(II) - Alejandro Pardo; Antonio L. De Lacey; Víctor M. Fernández; Hua-Jun Fan; Yubo Fan; Michael B. Hall (JBIC Journal of Biological Inorganic Chemistry, 2006)

The Pleistocene cinder cones surrounding Volcán Colima, Mexico re-visited: eruption ages and volumes, oxidation states, and sulfur content - Ian S. E. Carmichael; Holli M. Frey; Rebecca A. Lange; Chris M. Hall (Bulletin of Volcanology, 2006)

Effects of anti-phencyclidine and anti-(+)-methamphetamine monoclonal antibodies alone and in combination on the discrimination of phencyclidine and (+)-methamphetamine by pigeons - J. R. Daniels; W. D. Wessinger; W. C. Hardwick; M. Li; M. G. Gunnell; C. J. Hall; S. M. Owens; D. E. McMillan (Psychopharmacology, 2006)

Microbial assemblage during the spring‐summer transition on the northeast continental shelf of New Zealand - J. A. Hall; K. Safi; M. R. James; J. Zeldis; M. Weatherhead (New Zealand Journal of Marine and Freshwater Research, 2006)
The northeast shelf of the North Island of New Zealand was sampled on four occasions from early spring to late summer in 1996–97. During this period, tight linkages between the physical and chemical forcings and the response from the microbial food‐web were observed. During bloom conditions in early spring the phytoplankton population was dominated by large diatoms with the picophytoplankton contributing an average of 8% of the phytoplankton biomass. The picophytoplankton fraction increased to contribute a mean of 57% of the phytoplankton biomass in late summer when upwelling had ceased, the water column was strongly stratified and dissolved inorganic nitrogen concentrations were negligible. The changes in the phytoplankton assemblage were accompanied by changes in the microzooplankton population. In early spring the microzooplankton population was dominated by larger species, including copepod nauplii and >20 μm aloricate ciliates, with copepod nauplii contributing up to 50% of the microzooplankton biomass in early and late spring. Peak microzooplankton biomasses of 880–2093 μ g C m ‐2 in the mixed layer occurred in early and late spring, depending on the station. The large ciliate Laboea strobila was an important component of the microzooplankton biomass, and increased substantially at three out of the five stations between early and late spring. Strong upwelling in early summer resulted in substantial decreases in picophytoplankton and microzooplankton abundance. In late summer the composition of microzooplankton population had changed substantially, with the

Composition and Nutritional Characteristics of Fungi Consumed by Callimico goeldii in Pando, Bolivia - Amy M. Hanson; Mary Beth Hall; Leila M. Porter; Barbara Lintzenich (International Journal of Primatology, 2006)

Effect of improved fallow on crop productivity, soil fertility and climate-forcing gas emissions in semi-arid conditions - Nicola M. Hall; Bocary Kaya; Jan Dick; Ute Skiba; Amadou Niang; Ramadjita Tabo (Biology and Fertility of Soils, 2006)

Lake Sediment Core Records of Sulphur Accumulation and Sulphur Isotopic Composition in Central Ontario, Canada Lakes - M. Catherine Eimers; Andrew M. Paterson; Peter J. Dillon; Sherry L. Schiff; Brian F. Cumming; Roland I. Hall (Journal of Paleolimnology, 2006)

Identification of Components of Male-Produced Pheromone of Coffee White Stemborer, Xylotrechus quadripes - D. R. Hall; A. Cork; S. J. Phythian; S. Chittamuru; B. K. Jayarama; M. G. Venkatesha; K. Sreedharan; P. K. Vinod Kumar; H. G. Seetharama; R. Naidu (Journal of Chemical Ecology, 2006)

Effect of coastal boundary resolution and mixing upon internal wave generation and propagation in coastal regions - Philip Hall; Alan M. Davies (Ocean Dynamics, 2005)

Comparison of finite difference and element models of internal tides on the Malin–Hebrides shelf - Philip Hall; Alan M. Davies (Ocean Dynamics, 2005)

Avoiding Dangerous Anthropogenic Interference with the Climate System - Klaus Keller; Matt Hall; Seung-Rae Kim; David F. Bradford; M. Oppenheimer (Climatic Change, 2005)

Predicting Species Response to Disturbance from Size Class Distributions of Adults and Saplings in a Jamaican Tropical Dry Forest - K. P. McLaren; M. A. McDonald; J. B. Hall; J. R. Healey (Plant Ecology, 2005)

Tracing the Movement of Irrigated Effluent into an Alluvial Gravel Aquifer - L. W. Sinton; R. R. Braithwaite; C. H. Hall; L. Pang; M. E. Close; M. J. Noonan (Water, Air, & Soil Pollution, 2005)

The eruptive history of the Tequila volcanic field, western Mexico: ages, volumes, and relative proportions of lava types - Catherine B. Lewis-Kenedi; Rebecca A. Lange; Chris M. Hall; Hugo Delgado-Granados (Bulletin of Volcanology, 2005)

The eruptive history of the Tequila volcanic field, western Mexico: ages, volumes, and relative proportions of lava types - Catherine B. Lewis-Kenedi; Rebecca A. Lange; Chris M. Hall; Hugo Delgado-Granados (Bulletin of Volcanology, 2005)

Managing by‐catch and discards: how much progress are we making and how can we do better? - Stephen J. Hall; Brooke M. Mainprize (Fish and Fisheries, 2005)
There appears to be considerable potential for further reduction in global by‐catch. This reduction is most likely to be achieved by focusing even greater attention on the technical, regulatory and social approaches that are currently practiced. With respect to the technical approaches, meta‐analysis indicates that overall reductions in by‐catch of between 25% and 64% could be achieved if global fishing fleets could match somewhere between the minimum and median performance of gear modifications used in experimental studies. If such benefits are to be delivered, however, engaging fishers more comprehensively in solving the problems will be essential. Further developing legislative and institutional arrangements will also assist. However, notwithstanding the potential gains that can be achieved, it must be recognized that careful analysis will often be required to ensure that a proposed measure will achieve the desired objective at an acceptable cost.

Isopentenyl-diphosphate isomerase is essential for viability of Caenorhabditis elegans - John Yochem; David H. Hall; Leslie R. Bell; Edward M. Hedgecock; Robert K. Herman (Molecular Genetics and Genomics, 2005)

Carbon Dioxide and Methane Production in Small Reservoirs Flooding Upland Boreal Forest - Cory J. D. Matthews; Elizabeth M. Joyce; Vincent L. St. Louis; Sherry L. Schiff; Jason J. Venkiteswaran; Britt D. Hall; R. A. (Drew) Bodaly; Kenneth G. Beaty (Ecosystems, 2005)

Identification of the Herbicide Surflan and Its Active Ingredient Oryzalin, a Dinitrosulfonamide, as Xenoestrogens - L. C. Hall; J. M. Rogers; M. S. Denison; M. L. Johnson (Archives of Environmental Contamination and Toxicology, 2005)

First record of Passalora calotropidis in Australia and its generic position - Peter M. Wilkinson; Skye Thomas-Hall; Thomas S. Marney; Roger G. Shivas (Australasian Plant Pathology, 2005)

JUVENILE HORMONE REGULATES DE NOVO ISOPRENOID AGGREGATION PHEROMONE BIOSYNTHESIS IN PINE BARK BEETLES, Ips SPP., THROUGH TRANSCRIPTIONAL CONTROL OF HMG-CoA REDUCTASE - JULIE A. TILLMAN; FANG LU; LANE M. GODDARD; ZOE R. DONALDSON; SILVER C. DWINELL; CLAUS TITTIGER; GREGORY M. HALL; ANDREW J. STORER; GARY J. BLOMQUIST; STEVEN J. SEYBOLD (Journal of Chemical Ecology, 2004)

Interannual variation of Gulf Stream heat transport in a high-resolution model forced by reanalysis data - N. M. J. Hall; B. Barnier; T. Penduff; J. M. Molines (Climate Dynamics, 2004)

Effect of 6weeks of sprint training on growth hormone responses to sprinting - Keith A. Stokes; Mary E. Nevill; Paul W. Cherry; Henryk K. A. Lakomy; George M. Hall (European Journal of Applied Physiology, 2004)

Modelling tidally induced sediment-transport paths over the northwest European shelf: the influence of sea-level reduction - Philip Hall; Alan M. Davies (Ocean Dynamics, 2004)

Tidal currents, energy flux and bottom boundary layer thickness in the Clyde Sea and North Channel of the Irish Sea - A. M. Davies; P. Hall; M. J. Howarth; P. J. Knight; R. J. Player (Ocean Dynamics, 2004)

Molecular Characterization of Duck Hepatitis B Virus Isolates from South African Ducks - Nomathibane P. Mangisa; Heidi E. Smuts; Anna Kramvis; C. Wendy Linley; Michelle Skelton; Timothy J. Tucker; Pauline De La M. Hall; Del Kahn; Allison R. Jilbert; Michael C. Kew (Virus Genes, 2004)

A Flavanone and Two Phenolic Acids from Chrysanthemum morifolium with Phytotoxic and Insect Growth Regulating Activity - Clifford W. Beninger; Mamdouh M. Abou-Zaid; Adrienne L. E. Kistner; Rebecca H. Hallett; Muhammad J. Iqbal; Bernard Grodzinski; J. Christopher Hall (Journal of Chemical Ecology, 2004)

Peanut Stripe Potyvirus Resistance in Peanut (Arachis Hypogaea L.) Plants Carrying Viral Coat Protein Gene Sequences - Colleen M. Higgins; Rhonda M. Hall; Neena Mitter; Alan Cruickshank; Ralf G. Dietzgen (Transgenic Research, 2004)

Tephrochronology of last termination sequences in Europe: a protocol for improved analytical precision and robust correlation procedures (a joint SCOTAV–INTIMATE proposal) - Chris S. M. Turney; J. John Lowe; Siwan M. Davies; Valerie Hall; David J. Lowe; Stefan Wastegård; Wim Z. Hoek; Brent Alloway (Journal of Quaternary Science, 2004)
The precise sequence of events during the Last Termination (18 000–9000 ka 14 C yr BP), and the extent to which major environmental changes were synchronous, are difficult to establish using the radiocarbon method alone because of serious distortions of the radiocarbon time‐scale, as well as the influences of site‐specific errors that can affect the materials dated. Attention has therefore turned to other methods that can provide independent tests of the chronology and correlation of events during the Last Termination. With emphasis on European sequences, we summarise here the potential of tephrostratigraphy and tephrochronology to fulfil this role. Recent advances in the detection and analysis of ‘hidden’ tephra layers (cryptotephra) indicate that some tephras of Last Termination age are much more widespread in Europe than appreciated hitherto, and a number of new tephra deposits have also been identified. There is much potential for developing an integrated tephrochronological framework for Europe, which can help to underpin the overall chronology of events during the Last Termination. For that potential to be realised, however, there needs to be a more systematic and robust analysis of tephra layers than has been the practice in the past. We propose a protocol for improving analytical and reporting procedures, as well as the establishment of a centralised data base of the results, which will provide an important geochronological tool to support a diverse range of stratigraphical studies, including opportunities to reassess volcanic hazards. Although aimed primarily at Europe, the protocol proposed here is of equal relevance to other regions and periods of interest. Copyright © 2004 John Wiley & Sons, Ltd.

First report of olive knot caused by Pseudomonas savastanoi pv. savastanoi on olives (Olea europaea) in Australia - B. H. Hall; E. J. Cother; M. Whattam; D. Noble; J. Luck; D. Cartwright (Australasian Plant Pathology, 2004)

A precisely‐dated lake‐level rise marked by diatomite formation in northeastern Ireland - G. M. Plunkett; N. J. Whitehouse; V. A. Hall; D. M. Brown; M. G. L. Baillie (Journal of Quaternary Science, 2004)
The intercorrelation of palaeoclimate events from various studies is often hindered by a lack of precise chronological control. Tephra isochrons can overcome this problem by providing direct site linkages. This paper outlines a study of Holocene peat and diatomite deposits that accumulated within the floodplain of Lough Neagh, Northern Ireland. The Icelandic Hekla 4 tephra has been identified at the base of diatomite deposits at a number of sites and provides firm dating evidence for a widespread flooding event in the area at ca. 2300 BC . The evidence is consistent with other studies in Ireland and elsewhere for increased wetness at this time. The results demonstrate that the terrestrial deposits around Lough Neagh contain an important record of Holocene lake‐level change. Dendrochronological evidence from the Lough Neagh area provides additional information about lake‐level fluctuations over the past two millennia. Copyright © 2004 John Wiley & Sons, Ltd.

Response regulator homologues have complementary, light-dependent functions in the Arabidopsis circadian clock - Maria E. Eriksson; Shigeru Hanano; Megan M. Southern; Anthony Hall; Andrew J. Millar (Planta, 2003)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Usp9y (ubiquitin-specific protease 9 gene on the Y) is associated with a functional promoter and encodes an intact open reading frame homologous to Usp9x that is under selective constraint - Nicola M. Hall; Graeme M. Brown; Robert A. Furlong; Carole A. Sargent; Michael Mitchell; Dominique Rocha; Nabeel A. Affara (Mammalian Genome, 2003)

Complete Genomic Sequence of the Australian South-West Genotype of Sindbis Virus: Comparisons with Other Sindbis Strains and Identification of a Unique Deletion in the 3′-Untranslated Region - Suha M. Saleh; Michael Poidinger; John S. Mackenzie; Annette K. Broom; Michael D. Lindsay; Roy A. Hall (Virus Genes, 2003)

Minor Components in the Sex Pheromone of Legume Podborer: Maruca vitrata Development of an Attractive Blend - M. C. A. Downham; D. R. Hall; D. J. Chamberlain; A. Cork; D. I. Farman; M. Tamò; D. Dahounto; B. Datinon; S. Adetonah (Journal of Chemical Ecology, 2003)

Building the infrastructure for nationwide cancer surveillance and control – a comparison between The National Program of Cancer Registries (NPCR) and The Surveillance, Epidemiology, and End Results (SEER) Program (United States) - Phyllis A. Wingo; Patricia M. Jamison; Robert A. Hiatt; Hannah K. Weir; Paul M. Gargiullo; Mary Hutton; Nancy C. Lee; H. Irene Hall (Cancer Causes & Control, 2003)

Spatial Variation and Correlations of Mercury Levels in the Terrestrial and Aquatic Components of a Wetland Dominated Ecosystem: Kejimkujik Park, Nova Scotia, Canada - A. N. Rencz; N. J. O'Driscoll; G. E. M. Hall; T. Peron; K. Telmer; N. M. Burgess (Water, Air, & Soil Pollution, 2003)

Multiproxy Devensian Late‐glacial and Holocene environmental records at an Atlantic coastal site in Shetland - Graeme Whittington; Paul Buckland; Kevin. J. Edwards; Malcolm Greenwood; Adrian M. Hall; Marie Robinson (Journal of Quaternary Science, 2003)
Marine erosion at Clettnadal, West Burra island off the west coast of Shetland, caused the drainage of a small water body at Clettnadal, exposing deposits of Late Devensian and Holocene age. Pollen, diatom and invertebrate analyses have provided variable records of environmental change during stratigraphical event GI‐1. Event GS‐1 is revealed by the non‐pollen evidence, especially by Coleoptera, by sediment stratigraphy, and by radiocarbon dating. In contrast, the pollen evidence indicates that an arctic tundra flora, in which dwarf shrubs were prominent, persisted throughout the Late‐glacial. The Holocene brought colonisation by tree birch, but by ca. 9000 14 C yr BP the taxon had almost disappeared. This contrasts strongly with other Holocene pollen records for Shetland where both Betula and Corylus avellana ‐type survived longer—at some sites, for example, until ca. 2900 yr BP. The extreme westerly and exposed coastal situation of Clettnadal appears to be responsible both for a muted Late‐glacial response in the pollen record of terrestrial vegetation and for the early replacement of woodland by a maritime grassland. The results provoke questions concerning biological stability at times of marked climatic change. Copyright © 2003 John Wiley & Sons, Ltd.

Fragmentation of Florida scrub in an urban landscape - Jaclyn M. Hall; Thomas W. Gillespie; Donald Richardson; Steven Reader (Urban Ecosystems, 2002)

Isotopic Characterization of Six Major Brands of White Basic Lead Carbonate Paint Pigments - M. B. Rabinowitz; G. S. Hall (Bulletin of Environmental Contamination and Toxicology, 2002)

The energetics of autumn mast hoarding in eastern chipmunks - Murray M. Humphries; Donald W. Thomas; Carolyn L. Hall; John R. Speakman; Donald L. Kramer (Oecologia, 2002)

Global Distribution of Halogenated Dimethyl Bipyrroles in Marine Mammal Blubber - S. Tittlemier; A. Borrell; J. Duffe; P. J. Duignan; P. Fair; A. Hall; P. Hoekstra; K. M. Kovacs; M. M. Krahn; M. Lebeuf; C. Lydersen; D. Muir; et al. (Archives of Environmental Contamination and Toxicology, 2002)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Analysis of the growth of rimu (Dacrydium cupressinum) in South Westland, New Zealand, using process-based simulation models - David Whitehead; Graeme M. Hall; Adrian S. Walcroft; Kim J. Brown; Joe J. Landsberg; David T. Tissue; Matthew H. Turnbull; Kevin L. Griffin; William S. Schuster; Fiona E. Carswell; Craig M. Trotter; Ian L. James; et al. (International Journal of Biometeorology, 2002)

IR spectroelectrochemical study of the binding of carbon monoxide to the active site of Desulfovibrio fructosovorans Ni-Fe hydrogenase - Antonio L. De Lacey; Christian Stadler; Victor M. Fernandez; Claude E. Hatchikian; Hua-Jun Fan; Shuhua Li; Michael B. Hall (JBIC Journal of Biological Inorganic Chemistry, 2002)

Midgut tissue of male pine engraver, Ips pini, synthesizes monoterpenoid pheromone component ipsdienol de novo - Gregory M. Hall; Claus Tittiger; Gracie L. Andrews; Grant S. Mastick; Marilyn Kuenzli; Xin Luo; Steven J. Seybold; Gary J. Blomquist (The Science of Nature, 2002)

Copper and Manganese Influence the Uptake of Cadmium in Marine Macroalgae - M. J. Hall; M. T. Brown (Bulletin of Environmental Contamination and Toxicology, 2002)

Sedimentology, palaeoecology and geochronology of Marine Isotope Stage 5 deposits on the Shetland Islands, Scotland - Adrian M. Hall; John E. Gordon; Graeme Whittington; Geoffrey A. T. Duller; Hendrik Heijnis (Journal of Quaternary Science, 2002)
New stratigraphical, palynological and dating evidence is presented for pre‐Late Devensian/Weichselian sediments at Fugla Ness and Sel Ayre, Shetland. The Fugla Ness Peat rests on till and formed during an interglacial that saw the development of maritime heaths, with scattered trees and shrubs, including Pinus and possibly Ilex . A decline into stadial conditions is marked by overlying periglacial breccia and till. The Sel Ayre Organic Sands and Gravels lie between periglacial breccias and beneath till and appear to record a changing interstadial environment in which trees were absent and the vegetation comprised largely heaths, with Bruckenthalia , and grasslands. The Fugla Ness Peat is dated to 110+40/−35 ka by uranium series disequilibrium, suggesting that it formed during the Ipswichian/Eemian Interglacial (Marine Isotope Substage 5e). Luminescence ages of ca. 98–105 ka on intercalated sands within the Sel Ayre Organic Sands and Gravels place these deposits in Marine Isotope Substage 5c (Brørup Interstadial). The two sites provide the first detailed record of Marine Isotope Stage 5 environments on Shetland. Copyright © 2002 John Wiley & Sons, Ltd.

Kiddo, a new transposable element family closely associated with rice genes - G. Yang; J. Dong; M. Chandrasekharan; T. Hall (Molecular Genetics and Genomics, 2001)

Control of Nosocomial Multiresistant Enterobacteriaceae Using a Temporary Restrictive Antibiotic Agent Policy - M. Leverstein-van Hall; A. Fluit; H. Blok; A. Box; E. Peters; A. Weersink; J. Verhoef (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Visualisation of metal deposition in biofilm reactors by three-dimensional magnetic resonance imaging (MRI) - Kevin P. Nott; M. Paterson-Beedle; Lynne E. Macaskie; Laurance D. Hall (Biotechnology Letters, 2001)

Formulation and Evaluation of IMS, an Interactive Three-Dimensional Tropospheric Chemical Transport Model 3. Comparison of Modelled C2–C5 Hydrocarbons with Surface Measurements - K.-Y. Wang; J. A. Pyle; D. E. Shallcross; S. M. Hall (Journal of Atmospheric Chemistry, 2001)

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

Female Sex Pheromone of Brinjal Fruit and Shoot Borer, Leucinodes orbonalis Blend Optimization - A. Cork; S. N. Alam; A. Das; C. S. Das; G. C. Ghosh; D. I. Farman; D. R. Hall; N. R. Maslen; K. Vedham; S. J. Phythian; F. M. A. Rouf; K. Srinivasan (Journal of Chemical Ecology, 2001)

Mapping the Potential Sensitivity of Surface Waters to Acidification Using Measured Freshwater Critical Loads as an Indicator of Acid Sensitive Areas - J. M. Ullyett; J. R. Hall; M. Hornung; M. Kernan (Water, Air, & Soil Pollution, 2001)

Variation in Freshwater Critical Loads Across Two Upland Catchments in the UK: Implications for Catchment Scale Management - M. Kernan; J. Hall; J. Ullyet; T. Allott (Water, Air, & Soil Pollution, 2001)

Strategies to estimate national forest carbon stocks from inventory data: the 1990 New Zealand baseline - Graeme M. J. Hall; Susan K. Wiser; Robert B. Allen; Peter N. Beets; Chris J. Goulding (Global Change Biology, 2001)
Summary An estimate of live tree carbon stored in New Zealand forests at 1990 was made to partially satisfy New Zealand's international obligations under the Framework Convention for Climate Change. A national database was compiled of 4956 forest inventory plots measured as recently as possible to 1990. Plot biomass estimates were obtained by applying species allometric relationships derived from harvested stands. Forest areas and classes were taken from a 1987 national map of vegetation cover. Regularly spaced grids, based on an initial 1 km × 1 km grid, were overlaid on the total forest area and plots were tested for bias against site characteristics at the grid points. As grid point density and sample size increased, bias was minimal in regional sampling intensity and in total annual precipitation. Differences in mean elevation and annual temperature remained stable as grid point density increased, and showed little correlation with stem biomass. This sampling method gave a measure of precision not available from previous estimates. An efficient sample size to estimate the mean within a 5% level of precision (at 95% probability) required a sample of 574 plots selected from a 4‐km grid. This strategy generated a mean estimate for the 1990 New Zealand forest carbon biomass of 179.3 ± 4.9 Mg ha −1 (± SE), totalling 919.1 ± 25.1 Mt for the 5.1 million ha mapped forest area. The mean was 6–10% lower than previous estimates, and was within the range reported for other countries. Within forest classes, mean carbon biomass ranged from 105 Mg ha −1 in pure podocarp forest to 215 Mg ha −1 in mixed lowland podocarp–broadleaved–beech forest. Of the major taxa groups throughout the forest estate, beech ( Nothofagus ) contributed 60% of the national forest carbon biomass reservoir, 26.7% was in other hardwoods, 13.2% in conifers, and 0.1% in other taxa (e.g. tree ferns).

Contributions of genetic drift and negative selection on the evolution of three strains of wheat streak mosaic tritimovirus - I.-R. Choi; J. S. Hall; M. Henry; L. Zhang; G. L. Hein; R. French; D. C. Stenger (Archives of Virology, 2001)

Production of a recombinant human basic fibroblast growth factor with a collagen binding domain - J. A. Andrades; J. A. Santamara; L. T. Wu; F. L. Hall; M. E. Nimni; J. Becerra (Protoplasma, 2001)

The Effect of Temperature on Variation in Transmission of a BYDV PAV-like isolate by Clones of Rhopalosiphum Padi and Sitobion Avenae - I.N. Smyrnioudis; R. Harrington; M. Hall; N. Katis; S.J. Clark (European Journal of Plant Pathology, 2001)

Fluorescence in situ hybridization of single copy transgenes in rice chromosomes - Pushpa Kharb; Jinjiang Dong; M. N. Islam-Faridi; David M. Stelly; Timothy C. Hall (In Vitro Cellular & Developmental Biology - Plant, 2001)

Phenetic analysis shows conspecificity between Hispaniolan Viola domingensis Urban and North American Viola macloskeyi sensu lato (Violaceae) - Harvey E. Ballard; Dale A. Casamatta; Melissa M. Hall; Ross A. McCauley; Maria Claudia; Segovia-Salcedo; Robert G. Verb (Brittonia, 2001)

Novel genotypes ofPhytophthora infestans in Canada during 1994 and 1995 - R. D. Peters; H. Förster; H. W. (Bud) Platt; R. Hall; M. D. Coffey (American Journal of Potato Research, 2001)

Value of Terminal Subculture of Automated Blood Cultures in Patients with Candidaemia - A. Borst; M. Leverstein-Van Hall; J. Verhoef; A. Fluit (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

A high-resolution record of mire development and climatic change spanning the Late-glacial-Holocene boundary at Church Moss, Davenham (Cheshire, England) - P. D. M. Hughes; H. K. Kenward; A. R. Hall; F. D. Large (Journal of Quaternary Science, 2000)

PCR rescue and analysis of transgene sequences directly from crude extracts of transgenic embryos and plants - C. M. Higgins; R. M. Hall; P. R. Campbell; R. G. Dietzgen (Plant Molecular Biology Reporter, 2000)

Escherichia coli ß-galactosidase is heterogeneous with respect to a requirement for magnesium - Douglas B. Craig; Tara Hall; Douglas M. Goltz (BioMetals, 2000)

Transgene silencing in monocots - Lakshminarayan M. Iyer; Siva P. Kumpatla; Mahesh B. Chandrasekharan; Timothy C. Hall (Plant Molecular Biology, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Duetting and mate-guarding in Australian magpie-larks ( Grallina cyanoleuca) - M. L. Hall; R. D. Magrath (Behavioral Ecology and Sociobiology, 2000)

Mass sedimentation of picoplankton embedded in organic aggregates - Anya M. Waite; Karl A. Safi; Julie A. Hall; Scott D. Nodder (Limnology and Oceanography, 2000)
During a survey cruise crossing the Subtropical Front over the Chatham Rise east of New Zealand, we made the first observation in High Nutrient Low Chlorophyll waters of massive sedimentation of picoplankton embedded in large (>0.5 mm diam.) organic aggregates (OAs) sensu Riley (1963). We estimate 9.3 mg C m ‐2 yr ‐1 of prokaryotic picoplankton biomass alone may be transported below the euphotic zone via this mechanism. Using confocal microscopy, we made direct observations of picoplankton within undisrupted individual OAs, collected in sediment traps fitted with acrylimide gels, which largely conserved particle structure. Prokaryotic picoplankton autofluoresc‐ence was well‐preserved and concentrations were extremely high within large rapidly sedimenting aggregates, ranging from 1.06 × 10 8 ml ‐1 in the 120 m sediment traps in subantarctic waters to 7.5 × 10 6 ml ‐1 at 550 m in subtropical waters, yielding Enrichment Factors of 10 3 — 10 5 relative to picoplankton concentrations in the water column. Aggregate picoplankton concentrations showed a well‐constrained exponential decline with depth, which we speculate may represent an estimate of protozoan grazing rate within the aggregates. Picoplankton were found within heterotrophic flagellates, within copepod fecal pellets, and within organic matrices, all of which were incorporated in OAs. The key event of picoplankton incorporation into initial particles occurs in the upper water column, very likely through grazing with low assimilation efficiency. Once OAs are formed, their changing porosity and reduction in picoplankton cell numbers via heterotrophy is likely to be a key factor mediating picoplankton carbon fluxes in moderately productive ecosystems, and in determining the overall particle structure of sedimenting OAs.

Mus and Peromyscus chromosome homology established by FISH with three mouse paint probes - Wallace D. Dawson; S. Robert Young; Zongren Wang; Linda W. Liu; Ira F. Greenbaum; Lisa M. Davis; Bryan K. Hall (Mammalian Genome, 1999)

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.

Glucose, and not sucrose, is transported from wheat to wheat powdery mildew - P. N. Sutton; M. J. Henry; J. L. Hall (Planta, 1999)

Comparibility of Results Obtained by the Use of Different Selective Extraction Schemer for the Determination of Element Forms in Soils - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1999)

The effect of ethylene and cytokinin on guanosine 5′-triphosphate binding and protein phosphorylation in leaves of Arabidopsis thaliana - G. V. Novikova; I. E. Moshkov; A. R. Smith; O. N. Kulaeva; M. A. Hall (Planta, 1999)

Development of a Mercury Vapour Air Analyser for Measurement of Hg in Solution - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1999)

Specificity of Response to Sex Pheromones Among Sweetpotato Weevils, Cylas puncticollis and C. brunneus - M. C. A. Downham; N. E. J. M. Smit; P. O. Laboke; D. R. Hall; D. I. Farman; A. Braun; B. Odongo (Journal of Chemical Ecology, 1999)

Temporal variations in dissolved selenium in Lake Kinneret (Israel) - Ami Nishri; Itschak B. Brenner; Gwendy E. M. Hall; Howard E. Taylor (Aquatic Sciences, 1999)

Effects of isolation-rearing on voluntary consumption of ethanol, sucrose and saccharin solutions in Fawn Hooded and Wistar rats - F. S. Hall; S. Huang; A. Pert; M. Linnoila; G. W. Fong (Psychopharmacology, 1998)

Effects of isolation-rearing on locomotion, anxiety and responses to ethanol in Fawn Hooded and Wistar rats - F. S. Hall; S. Huang; G. W. Fong; A. Pert; M. Linnoila (Psychopharmacology, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Late Holocene eruptive activity at Nevado Cayambe Volcano, Ecuador - P. Samaniego; M. Monzier; C. Robin; M. L. Hall (Bulletin of Volcanology, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

The Electronic Encapsulation of Knowledge for Groundwater Quality Management - N. Kukurić; M. J. Hall (Water Resources Management, 1998)

The global carbon sink: a grassland perspective - J. M. O. Scurlock; D. O. Hall (Global Change Biology, 1998)
The challenge to identify the biospheric sinks for about half the total carbon emissions from fossil fuels must include a consideration of below‐ground ecosystem processes as well as those more easily measured above‐ground. Recent studies suggest that tropical grasslands and savannas may contribute more to the ‘missing sink’ than was previously appreciated, perhaps as much as 0.5 Pg (= 0.5 Gt) carbon per annum. The rapid increase in availability of productivity data facilitated by the Internet will be important for future scaling‐up of global change responses, to establish independent lines of evidence about the location and size of carbon sinks.

The effect of elevated CO 2 concentration and soil pH on the relationship between plant growth and rhizosphere denitrification potential - J. M. Hall; E. Paterson; K. Killham (Global Change Biology, 1998)
The effect of CO 2 concentration on plant growth and the size of the rhizosphere denitrifier population was investigated for ryegrass grown at 3 different soil pH values (pH 4.3, 5.9 and 7.0). Soil microcosms were planted with ryegrass and maintained under constant growth conditions at either ambient (450ppm) or elevated (720ppm) CO 2 concentration. At harvest, the rhizosphere soil was collected and subjected to a potential denitrification assay to provide an estimate of the size of the denitrifier population present. Ryegrass dry matter production varied across the pH range studied and contrary to other studies, elevated CO 2 concentration did not consistently increase growth. Plant growth was reduced by ≈ 35% and 23% at pH 4.3 and pH 5.9, respectively, under elevated CO 2 concentration. At pH 7.0, however, plant growth was increased by ≈ 45% under elevated CO 2 . Potential denitrification rates within the rhizosphere followed a similar pattern to plant growth in the different treatments, suggesting that plant growth and the size of denitrifier population within the rhizosphere are coupled. This study investigates the relationship between plant growth and rhizosphere denitrification potential, thereby providing an estimate of the size of the denitrifier population under increased CO 2 concentration and soil pH.

The role of striatal dopaminergic mechanisms in rotational behavior induced by phencyclidine and phencyclidine-like drugs - A. Mele; Krystyna M. Wozniak; F. S. Hall; A. Pert (Psychopharmacology, 1998)

A Computational Analysis of FXa Generation by TF:FVIIa on the Surface of Rat Vascular Smooth Muscle Cells - Connie L. Hall; Steven M. Slack; Vincent T. Turitto (Annals of Biomedical Engineering, 1998)

The utility of visible implant (VI) tags for marking tropical river fish - HALLS; M. E. AZIM (Fisheries Management and Ecology, 1998)
In tropical fisheries where ageing fish is often difficult, tagging programmes offer an important means to estimate growth parameters and mortality rates. The majority of tags are large and attached externally via a puncture in the muscle. These characteristics may cause significant biological effects which bias parameter estimates. Visible implant (VI) tags offer a more benign means to individually mark fish. The utility of VI tags for marking five species of tropical river fish was examined. The results indicate that the tag and tagging operation had no influence on either growth or mortality, although tag retention was poor compared with other studies. For three of the five species, the only suitable tagging location was highly inconspicuous and therefore inappropriate for tagging programmes that rely upon fishermen to return tagged fish. Alternative tagging locations may improve retention rates and the visibility of the tag.

A genetic linkage map of cowpea (Vigna unguiculata) developed from a cross between two inbred, domesticated lines - C. M. Menéndez; A. E. Hall; P. Gepts (Theoretical and Applied Genetics, 1997)

Food as the Dominant Pathway of Methylmercury Uptake by Fish - B. D. Hall; R. A. Bodaly; R. J. P. Fudge; J. W. M. Rudd; D. M. Rosenberg (Water, Air, & Soil Pollution, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Needle biopsy of liver in a marine teleost, Pagrus auratus (Bloch & Schneider) - A.R. Dyer; P. De La M Hall; G.I. Matsumoto (Journal of Fish Diseases, 1997)

Comparison of two reagents, sodium pyrophosphate and sodium hydroxide, in the extraction of labile metal organic complexes - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1997)

Use of polymerase chain reaction and antibody tests in the diagnosis of vertically transmitted hepatitis C virus infection - S. L. Thomas; M. L. Newell; C. S. Peckham; A. E. Ades; A. J. Hall (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Chronic Toxicity of Atrazine to Sago Pondweed at a Range of Salinities: Implications for Criteria Development and Ecological Risk - L. W. Hall Jr; R. D. Anderson; M. S. Ailstock (Archives of Environmental Contamination and Toxicology, 1997)

Comparison of the Water Transporting Properties of MIP and AQP1 - G. Chandy; G.A. Zampighi; M. Kreman; J.E. Hall (The Journal of Membrane Biology, 1997)

Fibromyalgia antirheumatic drug trials: Effects of a standardized instructional videotape on the reliability of observer-dependent outcome measures - N. Bellamy; R. Buchbinder; S. Hall; P. Lowthian; M. R. Patrick; P. F. J. Ryan; A. Stockman; G. Grant; S. Green; J. Campbell (Inflammopharmacology, 1997)

The effect of ethylene on GTP binding in extracts from pea epicotyls - G. Novikova; I. Moshkov; A. R. Smith; M. A. Hall (Planta, 1997)

Comparing past and present trophic states of seven Central Volcanic Plateau lakes, New Zealand - N. M. Burns; J. Deely; J. Hall; K. Safi (New Zealand Journal of Marine and Freshwater Research, 1997)
Data on seven lakes in the Rotorua District were examined to determine trophic state changes in these lakes. The method of data analysis was specifically designed to find small changes in the trophic state of lakes. For each variable, the P‐ value from 12 monthly paired sample Student t‐ test comparisons was calculated and a change of trophic state value (CTS) was assigned, based on the P‐value. The CTS values for all the variables examined for a single lake were averaged (C) with a standard error (CV). The resulting Change/ Confidence Value index (C/CV) indicated the nature of the trophic change observed and the degree of confidence that could be placed in the stated change. This study finds that in recent years Lakes Rotorua and Rotoiti have become less eutrophic; Lakes Okareka and Rotoma may have become less eutrophic; Lakes Okataina and Rotokakahi have not changed in trophic state in the last 22 years, and Lake Tikitapu may have become more eutrophic.

The application of biological pesticides: Limitations and a practical solution - A. C. Chapple; R. A. Downer; T. M. Wolf; R. A. J. Taylor; F. R. Hall (BioControl, 1996)

Structure and floristics of Bangladesh homegardens - M. D. Millate-E-Mustafa; John B. Hall; Zewge Teklehaimanot (Agroforestry Systems, 1996)

The influence of salinity on the chronic toxicity of atrazine to an estuarine copepod: Implications for development of an estuarine chronic criterion - L. W. Hall; M. C. Ziegenfuss; R. D. Anderson; D. P. Tierney (Archives of Environmental Contamination and Toxicology, 1995)

A novel complex formed between the flavivirus E and NS1 proteins: analysis of its structure and function - B. J. Blitvich; J. S. Mackenzie; R. J. Coelen; M. J. Howard; R. A. Hall (Archives of Virology, 1995)

Arboviruses causing human disease in the Australasian zoogeographic region - J. S. Mackenzie; M. D. Lindsay; R. J. Coelen; A. K. Broom; R. A. Hall; D. W. Smith (Archives of Virology, 1994)

Distribution and characterization of mutations induced by nitrous acid or hydroxylamine in the intron-containing thymidylate synthase gene of bacteriophage T4 - Michael D. Brown; Christine M. Povinelli; Dwight H. Hall (Biochemical Genetics, 1993)

Distribution and characterization of mutations induced by nitrous acid or hydroxylamine in the intron-containing thymidylate synthase gene of bacteriophage T4 - Michael D. Brown; Christine M. Povinelli; Dwight H. Hall (Biochemical Genetics, 1993)

Human herpesvirus-6 strain groups: a nomenclature - D. Ablashi; H. Agut; Z. Berneman; G. Campadelli-Fiume; D. Carrigan; L. Ceccerini-Nelli; B. Chandran; S. Chou; H. Collandre; R. Cone; T. Dambaugh; S. Dewhurst; et al. (Archives of Virology, 1993)

The influence of contaminant and water quality conditions on larval striped bass in the Potomac River and upper Chesapeake Bay in 1990: Anin situ study - Lenwood W. Hall; Michael C. Ziegenfuss; Steven A. Fischer; John A. Sullivan; Deborah M. Palmer (Archives of Environmental Contamination and Toxicology, 1993)

Pathogenesis of a phleboviral infection (Punta Toro virus) in golden Syrian hamsters - G. W. Anderson; M. V. Slayter; W. Hall; C. J. Peters (Archives of Virology, 1990)

Effects of chlorinated benzenes on diatom fatty acid composition and quantitative morphology. III. 1,2,3-Trichlorobenzene - L. Sicko-Goad; J. Hall; D. Lazinsky; M. S. Simmons (Archives of Environmental Contamination and Toxicology, 1989)

Effects of chlorinated benzenes on diatom fatty acid composition and quantitative morphology. II. 1,3,5-Trichlorobenzene - L. Sicko-Goad; J. Hall; D. Lazinsky; M. S. Simmons (Archives of Environmental Contamination and Toxicology, 1989)

Effects of chlorinated benzenes on diatom fatty acid composition and quantitative morphology. I. 1,2,4-Trichlorobenzene - L. Sicko-Goad; D. Lazinsky; J. Hall; M. S. Simmons (Archives of Environmental Contamination and Toxicology, 1989)

Effects of chlorinated benzenes on diatom fatty acid composition and quantitative morphology. IV. Pentachlorobenzene and comparison with trichlorobenzene isomers - L. Sicko-Goad; M. S. Evans; D. Lazinsky; J. Hall; M. S. Simmons (Archives of Environmental Contamination and Toxicology, 1989)

Isolation and characterization of dengue viruses serotype 1 from an epidemic in northern Queensland, Australia - J. Blok; B. H. Kay; R. A. Hall; B. M. Gorman (Archives of Virology, 1988)

Occurrence of bovine herpesvirus-1 DNA in nucleosomes and chromatin of bovine herpesvirus-1-infected cells: identification of a virion-associated protein in chromatin of infected cells - B. S. Seal; J. D. Martinez; M. R. Hall; S. C. St. Jeor (Archives of Virology, 1988)

Pixe analysis of reproductive fluids - Gene S. Hall; Robert M. Shelden (Biological Trace Element Research, 1987)

Changes in zinc metabolism following exercise in human subjects - Andre M. van Rij; Michael T. Hall; G. Lynis Dohm; John Bray; Walter J. Pories (Biological Trace Element Research, 1986)

Incidence of inherited enzyme activity variants in feral mouse populations - Grahame Bulfield; Jean M. Hall; Spyros Tsakas (Biochemical Genetics, 1984)

Correlation of guanosine triphosphate cyclohydrolase activity and the synthesis of pterins in Drosophila melanogaster - C. L. Fan; L. M. Hall; A. J. Skrinska; G. M. Brown (Biochemical Genetics, 1976)

Products of the oxidation of selected alkanes by a gram-negative bacterium - M. Y. Ali Khan; A. N. Hall; D. S. Robinson (Antonie van Leeuwenhoek, 1964)